Olefin-based resin, method for producing olefin-based resin, resin composition, molded body, package for lithium ion battery, and power storage device
Patent Information
- Application Number
- CN202580023333.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-27
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]作为聚烯烃系树脂材料,多使用丙烯系聚合物和乙烯系聚合物,但两者不相溶,因此,即使想要将它们混合并再生利用,也不会均匀地分散,物性降低,存在用途受限这样的问题
根据本发明,可以提供作为丙烯系聚合物与乙烯系聚合物的相容剂有用的新型烯烃系树脂,以及提供该烯烃系树脂的用途。另外,根据本发明,可以提供包含丙烯系聚合物和乙烯系聚合物、并且耐冲击性与伸长率的均衡性或耐冲击性与强度的均衡性得到改善的树脂组合物及成型体、锂离子电池用包装体及蓄电装置。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to olefin resins, methods for manufacturing olefin resins, resin compositions, molded articles, packaging for lithium-ion batteries, and energy storage devices. Background Technology
[0002] Plastic products are used in various fields, among which products made of polyolefin resins are widely used as various containers and are produced in large quantities. In recent years, the recycling of plastic products has been promoted, but further recycling is required for used products and waste plastics made of polyolefin resins.
[0003] As polyolefin resin materials, propylene-based polymers and ethylene-based polymers are commonly used. However, these two polymers are immiscible, so even if they are to be mixed and recycled, they will not be uniformly dispersed, resulting in reduced physical properties and limited applications. Therefore, it is desirable to develop methods that make propylene-based polymers miscible or compatible with ethylene-based polymers.
[0004] As methods for making propylene-based polymers and ethylene-based polymers compatible or soluble, methods have been proposed such as using crystalline block composites comprising i) crystalline ethylene-based polymers, ii) crystalline propylene-based polymers, and iii) block copolymers having crystalline ethylene-based blocks and crystalline propylene blocks (see Patent Documents 1-4), using plastic bodies of ethylene-α-olefin copolymers having specific weight-average molecular weights, densities, and crystallinity (see Patent Document 5), using thermoplastic random copolymers comprising ethylene and propylene with specific melting points obtained using specific catalysts (see Patent Document 6), and recently, olefin resins comprising grafted olefin polymers have been proposed (see Patent Documents 7 and 8), etc.
[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Publication No. 2016-537449 Patent Document 2: Japanese Patent Application Publication No. 2019-116638 Patent Document 3: Japanese Patent No. 5860043 Patent Document 4: Japanese Patent No. 6783851 Patent Document 5: Japanese Patent Publication No. 6-511028 Patent Document 6: Japanese Patent No. 5466986 Patent Document 7: Japanese Patent Publication No. 2022-548039 Patent Document 8: International Publication No. 2023 / 101004 Summary of the Invention
[0006] The problem that the invention aims to solve However, there is room for improvement in the balance between impact resistance and elongation, or between impact resistance and strength, of the compatibilizers already reported. The object of this invention is to provide a novel olefin-based resin useful as a compatibilizer for propylene-based and ethylene-based polymers, and to provide uses for this olefin-based resin. Furthermore, the object of this invention is to provide resin compositions and molded articles, lithium-ion battery packaging, and energy storage devices that comprise propylene-based and ethylene-based polymers and exhibit improved balance between impact resistance and elongation, or between impact resistance and strength.
[0007] Methods for solving problems The present invention relates to, for example, the following [1] to
[29] .
[0008] [1] Olefin resins (β), comprising grafted olefin polymers having a main chain and side chains [R1], The olefin resin (β) satisfies all of the following requirements (I) to (IV): (I) The main chain of the aforementioned grafted olefin polymer [R1] is composed of ethylene-propylene copolymer or ethylene-1-butene copolymer; (II) The side chains of the aforementioned grafted olefin polymer [R1] are composed of propylene homopolymer or propylene-ethylene copolymer; (III) The total content of P of the following components (i) to (iv) in the aforementioned olefin resin (β) is in the range of 10 to 80% by mass: (i) Propylene homopolymers constituting the side chains of the aforementioned grafted olefin polymer [R1]; (ii) A propylene-ethylene copolymer constituting the side chain of the aforementioned grafted olefin polymer [R1]; (iii) Terminal unsaturated propylene homopolymers that do not constitute the aforementioned grafted olefin polymer [R1]; (iv) Terminally unsaturated propylene-ethylene copolymers that do not constitute the aforementioned grafted olefin polymer [R1]; (IV) The intrinsic viscosity [η] of the aforementioned olefin resin (β) was measured at 135 °C in decahydronaphthalene and was 0.5~5.0 dL / g.
[0009] [2] The olefin resin (β) as described in [1], wherein the main chain of the aforementioned grafted olefin polymer [R1] is an ethylene-propylene copolymer. The content of ethylene-derived structural units in the aforementioned ethylene-propylene copolymer is 70-99 mol%. The content of propylene-derived structural units in the aforementioned ethylene-propylene copolymer is 1 to 30 mol.
[0010] [3] The olefin resin (β) as described in [2], wherein the weight-average molecular weight (Mw) of the ethylene-propylene copolymer constituting the main chain of the aforementioned grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in the form of a value converted to polyethylene, is 50,000 to 250,000.
[0011] [4] The olefin resin (β) as described in [2] or [3], wherein the total content of P of the components (i) to (iv) in the olefin resin (β) is 10 to 60 by mass.
[0012] [5] The olefin resin (β) as described in any one of [2] to [4], wherein the melt flow rate (MFR) of the aforementioned olefin resin (β), as determined in accordance with ASTM D1238 at 190°C and a load of 2.16 kg, is 0.01 to 30 g / 10 min.
[0013] [6] An olefinic resin (β) as described in any one of [2] to [5], wherein the content of the ethylene-derived structural units of the aforementioned ethylene-propylene copolymer is 75 to 85 mol%. The content of propylene-derived structural units in the aforementioned ethylene-propylene copolymer is 15-25 mol%. The intrinsic viscosity [η] of the aforementioned olefin resin (β), measured at 135 °C in decahydronaphthalene, is 0.9~1.25 dL / g.
[0014] [7] The olefin resin (β) as described in [1], wherein the main chain of the aforementioned grafted olefin polymer [R1] is an ethylene-1-butene copolymer. The content of ethylene-derived structural units in the aforementioned ethylene-1-butene copolymer is 70-90 mol%. The content of structural units derived from 1-butene in the aforementioned ethylene-1-butene copolymer is 10-30 mol%. The weight-average molecular weight (Mw) of the aforementioned ethylene-1-butene copolymer, calculated using gel permeation chromatography (GPC) in terms of polyethylene equivalents, is 30,000 to 120,000.
[0015] [8] The olefin resin (β) as described in [7], wherein the melt flow rate (MFR) of the aforementioned olefin resin (β), as determined according to ASTM D1238 at 190°C and a load of 2.16 kg, is 2.5 to 30 g / 10 min.
[0016] [9] An olefinic resin (β) as described in [7] or [8], wherein the content of the ethylene-derived structural units of the aforementioned ethylene-1-butene copolymer is 78-87 mol%. The content of the structural units derived from 1-butene in the aforementioned ethylene-1-butene copolymer is 13 to 22 mol.
[0017]
[10] The olefin resin (β) as described in any one of [7] to [9], wherein the intrinsic viscosity [η] of the aforementioned olefin resin (β), as measured in decahydronaphthalene at 135°C, is 0.5 to 1.25 dL / g.
[0018]
[11] The olefin resin (β) as described in any one of [1] to
[10] , wherein the content of propylene-derived structural units in the side chains of the aforementioned grafted olefin polymer [R1] is 80 to 100 mol%. The content of ethylene-derived structural units in the side chains of the aforementioned grafted olefin polymer [R1] is 0-20 mol%. The weight-average molecular weight (Mw) of the aforementioned polymers or copolymers constituting the side chains of the aforementioned grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is in the range of 5,000 to 50,000.
[0019] A method for manufacturing the olefinic resin (β) according to any one of
[12] [1] to
[11] , comprising the steps of (A) and (B) below: (A) In the presence of a catalyst for olefin polymerization containing a transition metal compound [A] of Group 4 of the periodic table, which includes a ligand having a dimethylsilyl diindenyl skeleton, The process of polymerizing propylene to produce terminally unsaturated polypropylene, or the process of copolymerizing propylene with ethylene to produce terminally unsaturated propylene-ethylene copolymer. (B) In the presence of a catalyst for olefin polymerization containing a bridged metallocene compound represented by the following general formula [B], The process of copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer manufactured in step (A) with ethylene and propylene, or the process of copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer manufactured in step (A) with ethylene and 1-butene.
[0020] [Chemical Formula 1] (In formula [B], R) 1 R 2 R 3 R 4 R 5 R8 R 9 and R 12 Each independently represents a hydrogen atom, a hydrocarbon group, a silicon-containing group, or a group containing heteroatoms other than a silicon-containing group, R 1 ~R 4 Two adjacent groups in R can bond with each other to form a ring. 6 and R 11 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 7 and R 10 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 6 and R 7 They can bond together to form a ring, R 10 and R 11 They can bond together to form a ring; however, R is not included. 6 R 7 R 10 and R 11 The case where all atoms are hydrogen. R 13 and R 14 Each aryl group is represented independently. Y 1 This represents a carbon atom or a silicon atom. M 1 This represents a zirconium or hafnium atom. Q represents a halogen atom, a hydrocarbon group, a halohydrocarbon group, a neutral conjugated or non-conjugated diene with 4-10 carbon atoms, an anionic ligand, or a neutral ligand capable of coordinating with a lone pair of electrons. j represents an integer from 1 to 4. When j is an integer greater than 2, multiple Qs may exist, and each Q may be the same or different.
[13] A resin composition (X) comprising: The olefin resin (β) described in any one of [1] to
[11] Propylene polymers (α1), and Vinyl polymers (α2).
[0021]
[14] The resin composition (X) as described in
[13] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-propylene copolymer. The ratio of the total mass of the aforementioned olefin resin (β) to the total mass of the aforementioned propylene polymer (α1) and the aforementioned ethylene polymer (α2) ((β) / ((α1)+(α2))) is 0.02~0.23.
[0022]
[15] The resin composition (X) as described in
[13] or
[14] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-propylene copolymer. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned propylene polymer (α1) was 0.01~20 g / 10 min at 230°C and a load of 2.16 kg.
[0023]
[16] The resin composition (X) as described in any one of
[13] to
[15] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-propylene copolymer. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned vinyl polymer (α2) is 0.01~2.0 g / 10 min at 190°C and a load of 2.16 kg.
[0024]
[17] The resin composition (X) as described in
[13] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. The ratio of the total mass of the aforementioned olefin resin (β) to the total mass of the aforementioned propylene polymer (α1) and the aforementioned ethylene polymer (α2) ((β) / ((α1)+(α2))) is 0.08~0.20.
[0025]
[18] The resin composition (X) as described in
[13] or
[17] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned propylene polymer (α1) was 0.01~25 g / 10 min at 230°C and a load of 2.16 kg.
[0026]
[19] The resin composition (X) as described in
[13] ,
[17] or
[18] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned vinyl polymer (α2) is 0.5~100g / 10min at 190°C and a load of 2.16kg.
[0027]
[20] The resin composition (X) as described in any one of
[13] and
[17] to
[19] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. The density of the aforementioned ethylene-based polymer (α2), as determined by ASTM D1505 at 25°C, is 850~900 kg / m³. 3 .
[0028]
[21] The resin composition (X) as described in any one of
[13] and
[17] to
[20] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned propylene polymer (α1) was determined at 230°C and a load of 2.16 kg to be 0.01~25 g / 10 min. The density of the aforementioned ethylene-based polymer (α2), as determined by ASTM D1505 at 25°C, is 850~900 kg / m³. 3 .
[0029]
[22] The resin composition (X) as described in any one of
[13] and
[17] to
[21] , wherein the main chain of the grafted olefin polymer [R1] in the aforementioned olefin resin (β) is an ethylene-1-butene copolymer. The ratio of the total mass of the aforementioned olefin resin (β) to the total mass of the aforementioned propylene polymer (α1) and the aforementioned ethylene polymer (α2) ((β) / ((α1)+(α2)))) is 0.08~0.20. According to ASTM D1238, the melt flow rate (MFR) of the aforementioned vinyl polymer (α2) is 0.5~100g / 10min at 190°C and a load of 2.16kg.
[0030]
[23] The resin composition (X) as described in any one of
[13] to
[22] , wherein the content of propylene-derived structural units in the side chains of the aforementioned grafted olefin polymer [R1] is 80 to 100 mol%. The content of ethylene-derived structural units in the side chains of the aforementioned grafted olefin polymer [R1] is 0-20 mol%. The weight-average molecular weight (Mw) of the aforementioned polymers or copolymers constituting the side chains of the aforementioned grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is in the range of 5,000 to 50,000.
[0031]
[24] An olefinic resin (β) as described in any one of [1] to
[11] , used for packaging of lithium-ion batteries.
[0032]
[25] The resin composition (X) as described in any one of
[13] to
[23] is used in the packaging of a lithium-ion battery.
[0033]
[26] A molded article comprising any one of the olefin resins (β) described in [1] to
[11] , or any one of the resin compositions (X) described in
[13] to
[23] .
[0034]
[27] A lithium-ion battery packaging containing any one of the olefin resins (β) described in [1] to
[11] , or any one of the resin compositions (X) described in
[13] to
[23] .
[0035]
[28] An energy storage device comprising the lithium-ion battery package described in
[27] .
[0036] Invention Effects According to the present invention, novel olefin resins useful as compatibilizers for propylene-based and ethylene-based polymers can be provided, as well as uses of the olefin resins. Furthermore, according to the present invention, resin compositions and molded articles comprising propylene-based and ethylene-based polymers, and having improved balance between impact resistance and elongation or between impact resistance and strength, as well as lithium-ion battery packaging and energy storage devices, can be provided. Attached Figure Description
[0037] [ Figure 1 ] Figure 1 This is a transmission electron microscope image of the resin composition (X) obtained in Example 1B.
[0038] [ Figure 2 ] Figure 2 A transmission electron microscope image of the resin composition (X) obtained in Reference Example 1B.
[0039] [ Figure 3 ] Figure 3 Transmission electron microscope image of the resin composition (X) obtained in Comparative Example 1B.
[0040] [ Figure 4 ] Figure 4 This is a transmission electron microscope image of the resin composition (X) obtained in Example 1C.
[0041] [ Figure 5 ] Figure 5 A transmission electron microscope image of the resin composition (X) obtained in Reference Example 1C.
[0042] [ Figure 6 ] Figure 6 Transmission electron microscope image of the resin composition (X) obtained in Comparative Example 1C. Detailed Implementation
[0043] The present invention will now be described in detail.
[0044] In this specification, the numerical range represented by "~" refers to the range including the values before and after "~" as the lower and upper limits. "A~B" indicating a numerical range means above A and below B.
[0045] In this manual, when the units of the values before and after the "~" indicating a numerical range are the same, the unit of the value before the "~" is sometimes omitted. For example, sometimes "851 kg / m 3 ~900kg / m 3 The record states "851~900 kg / m³". 3 ".
[0046] In this specification, when referring to the amount of each component in the resin composition, if multiple substances belonging to each component are present in the resin composition, unless otherwise specified, the total amount of the multiple substances present in the resin composition is used.
[0047] In this specification, a combination of two or more preferred embodiments constitutes a more preferred embodiment.
[0048] Unless otherwise specified, each component in the resin composition or each structural unit in the polymer (resin) may contain one or more types of components in this specification.
[0049] In this specification, the description of groups (atomic groups) includes not only cases without substituents but also cases with substituents.
[0050] In this specification, the term "layer" includes, in addition to the case where it is formed in the entirety of the region in which it is observed, the case where it is formed only in a part of the region.
[0051] In this instruction manual, room temperature refers to 23°C.
[0052] In this specification, the term "mainly possessing" means that the substance being targeted contains more than 50% by mass.
[0053] <Olefin Resins (β)> The olefin resin (β) of the present invention comprises a grafted olefin polymer [R1] having a main chain and side chains, and satisfies all of the following requirements (I) to (IV).
[0054] (I) The main chain of the aforementioned grafted olefin polymer [R1] is composed of ethylene-propylene copolymer or ethylene-1-butene copolymer; (II) The side chains of the aforementioned grafted olefin polymer [R1] are composed of propylene homopolymer or propylene-ethylene copolymer; (III) The total content of P of the following components (i) to (iv) in the aforementioned olefin resin (β) is in the range of 10 to 80% by mass: (i) Propylene homopolymers constituting the side chains of the aforementioned grafted olefin polymer [R1]; (ii) A propylene-ethylene copolymer constituting the side chain of the aforementioned grafted olefin polymer [R1]; (iii) Terminal unsaturated propylene homopolymers that do not constitute the aforementioned grafted olefin polymer [R1]; (iv) Terminally unsaturated propylene-ethylene copolymers that do not constitute the aforementioned grafted olefin polymer [R1]; (IV) The intrinsic viscosity [η] of the aforementioned olefin resin (β) was measured at 135 °C in decahydronaphthalene and was 0.5~5.0 dL / g.
[0055] In this invention, the term "grafted olefin polymer" refers to a polymer obtained by bonding one or more side chains of grafted olefin polymer [R1] to the main chain of grafted olefin polymer [R1].
[0056] The grafted olefin polymer [R1] of the present invention is a structure in which the side chain of the grafted olefin polymer [R1] composed of propylene homopolymer or propylene-ethylene copolymer is chemically bonded to the main chain of the grafted olefin polymer [R1] composed of ethylene-propylene copolymer or ethylene-1-butene copolymer. Therefore, the olefin resin (β) containing the grafted olefin polymer [R1] has high compatibility with both the propylene polymer (α1) and the ethylene polymer (α2) described later.
[0057] In the grafted olefin polymer [R1] of the present invention, the number-average molecular weight of the main chain and the number-average molecular weight of the side chain typically satisfy the relationship that "the number-average molecular weight of the main chain > the number-average molecular weight of the side chain". Therefore, it is possible to determine which chain in the grafted olefin polymer [R1] is the main chain or the side chain by measuring the number-average molecular weight (Mn).
[0058] The grafted olefin polymer [R1] of the present invention satisfies the following requirements (I) and (II).
[0059] (I): The main chain of the grafted olefin polymer [R1] is composed of ethylene-propylene copolymer or ethylene-1-butene copolymer.
[0060] For the main chain of the grafted olefin polymer [R1], from the viewpoint that the olefin resin (β) exhibits excellent compatibility with the ethylene polymer (α2) described later, and from the viewpoint that the resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, it is preferable that the content of structural units from ethylene is 70 to 99 mol% and the content of structural units from propylene or 1-butene is 1 to 30 mol%.
[0061] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, from the viewpoint of further improving the whitening resistance of the resin composition (X) containing the olefin resin (β) and the molded article, it is more preferable that the content of the structural unit from ethylene is 72 to 95 mol%, the content of the structural unit from propylene is 5 to 28 mol%, more preferably that the content of the structural unit from ethylene is 74 to 92 mol%, the content of the structural unit from propylene is 8 to 26 mol%, particularly preferably that the content of the structural unit from ethylene is 74 to 90 mol%, the content of the structural unit from propylene is 10 to 26 mol%, especially preferably that the content of the structural unit from ethylene is 78 to 87 mol%, the content of the structural unit from propylene is 13 to 22 mol%, and even more preferably that the content of the structural unit from ethylene is 75 to 85 mol%, the content of the structural unit from propylene is 15 to 25 mol.
[0062] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, from the viewpoint of further improving the whitening resistance of the resin composition (X) containing the olefin resin (β) and the molded article, it is more preferable that the content of the structural unit from ethylene is 79-86 mol%, and the content of the structural unit from 1-butene is 14-21 mol%, and even more preferably that the content of the structural unit from ethylene is 79-82 mol%, and the content of the structural unit from 1-butene is 18-21 mol%. The above-mentioned content of structural units can be obtained by utilizing... 1 H-NMR or 13 The measurements were performed using C-NMR.
[0063] (II): The side chains of the grafted olefin polymer [R1] are composed of propylene homopolymer or propylene-ethylene copolymer.
[0064] Regarding the side chains of the grafted olefin polymer [R1], from the viewpoint that the olefin resin (β) exhibits excellent compatibility with the propylene polymer (α1) described later, and from the viewpoint that the resin composition (X) containing the olefin resin (β) and the molded article have excellent whitening resistance, it is preferable that the content of the structural unit from propylene is 80-100 mol%, and the content of the structural unit from ethylene is 0-20 mol%, more preferably 85-100 mol%, and the content of the structural unit from ethylene is 0-15 mol%, even more preferably 90-100 mol%, and the content of the structural unit from ethylene is 0-10 mol%, further preferably 95-100 mol%, and the content of the structural unit from ethylene is 0-5 mol%, particularly preferably 100 mol%, and the content of the structural unit from ethylene is 0 mol%. The above-mentioned content of structural units can be obtained by using... 1 H-NMR or 13 The measurements were performed using C-NMR.
[0065] The main chain and side chains of the grafted olefin polymer [R1] can contain structural units other than those derived from ethylene and propylene, as long as the effects of the present invention are achieved. The proportion of such structural units in all structural units of the main chain and side chains of the grafted olefin polymer [R1] is typically 0-19 mol%, preferably 0-15 mol%, more preferably 0-10 mol%, and even more preferably 0-5 mol%. Examples of structural units other than those derived from ethylene and propylene include, for example, structural units derived from α-olefins with 4-20 carbon atoms, cyclic olefins, etc., preferably α-olefins with 4-10 carbon atoms, and more preferably α-olefins with 4-8 carbon atoms.
[0066] For grafted olefin polymers [R1], the weight-average molecular weight (Mw) of the ethylene-propylene copolymer or ethylene-1-butene copolymer constituting the main chain, as determined by gel permeation chromatography (GPC) in terms of polyethylene equivalents, is typically 5,000 to 250,000, preferably 35,000 to 180,000, and more preferably 40,000 to 140,000.
[0067] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, from the viewpoint that the olefin resin (β) exhibits excellent compatibility with the ethylene polymer (α2) described later, and from the viewpoint that the resin composition (X) containing the olefin resin (β) and the molded article have excellent resistance to whitening, the Mw of the ethylene-propylene copolymer constituting the main chain is preferably 50,000 to 250,000, more preferably 55,000 to 200,000, further preferably 60,000 to 150,000, particularly preferably 65,000 to 100,000, especially preferably 70,000 to 90,000, and extremely preferably 72,000 to 82,000.
[0068] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, from the viewpoint that the olefin resin (β) exhibits excellent compatibility with the ethylene polymer (α2) described later, and from the viewpoint that the resin composition (X) containing the olefin resin (β) and the molded article have excellent whitening resistance, the Mw of the ethylene-1-butene copolymer constituting the main chain is preferably 30,000 to 120,000, more preferably 40,000 to 110,000, further preferably 50,000 to 100,000, particularly preferably 60,000 to 90,000, and especially preferably 72,000 to 85,000.
[0069] Furthermore, considering the excellent compatibility of the olefin resin (β) with the propylene polymer (α1) described later, and the excellent whitening resistance of the resin composition (X) and the molded article containing the olefin resin (β), for the grafted olefin polymer [R1], the weight-average molecular weight (Mw) of the polymer or copolymer constituting the side chain (propylene homopolymer or propylene-ethylene copolymer constituting the side chain), calculated by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is preferably 5,000 to 50,000, more preferably 7,500 to 50,000, further preferably 10,000 to 50,000, particularly preferably 12,500 to 40,000, and especially preferably 15,000 to 30,000.
[0070] Furthermore, for the grafted olefin polymer [R1], the total weight-average molecular weight (Mw), calculated by gel permeation chromatography (GPC) for each side chain in terms of polypropylene equivalents, and the product of the number of side chains for each main chain, is preferably 5,000 to 150,000, more preferably 6,000 to 110,000, and even more preferably 6,000 to 70,000.
[0071] When the weight-average molecular weight (Mw) of the main chain, the weight-average molecular weight (Mw) of the side chain, and the total weight-average molecular weight of the grafted olefin polymer [R1] satisfy one or more, preferably two or more, or more preferably all of the above-mentioned preferred ranges, the olefin resin (β) containing it becomes a substance with excellent compatibility with either the propylene polymer (α1) and the ethylene polymer (α2) described later. The resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, and also have excellent whitening resistance.
[0072] The olefin resin (β) of the present invention comprises a grafted olefin polymer [R1] and satisfies all of the following requirements (III) and (IV).
[0073] (III): The total content of P of the following components (i) to (iv) in the olefin resin (β) is 10 to 80% by mass.
[0074] (i) Propylene homopolymers constituting the side chains of the grafted olefin polymer [R1] (ii) Propylene-ethylene copolymers constituting the side chains of grafted olefin polymers [R1] (iii) Terminally unsaturated propylene homopolymers that do not constitute grafted olefin polymers [R1] (iv) Terminally unsaturated propylene-ethylene copolymers that do not constitute grafted olefin polymers [R1] From the viewpoints that the olefin resin (β) has excellent compatibility with any of the propylene polymer (α1) and ethylene polymer (α2) described later, that the resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, and that the olefin resin (β) has excellent whitening resistance, the content of P (which is obtained by summing the components (i) to (iv) above) in the olefin resin (β) is preferably 10 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 15 to 55% by mass.
[0075] The olefin resin (β) of the present invention may consist solely of the grafted olefin polymer [R1], or may contain components other than the grafted olefin polymer [R1]. For example, it may sometimes contain unreacted products or byproducts from the synthesis of the grafted olefin polymer [R1], i.e., propylene homopolymers or propylene-ethylene copolymers that do not constitute the grafted olefin polymer [R1], as part of the aforementioned P. Therefore, components (i) to (iv) constituting P are generally terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymers derived from raw materials that become side chains of the grafted olefin polymer [R1], components (iii) are generally terminal unsaturated propylene homopolymers that remain as side chains during the synthesis of the grafted olefin polymer [R1], and components (iv) are generally terminal unsaturated propylene-ethylene copolymers that remain as side chains during the synthesis of the grafted olefin polymer [R1]. For example, when manufacturing an olefin resin (β) using the manufacturing method of the olefin resin (β) described later, P obtained by summing the above (i) to (iv) is the total of the components from the side chain raw materials.
[0076] The content of P in the olefin resin (β) can be determined by analyzing the olefin resin (β). Since the components other than P are components from the main chain, that is, the total amount of P and the components from the main chain is 100% by mass of the olefin resin (β), when the olefin resin (β) is a resin manufactured using the manufacturing method of the olefin resin (β) described later, it can be calculated from the difference between the amount of terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer, which are the raw materials for the side chain, and the amount of the obtained olefin resin (β). In addition, the content of P can also be calculated by analyzing the olefin resin (β) using the method described in the examples. It should be noted that, according to the inventors of this application, the content of P calculated from the difference between the amount of olefin resin (β) and the amount of side-chain raw material input, and the content of P calculated by analyzing the olefin resin (β) are extremely similar values. Therefore, it can be determined by any method. In the embodiments described later, the content of P is calculated from the difference between the amount of olefin resin (β) and the amount of side-chain raw material input.
[0077] (IV): The intrinsic viscosity [η] measured in decahydronaphthalene at 135 °C is 0.5~5.0 dL / g.
[0078] From the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength of the resin composition (X) containing olefin resin (β) and the molded article, excellent whitening resistance, and excellent resin composition and molding processability, the intrinsic viscosity [η] of the olefin resin (β) of the present invention, measured in decahydronaphthalene at 135°C, is preferably 0.5 to 4.0 dL / g, more preferably 0.5 to 3.0 dL / g, and even more preferably 0.7 to 3.0 dL / g.
[0079] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, the preferred concentration is 0.7 to 2.0 dL / g, more preferably 0.7 to 1.6 dL / g, even more preferably 0.9 to 1.35 dL / g, and particularly preferably 0.9 to 1.25 dL / g.
[0080] In addition, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, the preferred concentration is 0.5 to 3.0 dL / g, more preferably 0.5 to 2.0 dL / g, and even more preferably 0.5 to 1.25 dL / g.
[0081] The olefin-based resin (β) of the present invention preferably satisfies the following requirement (V).
[0082] (V): The melting point (Tm) determined by differential scanning calorimetry (DSC) is -40 to 165 °C.
[0083] It is desirable that the Tm of the olefin resin (β) of the present invention, as determined by differential scanning calorimetry (DSC), is in the range of -30 to 165°C, and even more preferably 0 to 165°C.
[0084] In DSC measurements, when multiple endothermic peaks exist, the temperatures of the endothermic peaks on the low-temperature side and the high-temperature side are the melting points (Tm) of the element (V).
[0085] Since olefin resins (β) contain grafted olefin polymers [R1], they typically have two melting point peaks. The Tm observed at low temperatures within the above range originates from the main chain of the grafted olefin polymers [R1] constituting the olefin resin (β), while the Tm at high temperatures originates from the side chains of the grafted olefin polymers [R1] constituting the olefin resin (β).
[0086] By keeping Tm within the above range, the resin composition (X) containing olefin resin (β) and the molded body become substances with excellent compatibility with either the propylene polymer (α1) and the ethylene polymer (α2) described later. The resin composition (X) containing olefin resin (β) and the molded body exhibit excellent balance between impact resistance and elongation or between impact resistance and strength, and consequently, excellent resistance to whitening.
[0087] As a method to adjust Tm to the above range, one example is to adjust the polymerization temperature, polymerization pressure, and the ratio of ethylene to propylene or 1-butene feed amounts in the following steps (A) and (B).
[0088] For the olefin resin (β) of the present invention, the melt flow rate (MFR) measured according to ASTM D1238 at 190°C and a load of 2.16 kg is preferably 0.01 to 100 g / 10 min.
[0089] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, the MFR of the olefin resin (β) is more preferably 0.01 to 80 g / 10 min, further preferably 0.01 to 50 g / 10 min, especially preferably 0.01 to 30 g / 10 min, particularly preferably 0.5 to 30 g / 10 min, and extremely preferably 2.0 to 28 g / 10 min.
[0090] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, the MFR of the olefin resin (β) is more preferably 2.2 to 50 g / 10 min, further preferably 2.5 to 30 g / 10 min, especially preferably 2.5 to 10 g / 10 min, and particularly preferably 2.5 to 8.5 g / 10 min.
[0091] It should be noted that the MFR of the olefin resin (β) can be set to a desired value by adjusting the manufacturing conditions. For example, methods such as adjusting the polymerization temperature, polymerization pressure, and hydrogen supply in steps (A) and (B) described later can be cited. Specifically, for example, the MFR can be increased by increasing the hydrogen supply relative to the feed amounts of ethylene, propylene, and 1-butene when polymerizing the olefin resin (β), and the MFR can be decreased by decreasing the hydrogen supply relative to the feed amounts of ethylene, propylene, and 1-butene.
[0092] When the MFR of the olefin resin (β) meets such a range, the resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, excellent whitening resistance, and excellent molding processability, and are therefore preferred.
[0093] For the olefin-based resin (β) of the present invention, the glass transition temperature (Tg) determined by differential scanning calorimetry (DSC) is preferably -75 to -40°C.
[0094] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, the Tg of the olefin resin (β) is more preferably -70 to -45°C, further preferably -65 to -45°C, especially preferably -60 to -50°C, and particularly preferably -57 to -51°C.
[0095] In addition, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, the Tg of the olefin resin (β) is more preferably -72 to -45°C, further preferably -70 to -50°C, and especially preferably -70 to -58°C.
[0096] When the Tg of the olefin resin (β) meets such a range, the resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, excellent whitening resistance, and excellent molding processability, and are therefore preferred.
[0097] For the olefinic resin (β) of the present invention, the density (density measured using the density gradient tube method) determined according to JIS K7112 at 23°C is preferably 850~950 kg / m³. 3 More preferably, it is 850~925 kg / m 3 A further preferred value is 860~900 kg / m³. 3 .
[0098] It should be noted that the density of the olefin resin (β) can be set to a desired value by adjusting the manufacturing conditions of the olefin resin (β). For example, by changing the ratio of ethylene to propylene or 1-butene feed amounts during the polymerization of the olefin resin (β) in step (B) described later, the density of the olefin resin (β) can be adjusted to a desired value. Specifically, the density can be decreased by increasing the feed amount of propylene or 1-butene relative to the feed amount of ethylene, and the density can be increased by decreasing the feed amount of propylene or 1-butene relative to the feed amount of ethylene. Furthermore, for example, the density of the olefin resin (β) can be adjusted to a desired value by changing the ratio of the main chain content to the aforementioned P content. Specifically, when the density of the main chain is lower than that of the side chain, the density can be reduced by increasing the content of the main chain. When the density of the side chain is lower than that of the main chain, the density can be reduced by increasing the content of P. When the density of the main chain is higher than that of the side chain, the density can be increased by increasing the content of the main chain. When the density of the side chain is higher than that of the main chain, the density can be increased by increasing the content of P.
[0099] When the density of the olefin resin (β) meets such a range, the resin composition (X) containing the olefin resin (β) and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent whitening resistance, and are therefore preferred.
[0100] For the olefin resin (β) of the present invention, when the total content of structural units from ethylene, structural units from propylene or 1-butene, and structural units other than structural units from ethylene and structural units from propylene or 1-butene (other structural units) in the olefin resin (β) containing the grafted olefin polymer [R1] is set to 100% by mass, from the viewpoint of compatibility with the propylene polymer (α1) and ethylene polymer (α2) described later, it is preferable to contain 10 to 92% by mass, more preferably 15 to 86% by mass, further preferably 20 to 80% by mass, and particularly preferably 20 to 70% by mass of structural units from ethylene.
[0101] The presence of grafted olefin polymer [R1] in the olefin resin (β) can be confirmed by the content ratio of the main chain portion (ethylene-propylene copolymer or ethylene-1-butene copolymer) and the side chain portion (propylene homopolymer or propylene-ethylene copolymer) of the grafted olefin polymer [R1] in the olefin resin (β) and by peak separation using GPC. For example, the composition ratio of each part can be determined by peak separation based on the molecular weight distribution curve determined using GPC, thereby confirming the formation of the grafted olefin polymer [R1]. Alternatively, it can be confirmed using various analytical methods; the means of confirmation are not particularly limited.
[0102] For the olefin resin (β) of the present invention, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, the content of structural units derived from ethylene in the ethylene-propylene copolymer that forms the main chain of the grafted olefin polymer [R1] is 51 to 99 mol%, and the content of structural units derived from propylene is 1 to 49 mol%. Preferably, the ethylene-propylene copolymer that forms the main chain of the grafted olefin polymer [R1] is a copolymer that forms the main chain of ethylene-propylene copolymer with a content of 70 to 99 mol% of structural units derived from ethylene and a content of 1 to 30 mol% of structural units derived from propylene. More preferably, the content of structural units derived from ethylene in the ethylene-propylene copolymer that forms the main chain of the grafted olefin polymer [R1] is 75 to 85 mol%, and the content of structural units derived from propylene in the ethylene-propylene copolymer that forms the main chain of the grafted olefin polymer [R1] is 15 to 25 mol%. The intrinsic viscosity [η] of the olefin resin (β), measured at 135°C in decahydronaphthalene, is 0.9 to 1.25 dL / g.
[0103] Furthermore, for the olefin resin (β) of the present invention, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, it is more preferable that the content of ethylene-derived structural units of the ethylene-1-butene copolymer as the main chain of the grafted olefin polymer [R1] is 70 to 90 mol%, the content of 1-butene-derived structural units of the ethylene-1-butene copolymer as the main chain of the grafted olefin polymer [R1] is 10 to 30 mol%, and the weight-average molecular weight (Mw) of the ethylene-1-butene copolymer as the main chain of the grafted olefin polymer [R1], calculated by gel permeation chromatography (GPC) in the form of a value converted to polyethylene, is 30,000 to 120,000. Furthermore, it is also preferable that at least one of the following requirements A to C is satisfied.
[0104] • Requirement A: The melt flow rate (MFR) of the olefin resin (β), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 2.5~30 g / 10 min.
[0105] • Requirement B: The content of ethylene-derived structural units in the ethylene-1-butene copolymer that forms the backbone of the grafted olefin polymer [R1] is 78 to 87 mol%, and the content of 1-butene-derived structural units in the ethylene-1-butene copolymer that forms the backbone of the grafted olefin polymer [R1] is 13 to 22 mol%.
[0106] • Requirement C: The intrinsic viscosity [η] of the olefin resin (β), measured in decahydronaphthalene at 135°C, is 0.5~1.25 dL / g.
[0107] <Method for manufacturing olefin-based resins (β)> Olefin resins (β) can be manufactured using manufacturing methods that include, for example, each of the steps in steps (A) and (B) below.
[0108] Step (A): A step of polymerizing propylene in the presence of a catalyst for olefin polymerization containing a transition metal compound [A] of Group 4 of the periodic table having a dimethylsilyl diindene backbone to produce terminally unsaturated polypropylene, or a step of copolymerizing propylene with ethylene to produce terminally unsaturated propylene-ethylene copolymer.
[0109] Step (B): A step in which the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) is copolymerized with ethylene and propylene in the presence of a catalyst for olefin polymerization containing a bridged metallocene compound represented by the following general formula [B], or a step in which the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) is copolymerized with ethylene and 1-butene.
[0110] [Chemical Formula 2] (In formula [B], R) 1 R 2 R 3 R 4 R 5 R 8 R 9 and R 12 Each independently represents a hydrogen atom, a hydrocarbon group, a silicon-containing group, or a group containing heteroatoms other than a silicon-containing group, R 1 ~R 4 Two adjacent groups in R can bond with each other to form a ring. 6 and R 11 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 7 and R 10 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 6 and R 7 They can bond together to form a ring, R 10 and R 11 They can bond together to form a ring; however, R is not included. 6 R 7 R 10 and R 11 The case where all atoms are hydrogen. R 13 and R 14Each aryl group is represented independently. Y 1 This represents a carbon atom or a silicon atom. M 1 This represents a zirconium or hafnium atom. Q represents a halogen atom, a hydrocarbon group, a halohydrocarbon group, a neutral conjugated or non-conjugated diene with 4-10 carbon atoms, an anionic ligand, or a neutral ligand capable of coordinating with a lone pair of electrons. j represents an integer from 1 to 4. When j is an integer greater than 2, multiple Qs may exist, and each Q may be the same or different. The following will describe the processes of (A) and (B) in turn.
[0111] [Process (A)] Step (A) is a step of producing terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer as a raw material for the side chain of a grafted olefin polymer [R1], and is a step of producing terminally unsaturated polypropylene by polymerizing propylene in the presence of an olefin polymerization catalyst containing a transition metal compound [A] of Group 4 of the periodic table having a dimethylsilyl bisindenyl backbone, or a step of producing terminally unsaturated propylene-ethylene copolymer by copolymerizing propylene with ethylene.
[0112] [Transition metal compound [A]] In step (A), a catalyst for olefin polymerization is used, which contains a transition metal compound [A] (hereinafter also simply referred to as transition metal compound [A]) belonging to Group 4 of the periodic table and comprising a ligand having a dimethylsilyl bisindenyl skeleton. The transition metal compound [A] functions as a catalyst for the polymerization of propylene or the copolymerization of propylene and ethylene, and its function is further enhanced by its use in combination with catalyst component (C) described later.
[0113] As the transition metal compound [A], any transition metal compound of Group 4 of the periodic table containing a ligand having a dimethylsilyl bisindenyl skeleton can be used. For example, compounds disclosed in Japanese Patent Application Publication No. 6-100579, Japanese Patent Application Publication No. 2001-525461, Japanese Patent Application Publication No. 2005-336091, Japanese Patent Application Publication No. 2009-299046, Japanese Patent Application Publication No. 11-130807, and Japanese Patent Application Publication No. 2008-285443 are preferred.
[0114] More specifically, as the aforementioned transition metal compound [A], preferred examples include compounds selected from the group consisting of bridged bis(indenyl)zirconia or hafnium bis(indenyl)zirconia. More preferably, dimethylsilyl-bridged bis(indenyl)zirconia or hafnium bis(indenyl)zirconia. Even more preferably, dimethylsilyl-bridged bis(indenyl)zirconia is preferred, as the selection of zirconia allows for the efficient manufacture of olefin resins (β) containing the desired grafted olefin polymer [R1].
[0115] More specifically, preferred compounds include dimethylsilylbis{1-(2-n-propyl-4-(9-phenanthyl)indyl)} zirconium dichloride, dimethylsilylbis(2-methyl-4-phenylindyl) zirconium dichloride, and dimethylsilylbis(2-methyl-4-phenylindyl)dimethylzirconium.
[0116] The above-mentioned transition metal compounds [A] can be used alone or in combination of two or more.
[0117] [Polymerization Catalyst] The catalyst used in step (A) for olefin polymerization may be any transition metal compound [A] of Group 4 of the periodic table containing a ligand having a dimethylsilyl bisindenyl skeleton, as described above. There are no particular limitations, but it is preferable that, in addition to the transition metal compound [A], it also contains catalyst component (C) selected from (C1) organometallic compounds, (C2) organoaluminum oxide compounds, and (C3) compounds capable of reacting with the transition metal compound [A] to form ion pairs. Details of catalyst component (C) are described below.
[0118] [Process (A)] The polymerization of propylene or the copolymerization of propylene and ethylene in step (A) can ideally be carried out using known (co)polymerization methods for polymerizing or copolymerizing olefins in the presence of the aforementioned polymerization catalyst. Regarding polymerization conditions, there are no particular limitations as long as a solution polymerization process for manufacturing olefin polymers is used; for example, the following step is preferred: using an aliphatic or aromatic hydrocarbon as a polymerization solvent, propylene is polymerized alone or copolymerized with ethylene in the presence of an olefin polymerization catalyst containing the aforementioned transition metal compound [A] to obtain a polymerization reaction solution.
[0119] Examples of polymerization solvents used in step (A) include aliphatic hydrocarbons and aromatic hydrocarbons. Specifically, examples include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as vinyl chloride, chlorobenzene, and dichloromethane. One of these solvents may be used alone, or two or more may be used in combination. Furthermore, the polymerization solvent in step (A) may be the same as or different from the polymerization solvent in step (B) described later.
[0120] The polymerization temperature of process (A) is preferably in the range of 15°C to 200°C, and more preferably in the range of 20°C to 150°C.
[0121] Regarding the polymerization pressure of process (A), under conditions typically atmospheric pressure to 10 MPa gauge pressure, preferably atmospheric pressure to 5 MPa gauge pressure, the polymerization reaction can be carried out in any batch, semi-continuous, or continuous manner.
[0122] The reaction time of process (A) (in the case of continuous polymerization, it is the average residence time) varies depending on the catalyst concentration, polymerization temperature and other conditions, but is usually 0.5 minutes to 5 hours, preferably 5 minutes to 3 hours.
[0123] During polymerization or copolymerization in step (A), it is preferable to supply propylene alone, or to supply propylene and ethylene in a ratio of 80-100 mol% and 0-20 mol% respectively. Furthermore, in step (A), it is desirable to polymerize or copolymerize the resulting terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer under conditions where the weight-average molecular weight (Mw), calculated by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is in the range of 5,000-50,000.
[0124] The molecular weight of the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer obtained in step (A) can also be adjusted by introducing hydrogen into the polymerization system or by changing the polymerization temperature. Alternatively, it can be adjusted by using the catalyst component (C) described later; for example, triisobutylaluminum, methylaluminoxane, diethylzinc, etc. When hydrogen is added, an amount of approximately 0.001 to 100 NL per 1 kg of olefin is appropriate. To increase the content of terminal vinyl groups, it is preferable to carry out the process under hydrogen-free conditions.
[0125] The terminal vinyl ratio (the proportion of vinyl groups relative to the total number of unsaturated carbon-carbon bonds) in the terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer generated in step (A) is typically 40% or more, preferably 50%, and more preferably 60% or more.
[0126] In addition, the proportion of terminal vinyl groups in the terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer generated in step (A) is typically 0.1 to 15 per 1000 carbon atoms, preferably 0.4 to 15.
[0127] When the terminal vinyl ratio (the proportion of vinyl groups relative to all unsaturated carbon-carbon bonds) and the proportion of terminal vinyl groups per 1000 carbon atoms are low, the amount of terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer (specifically, propylene homopolymer or propylene-ethylene copolymer with vinyl groups at a single end) introduced into the main chain in subsequent process (B) is low, and the amount of grafted olefin polymer [R1] generated is low, so sometimes the desired effect is not obtained.
[0128] The terminal vinyl ratio (the proportion of vinyl groups relative to the total number of unsaturated carbon-carbon bonds), and the proportion of terminal vinyl groups per 1000 carbon atoms, can be determined by... 1 The polymer structure was analyzed by H-NMR and calculated using conventional methods.
[0129] [Process (B)] Step (B) is: in the presence of a catalyst for olefin polymerization containing a bridged metallocene compound (transition metal compound [B]) represented by the above general formula, copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) with ethylene and propylene, or copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) with ethylene and 1-butene.
[0130] [Bridge-linked metallocene compounds] The bridged metallocene compound used in process (B) is a compound represented by the following general formula [B].
[0131] [Chemical Formula 3] In formula [B], R 1 R 2 R 3 R 4 R 5 R 8 R 9 and R 12 Each independently represents a hydrogen atom, a hydrocarbon group, a silicon-containing group, or a group containing heteroatoms other than a silicon-containing group, R 1 ~R 4 Two adjacent groups in a ring can bond with each other to form a ring.
[0132] As a hydrocarbon group, it is preferably a hydrocarbon group with 1 to 20 carbon atoms. Specifically, examples include alkyl groups with 1 to 20 carbon atoms, arylalkyl groups with 7 to 20 carbon atoms, aryl groups with 6 to 20 carbon atoms, or substituted aryl groups. Examples include methyl, ethyl, n-propyl, isopropyl, allyl group, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, 3-methylpentyl, 1,1-diethylpropyl, 1,1-dimethylbutyl, 1-methyl-1-propylbutyl, 1,1-propylbutyl, 1,1-dimethyl-2-methylpropyl, 1-methyl-1-isopropyl-2-methylpropyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, norbornyl, and gold. Alkyl, phenyl, o-tolyl, m-tolyl, p-tolyl, xylyl, isopropylphenyl, tert-butylphenyl, naphthyl, biphenyl, terphenyl, phenanthryl, anthracene, benzyl, cumyl, and groups containing oxygen-containing groups such as methoxy, ethoxy, and phenoxy, nitrogen-containing groups such as nitro, cyano, N-methylamino, N,N-dimethylamino, and N-phenylamino, boron-containing groups such as boranetriylgroup and diboranyl group, and sulfur-containing groups such as sulfonyl and sulfenyl group can also be listed as hydrocarbon groups.
[0133] For the aforementioned hydrocarbon groups, the hydrogen atom can be replaced by a halogen atom, for example, trifluoromethyl, trifluoromethylphenyl, pentafluorophenyl, chlorophenyl, etc.
[0134] Examples of silicon-containing groups include silyl groups, silanoxy groups, hydrocarbon-substituted silyl groups, and hydrocarbon-substituted silanoxy groups. For instance, examples include methylsilyl, dimethylsilyl, trimethylsilyl, ethylsilyl, diethylsilyl, triethylsilyl, diphenylmethylsilyl, triphenylsilyl, dimethylphenylsilyl, dimethyltert-butylsilyl, and dimethyl(pentafluorophenyl)silyl.
[0135] R 6 and R 11 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 7 and R 10 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 6 and R 7 They can bond together to form a ring, R 10 and R 11They can bond together to form a ring. This does not include R. 6 R 7 R 10 and R 11 The case where all atoms are hydrogen atoms.
[0136] R 13 and R 14 Each aryl group represents an aryl group independently.
[0137] M 1 This indicates a zirconium atom or a hafnium atom.
[0138] Y 1 It represents a carbon atom or a silicon atom.
[0139] Q represents a halogen atom, a hydrocarbon group, a halohydrocarbon group, a neutral conjugated or non-conjugated diene with 4 to 20 carbon atoms, an anionic ligand, or a neutral ligand that can coordinate with lone pair electrons. j represents an integer from 1 to 4. When j is an integer greater than 2, there can be multiple Qs, each of which can be the same or different.
[0140] Examples of halogen atoms include fluorine, chlorine, bromine, and iodine, with chlorine being the preferred type.
[0141] As a hydrocarbon group, it is preferred to be a hydrocarbon group with 1 to 10 carbon atoms. Specifically, examples include methyl, ethyl, n-propyl, isopropyl, 2-methylpropyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1,1-diethylpropyl, 1-ethyl-1-methylpropyl, 1,1,2,2-tetramethylpropyl, sec-butyl, tert-butyl, 1,1-dimethylbutyl, 1,1,3-trimethylbutyl, neopentyl, cyclohexylmethyl, cyclohexyl, 1-methyl-1-cyclohexyl, benzyl, etc., with methyl, ethyl, and benzyl being preferred.
[0142] The preferred neutral conjugated or non-conjugated diene has 4 to 20 carbon atoms, and is preferably a neutral conjugated or non-conjugated diene with 4 to 10 carbon atoms. Specific examples of neutral conjugated or non-conjugated dienes include s-cis- or s-trans-η. 4 -1,3-Butadiene, s-cis- or s-trans-η 4 -1,4-Diphenyl-1,3-butadiene, s-cis- or s-trans-η 4 -3-methyl-1,3-pentadiene, s-cis- or s-trans-η 4 -1,4-Dibenzyl-1,3-butadiene, s-cis- or s-trans-η 4 -2,4-hexadiene, s-cis- or s-trans-η 4 -1,3-pentadiene, s-cis- or s-trans-η 4-1,4-Dimethyl-1,3-butadiene, s-cis- or s-trans-η 4 -1,4-bis(trimethylsilyl)-1,3-butadiene, etc.
[0143] Specific examples of anionic ligands include alkoxy groups such as methoxy, tert-butoxy, and phenoxy, carboxylic acid groups such as acetate and benzoate, and sulfonate groups such as methanesulfonate and toluenesulfonate.
[0144] Specific examples of neutral ligands that can coordinate with lone pairs of electrons include organophosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine, or ethers such as tetrahydrofuran, diethyl ether, dioxane, and 1,2-dimethoxyethane.
[0145] As in the above formula [B], the substituent R 1 ~R 4 Cyclopentadienyl groups can be exemplified by R. 1 ~R 4 The 3-position 1-substituted cyclopentadienyl groups, such as unsubstituted cyclopentadienyl, 3-tert-butylcyclopentadienyl, 3-methylcyclopentadienyl, 3-trimethylsilylcyclopentadienyl, 3-phenylcyclopentadienyl, 3-adamantylcyclopentadienyl, 3-pentylcyclopentadienyl, 3-cyclohexylcyclopentadienyl, etc., and 3-tert-butyl-5-methylcyclopentadienyl, 3-tert-butyl-5-ethylcyclopentadienyl, 3-phenyl-5-methylcyclopentadienyl, 3,5-di-tert-butylcyclopentadienyl, 3,5-dimethylcyclopentadienyl, 3-phenyl-5-methylcyclopentadienyl, 3-trimethylsilyl-5-methylcyclopentadienyl, etc., are preferred, but not limited to these. From the viewpoint of ease of synthesis, manufacturing cost, and copolymerization ability of non-conjugated polyenes, unsubstituted (R... 1 ~R 4 Cyclopentadienyl (containing hydrogen atoms)
[0146] As in formula [B], R has a substituent R 5 ~R 12 Fluorene groups, for example, R 5 ~R 12 Unsubstituted fluorenyl groups with hydrogen atoms, 2-methylfluorenyl, 2-tert-butylfluorenyl, 2-phenylfluorenyl, etc., 2-position 1-substituted fluorenyl groups, 4-methylfluorenyl, 4-tert-butylfluorenyl, 4-phenylfluorenyl, etc., 4-position 1-substituted fluorenyl groups, or 2,7-di-tert-butylfluorenyl, 3,6-di-tert-butylfluorenyl, etc., 2,7-dimethyl-3,6-di-tert-butylfluorenyl, 2,7-diphenyl-3,6-di-tert-butylfluorenyl, etc., 2,3,6,7-position 4-substituted fluorenyl groups, or R groups represented by the following general formulas [VI], [V-II] 6 With R7 They bond together to form rings, R 10 With R 11 They are mutually bonded to form rings with 4-substituted fluorene groups at positions 2, 3, 6, and 7, but are not limited to these.
[0147] [Chemical Formula 4] [Chemical Formula 5] In equations [VI] and [V-II], R 5 R 8 R 9 R 12 Similar to the definition in the above general formula [B], R a R b R c R d R e R f R g and R h Each alkyl group is independently composed of hydrogen atoms or 1 to 5 carbon atoms, and may also form a ring by bonding with adjacent substituents. Examples of such alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, pentyl, and n-pentyl. Furthermore, in formula [VI], R... x and R y Each is an independent hydrocarbon group with 1 to 3 carbon atoms and may have unsaturated bonds, R x Can be used with R a Or R c The bonded carbon atoms together form a double bond, R y Can be used with R e Or R g The bonded carbon atoms together form a double bond, R x and R y All are preferably saturated or unsaturated hydrocarbon groups with 1 or 2 carbon atoms.
[0148] Specifically, examples of the groups represented by the above general formulas [VI] or [V-II] include octamethyloctahydrodibenzofluorenyl (represented by formula [V-III]), tetramethyldodecyldibenzofluorenyl (represented by formula [V-IV]), octamethyltetrahydrodicyclopentadienylfluorenyl (represented by formula [VV]), hexamethyldicyclopentadienylfluorenyl (represented by formula [V-VI]), and b,h-dibenzofluorenyl (represented by formula [V-VII]).
[0149] [Chemical Formula 6] [Chemical Formula 7] [Chemical Formula 8] [Chemical Formula 9] [Chemical Formula 10] For the bridged metallocene compounds represented by the above general formula [B] containing these fluorene groups, the copolymerization ability of non-conjugated polyenes is excellent, especially in Y. 1 When Y is a silicon atom, transition metal compounds having a 2-substituted fluorene group at the 2,7 position, a 2-substituted fluorene group at the 3,6 position, a 4-substituted fluorene group at the 2,3,6,7 position, or a 4-substituted fluorene group at the 2,3,6,7 position as shown in the above general formula [VI] are particularly advantageous. When Y is a carbon atom, R... 5 To R 12 Metallocene compounds with unsubstituted fluorenyl groups at the hydrogen atom, 2-substituted fluorenyl groups at the 3,6 position, 4-substituted fluorenyl groups at the 2,3,6,7 position, and 4-substituted fluorenyl groups at the 2,3,6,7 position as shown in the above general formula [VI] are particularly superior.
[0150] It should be noted that, in this invention, in the bridged metallocene compound represented by the above general formula [B], Y 1 For silicon atoms, R 5 To R 12 When all atoms are hydrogen, R 13 and R 14 Preferably, the group is selected from groups other than methyl, butyl, phenyl, silicon-substituted phenyl, cyclohexyl, and benzyl; Y 1 For silicon atoms, R 6 and R 11 All are tert-butyl, R 5 R 7 R 8 R 9 R 10 R 12 In the absence of tert-butyl, R 13 and R 14 Preferably, the groups are selected from groups other than benzyl and silyl-substituted phenyl groups; Y 1 For carbon atoms, R 5 To R 12 When all atoms are hydrogen, R 13 R 14Preferably, the group is selected from groups other than methyl, isopropyl, tert-butyl, isobutyl, phenyl, p-tert-butylphenyl, p-n-butylphenyl, silanized phenyl, 4-biphenyl, p-tolyl, naphthyl, benzyl, cyclopentyl, cyclohexyl, and xylyl. Y 1 For carbon atoms, R 6 and R 11 It is the same group selected from tert-butyl, methyl, or phenyl, and is related to R. 5 R 7 R 8 R 9 R 10 and R 12 In the case of different groups or atoms, R 13 R 14 Preferably, the group is selected from groups other than methyl, phenyl, p-tert-butylphenyl, p-n-butylphenyl, silicon-substituted phenyl, and benzyl; Y 1 For carbon atoms, R 6 It is dimethylamino, methoxy, or methyl, R 5 R 7 R 8 R 9 R 10 R 11 and R 12 To be with R 6 In the case of different groups or atoms, R 13 R 14 Preferably, the groups are selected from groups other than methyl and phenyl; Y 1 It consists of carbon atoms, fluorene groups, and R 5 ~R 12 When the constituent part is b,h-dibenzofluorenyl or a,i-dibenzofluorenyl, R 13 R 14 Preferably, the group is selected from groups other than methyl and phenyl.
[0151] The following are specific examples of bridged metallocene compounds represented by the above general formula [B], but are not intended to limit the scope of the invention.
[0152] As a specific example of the bridged metallocene compound represented by the above general formula [B] When Y represents silicon atoms, examples can be given: Diphenylmethylenesilyl(cyclopentadienyl)(2,7-di-tert-butylfluorene)zirconium dichloride, Diphenylmethylenesilyl(cyclopentadienyl)(3,6-di-tert-butylfluorene)zirconium dichloride, Diphenylmethylenesilyl(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorene)zirconium dichloride, Diphenylmethylenesilyl(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorene)zirconium dichloride, Diphenylmethylenesilyl(cyclopentadienyl ... Zirconium dichloride: diphenylmethylenesilyl(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium dichloride, diphenylmethylenesilyl(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, diphenylmethylenesilyl(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, diphenylmethylenesilyl(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(p-tolyl)methylenesilyl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(p-tolyl)methylenesilyl(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(p-tolyl)methylenesilyl(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(p-tolyl)methylenesilyl(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconia dichloride 1. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(octamethyloctahydrodibenzo[a]fluorenyl)zirconium dichloride, 2. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(tetramethyldodecyldibenzo[a]fluorenyl)zirconium dichloride, 2. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(octamethyltetrahydrodicyclopentadien[a]fluorenyl)zirconium dichloride, 2. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(hexamethyldihydrodicyclopentadien[a]fluorenyl)zirconium dichloride, 2. Di(p-tolyl)methylenesilyl(cyclopentadienyl)(b,h-dibenzo[a]fluorenyl)zirconium dichloride Di(m-tolyl)methylenesilyl(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(m-tolyl)methylenesilyl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(m-tolyl)methylenesilyl(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-tolyl)methylenesilyl(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-tolyl)methylenesilyl(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconia dichloride Zirconium dichloride, including: di(m-tolyl)methylenesilyl(cyclopentadienyl)(octamethyloctahydrodibenzo[a]fluorenyl)zirconium dichloride, di(m-tolyl)methylenesilyl(cyclopentadienyl)(tetramethyldodecyldibenzo[a]fluorenyl)zirconium dichloride, di(m-tolyl)methylenesilyl(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl[a]fluorenyl)zirconium dichloride, di(m-tolyl)methylenesilyl(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl[a]fluorenyl)zirconium dichloride, and di(m-tolyl)methylenesilyl(cyclopentadienyl)(b,h-dibenzo[a]fluorenyl)zirconium dichloride, etc.
[0153] When Y is a carbon atom, examples can be given: Diphenylmethylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienylfluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienylfluorenyl)zirconium chloride, Diphenylmethylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium chloride The following are listed: di(p-tolyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, di(p-tolyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, di(p-tolyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzo[a]fluorenyl)zirconia dichloride, di(p-tolyl)methylene(cyclopentadienyl)(tetramethyldodecyldibenzo[a]fluorenyl)zirconia dichloride, di(p-tolyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl[a]fluorenyl)zirconia dichloride. Di(p-tolyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienylfluorenyl)zirconia dichloride, Di(p-tolyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconia dichloride, Di(m-tolyl)methylene(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(m-tolyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(m-tolyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-tolyl)methylene(cyclopentadienyl)(2,7-dimethyl- ... Zirconium dichloride is composed of the following compounds: di(m-tolyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, di(m-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride, di(m-tolyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, di(m-tolyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, and di(m-tolyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride. Di(p-tert-butylphenyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(p-tert-butylphenyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(p-tert-butylphenyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(p-tert-butylphenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl) Zirconium dichloride, bis(p-tert-butylphenyl)methylene(cyclopentadienyl)(tetramethyldodecyl dibenzofluorenyl)zirconium dichloride, bis(p-tert-butylphenyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, bis(p-tert-butylphenyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, bis(p-tert-butylphenyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride, Di(4-biphenyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride, Di(4-biphenyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(4-biphenyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(4-biphenyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, Di(4-biphenyl)methylene ( Zirconium dichloride of the following compounds: cyclopentadienyl(octamethyloctahydrodibenzofluorenyl)zirconium dichloride, bis(4-biphenyl)methylene(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium dichloride, bis(4-biphenyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, bis(4-biphenyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, bis(4-biphenyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride. Di(p-chlorophenyl)methylene(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(p-chlorophenyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(p-chlorophenyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(p-chlorophenyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(p-chlorophenyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconia dichloride 1. Di(p-chlorophenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride, 2. Di(p-chlorophenyl)methylene(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium dichloride, 2. Di(p-chlorophenyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, 2. Di(p-chlorophenyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, 2. Di(p-chlorophenyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride Di(m-chlorophenyl)methylene(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(m-chlorophenyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(m-chlorophenyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-chlorophenyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-chlorophenyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconia dichloride , bis(m-chlorophenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride, bis(m-chlorophenyl)methylene(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium dichloride, bis(m-chlorophenyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, bis(m-chlorophenyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, bis(m-chlorophenyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride, Di(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(fluorenyl)zirconia dichloride, Di(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia dichloride, Di(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorenyl)zirconia dichloride, Di(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconia dichloride , bis(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride, bis(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(tetramethyldodecyldibenzofluorenyl)zirconium dichloride, bis(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, bis(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, bis(m-trifluoromethylphenyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride, Di(2-naphthyl)methylene(cyclopentadienyl)(2,7-di-tert-butylfluorene)zirconia dichloride, Di(2-naphthyl)methylene(cyclopentadienyl)(3,6-di-tert-butylfluorene)zirconia dichloride, Di(2-naphthyl)methylene(cyclopentadienyl)(2,7-dimethyl-3,6-di-tert-butylfluorene)zirconia dichloride, Di(2-naphthyl)methylene(cyclopentadienyl)(2,7-diphenyl ... Zirconium dichloride, including: bis(2-naphthyl)methylene(cyclopentadienyl)(tetramethyldodecyl)zirconium dichloride, bis(2-naphthyl)methylene(cyclopentadienyl)(octamethyltetrahydrodicyclopentadienyl)zirconium dichloride, bis(2-naphthyl)methylene(cyclopentadienyl)(hexamethyldihydrodicyclopentadienyl)zirconium dichloride, and bis(2-naphthyl)methylene(cyclopentadienyl)(b,h-dibenzofluorenyl)zirconium dichloride, etc.
[0154] Furthermore, as a bridged metallocene compound represented by the above general formula [B], one can cite examples where M in the general formula [B] is represented by M in the specific examples described above. 1 The compound obtained by replacing zirconium atoms with hafnium atoms.
[0155] As an example of the structural formulas of these metallocene compounds, the following shows the structural formulas of di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconia dichloride (hereinafter (A)) and di(p-chlorophenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconia dichloride (hereinafter (B)).
[0156] [Chemical Formula 11] The aforementioned bridging metallocene compounds can be used alone or in combination of two or more.
[0157] The bridged metallocene compound represented by the above formula [B] used in step (B) can be manufactured by any method without particular limitation. For example, it can be manufactured according to the methods described in J. Organomet. Chem., 63, 509 (1996), WO2005 / 100410, WO2006 / 123759, WO01 / 27124, Japanese Patent Application Publication No. 2004-168744, Japanese Patent Application Publication No. 2004-175759, Japanese Patent Application Publication No. 2000-212194, etc.
[0158] [Polymerization Catalyst] The catalyst used in step (B) for olefin polymerization may contain any bridged metallocene compound represented by the above general formula [B], without particular limitation, but preferably contains, in addition to the bridged metallocene compound, a catalyst component (C) selected from (C1) organometallic compounds, (C2) organoaluminum oxide compounds, and (C3) compounds capable of reacting with transition metal compound [A] to form ion pairs. Details of the catalyst component (C) are described below.
[0159] [Process (B)] Step (B) is: in the presence of the above-mentioned polymerization catalyst, copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) with ethylene and propylene, or copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) with ethylene and 1-butene.
[0160] The polymerization method of step (B) is not particularly limited, but it is preferred to carry out it in solution (dissolution) polymerization. Regarding the polymerization conditions, there are no particular limitations as long as a solution polymerization process for manufacturing olefin polymers is used. For example, the following step is preferred: using an aliphatic or aromatic hydrocarbon as a polymerization solvent, in the presence of a catalyst for olefin polymerization containing a bridging metallocene compound represented by the above general formula [B], ethylene and propylene or ethylene and 1-butene are copolymerized with the terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer produced in step (A) above to obtain a polymerization reaction solution containing a grafted olefin polymer [R1].
[0161] In step (B), the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer produced in step (A) is typically fed into the reactor in step (B) in the form of a solution or slurry. There are no particular limitations on the feeding method; the polymerization reaction liquid obtained in step (A) can be continuously fed into the reactor in step (B), or the polymerization reaction liquid obtained in step (A) can be temporarily stored in a buffer tank or the like and then fed into step (B).
[0162] Examples of polymerization solvents used in step (B) include aliphatic hydrocarbons and aromatic hydrocarbons. Specifically, examples include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as vinyl chloride, chlorobenzene, and dichloromethane. One solvent can be used alone, or two or more can be used in combination. Furthermore, the polymerization solvent in step (B) can be the same as or different from the polymerization solvent in step (A).
[0163] The polymerization temperature of step (B) is typically in the range of 50°C to 200°C, preferably in the range of 80°C to 200°C, and more preferably in the range of 90°C to 200°C.
[0164] Regarding the polymerization pressure in step (B), the polymerization reaction can be carried out in any manner, such as batch, semi-continuous, or continuous, under conditions typically ranging from atmospheric pressure to 10 MPa gauge pressure, and preferably from atmospheric pressure to 5 MPa gauge pressure. Furthermore, the polymerization can be divided into two or more steps with different reaction conditions. In this invention, a method of continuously feeding monomers into the reactor to carry out copolymerization is preferred.
[0165] The reaction time of process (B) (in the case of copolymerization using a continuous method, it is the average residence time) also varies depending on the catalyst concentration, polymerization temperature and other conditions, but it is usually 0.5 minutes to 5 hours, preferably 5 minutes to 3 hours.
[0166] For the polymer concentration in step (B), during stable operation, it is, for example, 0.5 to 40% by mass, preferably 1 to 35% by mass. From the viewpoint of viscosity limitations in polymerization capacity, post-treatment process (solvent removal) load, and productivity, 1.5 to 35% by mass is preferred.
[0167] In step (B), when the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer manufactured in step (A) is copolymerized with ethylene and propylene or ethylene and 1-butene, the amount of ethylene and propylene, or ethylene and 1-butene used is preferably such that, in a total of 100 mol% of ethylene and propylene, or ethylene and 1-butene, the amount of ethylene is 70 to 99 mol% and the amount of propylene or 1-butene is 1 to 30 mol%. Furthermore, in step (B), it is desirable that the copolymerization is carried out under conditions where the weight-average molecular weight (Mw), calculated by gel permeation chromatography (GPC) in the form of a value converted to polyethylene, for the ethylene-propylene polymer portion or the ethylene-1-butene polymer portion that forms the backbone of the obtained grafted olefin polymer [R1], is in the range of 30,000 to 200,000.
[0168] The molecular weight of the resulting copolymer, i.e., the grafted olefin polymer [R1], can also be adjusted by introducing hydrogen into the polymerization system or by changing the polymerization temperature. Furthermore, it can be adjusted by the amount of catalyst component (C1) used, as described later. Specifically, examples include triisobutylaluminum, methylaluminoxane, and diethylzinc. When hydrogen is added, an amount of approximately 0.001 to 100 NL per 1 kg of olefin is appropriate.
[0169] [Catalyst component (C)] In the method for manufacturing the olefin resin (β) of the present invention, it is also preferable that the olefin polymerization catalyst used in the above-described steps (A) and (B) includes catalyst component (C). Catalyst component (C) can be used as a catalyst component for olefin polymerization in both steps (A) and (B), or as a catalyst component for olefin polymerization in either step (A) or step (B). When catalyst component (C) is used as a catalyst component for olefin polymerization in both steps (A) and (B), the catalyst component (C) used in steps (A) and (B) can be the same or different.
[0170] The catalyst component (C) is one or more compounds selected from (C1) organometallic compounds, (C2) organoaluminum oxide compounds, and (C3) compounds that can react with transition metal compounds contained in catalysts for olefin polymerization to form ion pairs.
[0171] The compounds (C1) to (C3) will be described in turn below.
[0172] ((C1) Organometallic compounds) As the (C1) organometallic compound used in the present invention, specific examples include organoaluminum compounds represented by the following general formula (C1-a), complex alkylates of Group 1 metal of the periodic table and aluminum represented by general formula (C1-b), and dialkyl compounds of Group 2 or Group 12 metal of the periodic table represented by general formula (C1-c). It should be noted that the (C1) organometallic compound does not include the (C2) organoaluminum oxy-compound described later.
[0173] R a p Al(OR b ) q H r Y s …(C1-a) In the above general formula (C1-a), R a and R b may be the same or different, each representing a hydrocarbon group having 1 to 15, preferably 1 to 4 carbon atoms, Y represents a halogen atom, p is a number satisfying 0<p≤3, q is a number satisfying 0≤q<3, r is a number satisfying 0≤r<3, s is a number satisfying 0≤s<3, and p+q+r+s=3.) M 3 AlR c 4…(C1-b) In the above general formula (C1-b), M 3 represents Li, Na or K, R c represents a hydrocarbon group having 1 to 15, preferably 1 to 4 carbon atoms.) R d R e M 4 …(C1-c) In the above general formula (C1-c), R d and R e may be the same or different, each representing a hydrocarbon group having 1 to 15, preferably 1 to 4 carbon atoms, M 4 is Mg, Zn or Cd.
[0174] Examples of the organoaluminum compound represented by the above general formula (C1-a) include compounds represented by the following general formulas (C-1a-1) to (C-1a-4).
[0175] R a p Al(OR b ) 3-p …organoaluminum compound represented by (C-1a-1), (In formula (C-1a-1), R a and R bwhich may be the same or different from each other, represent a hydrocarbyl group having 1 to 15, preferably 1 to 4 carbon atoms, and p is preferably a number of 1.5≤p≤3); R a p AlY 3-p ... an organoaluminum compound represented by (C-1a-2), (In the formula (C-1a-2), R a represents a hydrocarbyl group having 1 to 15, preferably 1 to 4 carbon atoms, Y represents a halogen atom, and p is preferably a number of 0<p<3); R a p AlH 3-p ... an organoaluminum compound represented by (C-1a-3), (In the formula (C-1a-3), R a represents a hydrocarbyl group having 1 to 15, preferably 1 to 4 carbon atoms, and p is preferably a number of 2≤p<3); R a p Al(OR b ) q Y s ... an organoaluminum compound represented by (C-1a-4), (In the formula (C-1a-4), R a and R b may be the same or different from each other, and each represents a hydrocarbyl group having 1 to 15, preferably 1 to 4 carbon atoms, Y represents a halogen atom, p is a number of 0<p≤3, q is a number of 0≤q<3, s is a number of 0≤s<3, and p+q+s=3).
[0176] Specific examples of the organoaluminum compounds belonging to the general formula (C1-a) include tri-n-alkylaluminums such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, tripropylaluminum, tripentylaluminum, trihexylaluminum, trioctylaluminum and tridecylaluminum; tri-branched alkylaluminums such as triisopropylaluminum, triisobutylaluminum, tri-sec-butylaluminum, tri-tert-butylaluminum, tri-2-methylbutylaluminum, tri-3-methylbutylaluminum, tri-2-methylpentylaluminum, tri-3-methylpentylaluminum, tri-4-methylpentylaluminum, tri-2-methylhexylaluminum, tri-3-methylhexylaluminum and tri-2-ethylhexylaluminum; tricycloalkylaluminums such as tricyclohexylaluminum and tricyclooctylaluminum; triarylaluminums such as triphenylaluminum and tritolylaluminum; dialkylaluminum hydrides such as diisobutylaluminum hydride; (i-C4H9) x Al y (C5H 10 ) z(In the formula, x, y, and z are positive numbers, z ≥ 2x.) These include tri-isoprene-aluminum and other trienyl aluminum; aluminum isobutylmethoxide, aluminum isobutylethoxide, aluminum isobutylisopropoxide and other alkylalkanol aluminum; aluminum dimethylmethoxide, aluminum diethylethoxide, aluminum dibutylbutoxide and other dialkylalkanol aluminum; aluminum ethyl sesquiethanol, aluminum butyl sesquibutoxide and other alkyl sesquibutoxide aluminum; and aluminum with R a 2.5 Al(OR) b ) 0.5 The average composition represented by the partially alkoxylated alkylaluminum (where R is the average composition of the alkylaluminum) is: a and R b These can be the same or different, representing hydrocarbon groups with 1 to 15 carbon atoms, preferably 1 to 4; dialkylaryloxyaluminum such as diethylphenolaluminum, diethyl(2,6-di-tert-butyl-4-methylphenol)aluminum, ethylbis(2,6-di-tert-butyl-4-methylphenol)aluminum, diisobutyl(2,6-di-tert-butyl-4-methylphenol)aluminum, and isobutylbis(2,6-di-tert-butyl-4-methylphenol)aluminum; dimethylaluminum chloride, diethylaluminum chloride, dibutylaluminum bromide, and diisobutylaluminum chloride. Alkyl aluminum halides such as dialkyl aluminum halides; alkyl silsesquichlorides such as ethyl aluminum silsesquichloride, butyl aluminum silsesquichloride, and ethyl aluminum silsesquibromide; partially halogenated alkyl aluminum halides such as ethyl aluminum dichloride, propyl aluminum dichloride, and butyl aluminum dibromide; dialkyl aluminum hydrides such as diethyl aluminum hydride and dibutyl aluminum hydride; other partially hydrogenated alkyl aluminum halides such as ethyl aluminum dihydride and propyl aluminum dihydride; and partially alkoxylated and halogenated alkyl aluminum halides such as ethyl aluminum ethoxychloride, butyl aluminum butoxychloride, and ethyl aluminum ethoxybromide.
[0177] Alternatively, compounds similar to (C1-a) can also be used in this invention. Examples of such compounds include organoaluminum compounds formed by the bonding of two or more aluminum compounds through nitrogen atoms. Specifically, examples of such compounds include (C2H5)2AlN(C2H5)Al(C2H5)2.
[0178] Examples of compounds belonging to the above general formula (C1-b) include LiAl(C2H5)4 and LiAl(C7H5)4. 15 ) 4, etc.
[0179] Examples of compounds belonging to the above general formula (C1-c) include dimethyl magnesium, diethyl magnesium, dibutyl magnesium, butylethyl magnesium, dimethyl zinc, diethyl zinc, diphenyl zinc, di-n-propyl zinc, diisopropyl zinc, di-n-butyl zinc, diisobutyl zinc, bis(pentafluorophenyl) zinc, dimethyl cadmium, and diethyl cadmium.
[0180] In addition, as (C1) organometallic compounds, methyl lithium, ethyl lithium, propyl lithium, butyl lithium, methyl magnesium bromide, methyl magnesium chloride, ethyl magnesium bromide, ethyl magnesium chloride, propyl magnesium bromide, propyl magnesium chloride, butyl magnesium bromide, butyl magnesium chloride, etc. can also be used.
[0181] Alternatively, compounds that can form the above-mentioned organoaluminum compounds within a polymerization system, such as combinations of aluminum halides and alkyllithium, or combinations of aluminum halides and alkylmagnesium, can be used as the above-mentioned (C1) organometallic compounds.
[0182] The (C1) organometallic compounds mentioned above can be used alone or in combination of two or more.
[0183] The (C1) organometallic compound is used in an amount where the molar ratio (C1 / M) of the (C1) organometallic compound and the transition metal atom (M) in the transition metal compound contained in the catalyst for olefin polymerization is typically 0.01 to 100,000, preferably 0.05 to 50,000.
[0184] ((C2) Organoaluminum oxide) The (C2) organoaluminum oxide used in this invention can be a previously known aluminum oxide, or a benzene-insoluble organoaluminum oxide as exemplified in Japanese Patent Application Publication No. 2-78687. Specifically, examples of (C2) organoaluminum oxides include methylaluminoxane, ethylaluminoxane, and isobutylaluminoxane.
[0185] Previously known aluminoxanes could be manufactured using methods such as (1) to (3) described below, and were usually obtained in the form of a solution in a hydrocarbon solvent.
[0186] Method (1) involves adding an organoaluminum compound such as trialkylaluminum to a hydrocarbon medium suspension containing a compound with adsorbed water or a salt containing water of crystallization, such as magnesium chloride hydrate, copper sulfate hydrate, aluminum sulfate hydrate, nickel sulfate hydrate, cerium chloride hydrate, etc., so that the adsorbed water or water of crystallization reacts with the organoaluminum compound.
[0187] Method (2) involves directly applying water, ice, or water vapor to organoaluminum compounds such as trialkylaluminum in media such as benzene, toluene, diethyl ether, or tetrahydrofuran.
[0188] Method (3) involves reacting organotin oxides such as dimethyltin oxide and dibutyltin oxide with organoaluminum compounds such as trialkylaluminum in media such as decane, benzene, and toluene.
[0189] It should be noted that the aforementioned aluminoxane may contain a small amount of organometallic components. Alternatively, after distilling away the solvent or unreacted organoaluminum compounds from the recovered aluminoxane solution, the resulting aluminoxane can be redissolved in a solvent or suspended in a poor solvent for aluminoxane.
[0190] As for the organoaluminum compounds used in the preparation of aluminoxanes, specifically, the same organoaluminum compounds as those exemplified as organoaluminum compounds belonging to the above general formula (C1-a) can be cited.
[0191] Among them, trialkylaluminum and tricycloalkylaluminum are preferred, and trimethylaluminum is particularly preferred. The organoaluminum compounds described above can be used alone or in combination of two or more.
[0192] Examples of solvents used for preparing aluminoxanes include aromatic hydrocarbons such as benzene, toluene, xylene, cumene, and umbelliferous hydrocarbons; aliphatic hydrocarbons such as pentane, hexane, heptane, octane, decane, dodecane, hexadecane, and octadecane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cyclooctane, and methylcyclopentane; petroleum fractions such as gasoline, kerosene, and light oil; or halides, especially chlorides and bromides, of the aforementioned aromatic hydrocarbons, aliphatic hydrocarbons, and alicyclic hydrocarbons. Ethers such as diethyl ether and tetrahydrofuran can also be used. Among these solvents, aromatic hydrocarbons or aliphatic hydrocarbons are particularly preferred.
[0193] Furthermore, the benzene-insoluble organoaluminum oxide compound used in this invention is preferably a compound whose Al content, calculated by Al atom conversion, is generally 10% or less, preferably 5% or less, and particularly preferably 2% or less in benzene, i.e., it is insoluble or poorly soluble in benzene.
[0194] As the (C2) organoaluminum oxide used in this invention, examples of boron-containing organoaluminum oxides represented by the following general formula (III) can also be cited.
[0195] [Chemical Formula 12] (In general formula (III), R) 17 This indicates a hydrocarbon group with 1 to 10 carbon atoms, represented by 4 R's. 18 These can be the same or different, representing hydrocarbon groups with 1 to 10 carbon atoms, consisting of hydrogen atoms, halogen atoms, and carbon atoms. The organoaluminum oxide containing boron represented by the above general formula (III) can be produced by reacting an alkylboronic acid represented by the following general formula (IV) with an organoaluminum compound in an inactive gas atmosphere and in an inactive solvent at a temperature of -80°C to room temperature for 1 minute to 24 hours.
[0196] R 19-B(OH)2…(IV) (In general formula (IV), R) 19 R represents the expression in general formula (III) above. 17 Same group. Specific examples of alkylboronic acids represented by the above general formula (IV) include methylboronic acid, ethylboronic acid, isopropylboronic acid, n-propylboronic acid, n-butylboronic acid, isobutylboronic acid, n-hexylboronic acid, cyclohexylboronic acid, phenylboronic acid, 3,5-difluorophenylboronic acid, pentafluorophenylboronic acid, and 3,5-bis(trifluoromethyl)phenylboronic acid. Among these, methylboronic acid, n-butylboronic acid, isobutylboronic acid, 3,5-difluorophenylboronic acid, and pentafluorophenylboronic acid are preferred. One of these can be used alone or in combination of two or more.
[0197] As organoaluminum compounds that react with such alkylboronic acids, specifically, the same organoaluminum compounds as those exemplified as organoaluminum compounds belonging to the above general formula (C1-a) can be cited.
[0198] As the aforementioned organoaluminum compounds, trialkylaluminum, tricycloalkylaluminum, and particularly trimethylaluminum, triethylaluminum, and triisobutylaluminum are preferred. They can be used alone or in combination of two or more.
[0199] If the catalyst for olefin polymerization contains (C2) organoaluminum oxide, it becomes a catalyst with high polymerization activity for olefin compounds, and is therefore preferred.
[0200] The (C2) organoaluminum oxide compounds mentioned above can be used alone or in combination of two or more.
[0201] The organoaluminum oxide (C2) is used in an amount in which the molar ratio (C2 / M) of aluminum atoms in the organoaluminum oxide (C2) to transition metal atoms (M) in the transition metal compound contained in the catalyst for olefin polymerization is typically 10 to 500,000, preferably 20 to 100,000.
[0202] (C3) Compounds that can react with transition metal compounds to form ion pairs. (C3) A compound that can react with a transition metal compound to form an ion pair is a compound that can react with a transition metal compound contained in a catalyst for olefin polymerization to form an ion pair. The transition metal compound contained in a catalyst for olefin polymerization refers to a transition metal compound of Group 4 of the periodic table [A] used in step (A) above, which contains a ligand having a dimethylsilyl bisindenyl skeleton, or a transition metal compound of Group 4 of the periodic table [B] used in step (B) that contains a bridged metallocene compound.
[0203] Examples of Lewis acids, ionic compounds, borane compounds, and carborane compounds described in Japanese Patent Application Publications Nos. 1-501950, 1-502036, 3-179005, 3-179006, 3-207703, 3-207704, and USP-5321106, as well as other similar publications, include those containing (C3) compounds capable of reacting with transition metal compounds to form ion pairs (hereinafter referred to as "ionized ionic compounds"). Furthermore, heteropoly compounds and homopoly compounds may also be cited.
[0204] Specifically, as Lewis acids mentioned above, examples include compounds represented by BR3 (where R is a phenyl or fluorine group that may have substituents such as fluorine, methyl, or trifluoromethyl), such as boron trifluoride, triphenylboron, tris(4-fluorophenyl)boron, tris(3,5-difluorophenyl)boron, tris(4-fluoromethylphenyl)boron, tris(pentafluorophenyl)boron, tris(p-tolyl)boron, tris(o-tolyl)boron, tris(3,5-dimethylphenyl)boron, etc.
[0205] Examples of such ionic compounds include those represented by the general formula (V).
[0206] [Chemical Formula 13] (In general formula (V), R) 20 For H + Carbium cations, oxonium cations, ammonium cations, phosphonium cations, cycloheptyltrienyl cations, or ferrocene cations containing transition metals, R 21 ~R 24 They can be the same or different from each other, and are organic groups, preferably aryl or substituted aryl.
[0207] Specifically, examples of the aforementioned carbium cations include triphenylcarbium cations, tri(methylphenyl)carbium cations, tri(dimethylphenyl)carbium cations, and other trisubstituted carbium cations.
[0208] Specifically, examples of the aforementioned ammonium cations include trialkylammonium cations such as trimethylammonium cation, triethylammonium cation, tripropylammonium cation, tributylammonium cation, and tri(n-butyl)ammonium cation; N,N-dimethylaniline-onium cations such as N,N-diethylaniline-onium cation, N,N-2,4,6-pentamethylaniline-onium cation; and dialkylammonium cations such as di(isopropyl)ammonium cation and dicyclohexylammonium cation.
[0209] Specifically, examples of the aforementioned phosphonium cations include triphenylphosphonium cations, tri(methylphenyl)phosphonium cations, tri(dimethylphenyl)phosphonium cations, and other triarylphosphonium cations.
[0210] As R 20 Preferably, it contains carbium cations and ammonium cations, and particularly preferably triphenylcarbium cations, N,N-dimethylaniline cations, and N,N-diethylaniline cations.
[0211] In addition, trialkyl-substituted ammonium salts, N,N-dialkylaniline onium salts, dialkylammonium salts, triarylphosphonium salts, etc., can also be cited as ionic compounds.
[0212] Examples of the aforementioned trialkyl-substituted ammonium salts include, for instance, triethylammonium tetra(phenyl)boron, tripropylammonium tetra(phenyl)boron, tri(n-butyl)ammonium tetra(phenyl)boron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o-tolyl)boron, tri(n-butyl)ammonium tetra(pentafluorophenyl)boron, tripropylammonium tetra(o,p-dimethylphenyl)boron, tri(n-butyl)ammonium tetra(m,m-dimethylphenyl)boron, tri(n-butyl)ammonium tetra(p-trifluoromethylphenyl)boron, tri(n-butyl)ammonium tetra(3,5-bistrifluoromethylphenyl)boron, and tri(n-butyl)ammonium tetra(o-tolyl)boron.
[0213] Examples of the aforementioned N,N-dialkylaniline onium salts include, for instance, N,N-dimethylaniline onium tetra(phenyl)boron, N,N-diethylaniline onium tetra(phenyl)boron, and N,N,2,4,6-pentamethylaniline onium tetra(phenyl)boron.
[0214] Examples of the aforementioned dialkylammonium salts include, for instance, di(1-propyl)ammonium tetra(pentafluorophenyl)boron and dicyclohexylammonium tetra(phenyl)boron.
[0215] In addition, examples of ionic compounds include triphenylcarbazium tetra(pentafluorophenyl)borate, N,N-dimethylaniline tetra(pentafluorophenyl)borate, ferrocene tetra(pentafluorophenyl)borate, triphenylcarbazium pentaphenylcyclopentadienyl complex, N,N-diethylaniline pentaphenylcyclopentadienyl complex, and boron compounds represented by formulas (VI) or (VII) below.
[0216] [Chemical Formula 14] (In formula (VI), Et represents ethyl.) [Chemical Formula 15] (In formula (VII), Et represents ethyl.) Regarding borane compounds as examples of ionized ionic compounds (compounds [C3]), specifically, examples include decborane; salts of anions such as bis[tris(n-butyl)ammonium]nonabortate, bis[tris(n-butyl)ammonium]decborate, bis[tris(n-butyl)ammonium]undecobortate, bis[tris(n-butyl)ammonium]dodecobortate, bis[tris(n-butyl)ammonium]dodecochlorodecobortate, and bis[tris(n-butyl)ammonium]dodecochlorododecobortate; and salts of metal borane anions such as tri(n-butyl)ammonium bis(dodecanoyldodecobortate)cobaltate (III) and bis[tris(n-butyl)ammonium]bis(dodecanoyldodecobortate)nickelate (III).
[0217] Regarding carborane compounds as examples of ionized ionic compounds, examples include, for instance, 4-carbanonaborane, 1,3-dicarbanonaborane, 6,9-dicarbodecoborane, dodecahydro-1-phenyl-1,3-dicarbanonaborane, dodecahydro-1-methyl-1,3-dicarbanonaborane, and undecanohydro-1,3-dimethyl-1,3-dicarbanonaborane. 7,8-Dicarboundecorane, 2,7-Dicarboundecorane, Undecylhydro-7,8-dimethyl-7,8-dicarboundecorane, Dodecahydro-11-methyl-2,7-Dicarboundecorane, Tris(n-butyl)ammonium 1-carbodecorate, Tris(n-butyl)ammonium 1-carboundecorate, Tris(n-butyl)ammonium 1-carbododecorate, Tris(n-butyl)ammonium 1-trimethylsilyl-1-carbodecorate, Tris (n-Butyl)ammonium bromide-1-carbododecoborate, tris(n-Butyl)ammonium 6-carbodecoborate, tris(n-Butyl)ammonium 6-carboundecoborate, tris(n-Butyl)ammonium 7-carboundecoborate, tris(n-Butyl)ammonium 7,8-dicarboundecoborate, tris(n-Butyl)ammonium 2,9-dicarboundecoborate, tris(n-Butyl)ammonium dodecahydro-8-methyl-7,9-dicarboundecoborate, tris(n-Butyl)ammonium undecylhydro Salts of anions such as -8-ethyl-7,9-dicarboundecanoborate, tris(n-butyl)ammonium undecanohydro-8-butyl-7,9-dicarboundecanoborate, tris(n-butyl)ammonium undecanohydro-8-allyl-7,9-dicarboundecanoborate, tris(n-butyl)ammonium undecanohydro-9-trimethylsilyl-7,8-dicarboundecanoborate, and tris(n-butyl)ammonium undecanohydro-4,6-dibromo-7-carboundecanoborate; Tris(n-butyl)ammonium bis(nonahydro-1,3-dicarboborate)cobaltate (III), Tris(n-butyl)ammonium bis(undecande ... Salts of metal carborane anions, such as ferrates (III), tri(n-butyl)ammonium bis(nonahydro-7,8-dimethyl-7,8-dicarboundecanoborate) chromate (III), tri(n-butyl)ammonium bis(tribromooctahydro-7,8-dicarboundecanoborate) cobaltate (III), tri[tri(n-butyl)ammonium] bis(undecaphydro-7-carboundecanoborate) chromate (III), bis[tri(n-butyl)ammonium] bis(undecaphydro-7-carboundecanoborate) manganate (IV), bis[tri(n-butyl)ammonium] bis(undecaphydro-7-carboundecanoborate) cobaltate (III), and bis[tri(n-butyl)ammonium] bis(undecaphydro-7-carboundecanoborate) nickelate (IV).
[0218] Examples of heteropoly compounds, as ionized ionic compounds, are compounds containing atoms selected from silicon, phosphorus, titanium, germanium, arsenic, and tin, and one or more atoms selected from vanadium, niobium, molybdenum, and tungsten. Specifically, examples include phosphovanadic acid, germanovanadic acid, arsenicvanadic acid, phosphoniobic acid, germanoniobic acid, silimolybdic acid, phosphomolybdic acid, titanomolybdic acid, germanomolybdic acid, arsenicmolybdic acid, stanmolybdic acid, phosphotungstic acid, germanotungstic acid, stantungstic acid, phosphomolybdic acid, phosphotungstic acid, germanotungstic acid, phosphomolybdic acid, germanotungstic acid, phosphomolybdic acid, phosphomolybdic acid, phosphomolybdic acid, niobic acid, and salts of these acids, but are not limited to these. Furthermore, examples of the aforementioned salts include salts formed by the aforementioned acids with metals of Group 1 or Group 2 of the periodic table, specifically lithium, sodium, potassium, rubidium, cesium, beryllium, magnesium, calcium, strontium, barium, etc., and organic salts such as triphenylethyl salts.
[0219] Examples of ionized ionic compounds include compounds composed of metal ions selected from vanadium, niobium, molybdenum, and tungsten, which can be considered as molecular ions of metal oxides. Specifically, examples include vanadic acid, niobic acid, molybdic acid, tungstic acid, and salts of these acids, but are not limited to these. Furthermore, examples of such salts include salts formed by the aforementioned acids with metals from Group 1 or Group 2 of the periodic table, specifically lithium, sodium, potassium, rubidium, cesium, beryllium, magnesium, calcium, strontium, and barium, as well as organic salts such as triphenylethyl salts.
[0220] The ionized ionic compounds (compounds (C3) that can react with transition metal compounds contained in catalysts for olefin polymerization to form ion pairs) described above can be used alone or in combination of two or more.
[0221] The ionized ionic compound (C3) is used in an amount in which the molar ratio (C3 / M) of the ionized ionic compound (C3) and the transition metal atom (M) in the transition metal compound contained in the catalyst for olefin polymerization is typically 1 to 10, preferably 1 to 5.
[0222] 〔monomer〕 In this invention, during the polymerization process, without prejudice to the purpose of the invention, at least one monomer selected from α-olefins having 3 to 20 carbon atoms may be used as a copolymerizing component, together with ethylene and propylene, or ethylene and 1-butene. Specific examples of α-olefins having 3 to 20 carbon atoms that can be used as copolymerizing components include propylene, 1-butene, 2-methyl-1-propylene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, and 1-heptene. Alkenes, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, etc. Among these, α-olefins selected from 1-butene, 1-pentene, 1-hexene, and 1-octene are preferred.
[0223] It should be noted that ethylene, propylene, 1-butene, and α-olefins with 3 to 20 carbon atoms can be feedstocks derived from naphtha, bio-naphtha, or a combination of naphtha and bio-naphtha feedstocks. Additionally, it may include one or more feedstocks derived from chemical recycling.
[0224] [Other processes] In the method for manufacturing the olefinic resin (β) of the present invention, in addition to the steps (A) and (B) described above, a step may also be included as needed to recover the polymer generated in steps (A) or (B), or steps (A) and (B). This step is a step of separating the organic solvent used in steps (A) and (B) and removing the polymer. There are no particular limitations as long as the steps are known, such as solvent concentration, extrusion degassing, granulation, crystallization, etc.
[0225] <Resin Composition (X)> The resin composition (X) of the present invention is a composition containing the above-mentioned olefin resin (β), propylene polymer (α1), and ethylene polymer (α2). The propylene polymer (α1) is a polymer or copolymer having mainly structural units derived from propylene, and the ethylene polymer (α2) is a polymer or copolymer having mainly structural units derived from ethylene.
[0226] [Propylene polymers (α1)] The resin composition (X) of the present invention may contain an propylene polymer (α1).
[0227] Examples of propylene-based polymers (α1) include propylene homopolymers (homopolymer polypropylene) and copolymers of propylene with α-olefins having 2 to 20 carbon atoms other than propylene. The copolymers of propylene with the aforementioned α-olefins can be random copolymers (random polypropylene) or block copolymers (block polypropylene).
[0228] Here, specific examples of α-olefins with 2 to 20 carbon atoms, excluding propylene, include ethylene, 1-butene, 2-methyl-1-propene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1- Heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, etc. Among these, α-olefins with 2 to 10 carbon atoms, excluding propylene, such as ethylene, 1-butene, 1-pentene, 1-hexene, and 1-octene, are preferred.
[0229] The α-olefin having 2 to 20 carbon atoms, excluding propylene, can be a single type or two or more types. From the viewpoint of excellent whitening resistance of the resin composition (X) containing olefin resin (β) and the molded article, it is preferable that the α-olefin having 2 to 20 carbon atoms, excluding propylene, is one type or two or more types, more preferably one type or two types.
[0230] The propylene-based polymer (α1) may have at least one structural unit derived from a monomer derived from biomass. Examples of monomers derived from biomass include propylene from biomass, ethylene from biomass, and α-olefins from biomass with 4 to 20 carbon atoms. The same type of monomers constituting the polymer may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0231] The resin composition (X) of the present invention may contain one or more propylene polymers (α1), but from the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength of the resin composition (X) containing olefin resin (β) and the molded article, and excellent whitening resistance, in a preferred embodiment, the resin composition (X) of the present invention contains two or more propylene polymers (α1).
[0232] In this invention, the propylene polymer (α1) can be any of the manufactured products, commercially available products, or recycled products obtained by polymerization or copolymerization.
[0233] When the propylene polymer (α1) is a copolymer of propylene and an α-olefin having 2 to 20 carbon atoms other than propylene, the propylene polymer (α1) contains preferably more than 50 mol%, more preferably more than 60 mol%, further preferably more than 70 mol%, especially preferably more than 80 mol%, particularly preferably more than 90 mol%, and extremely preferably more than 95 mol% of structural units (iv) derived from propylene.
[0234] On the other hand, the propylene polymer (α1) preferably contains 50 mol% or less, more preferably 40 mol% or less, further preferably 30 mol% or less, particularly preferably 20 mol% or less, especially preferably 10 mol% or less, and extremely preferably 5 mol% or less of structural units (v) derived from α-olefins having 2 to 20 carbon atoms other than propylene. (Where the total content of structural units (iv) and structural units (v) is set to 100 mol%.)
[0235] In addition, when the propylene polymer (α1) is a copolymer of propylene and two α-olefins with 2 to 20 carbon atoms other than propylene, the propylene polymer (α1) may contain 53 mol% or more and less than 95 mol% of structural units (iv) derived from propylene.
[0236] On the other hand, it may contain more than 2 mol% and less than 23 mol% of structural units from α-olefins with fewer carbon atoms (excluding propylene), and may contain more than 3 mol% and less than 24 mol% of structural units from α-olefins with more carbon atoms (excluding propylene). (Where, in the case that the propylene polymer (α1) is a copolymer of propylene and two or more α-olefins, the content of structural units from α-olefins refers to the total content of structural units from two or more α-olefins, and the total content of structural units (iv) and (v) is set to 100 mol%). The content of the above structural units can be utilized... 1 H-NMR or 13 The measurements were performed using C-NMR.
[0237] When the propylene polymer (α1) is a manufactured product obtained by polymerization or copolymerization, it can be manufactured by polymerizing or copolymerizing monomers with propylene as the main component using known olefin polymerization catalysts, such as Ziegler-Natta catalysts.
[0238] When the propylene polymer (α1) is a commercially available product, it can be used without particular restriction. Examples of commercially available propylene polymers (α1) include so-called homopolymer polypropylene resin (a resin formed essentially from a homopolymer of propylene), atactic polypropylene resin, and block polypropylene resin. From the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength of the resin composition (X) containing olefin resin (β) and the molded article, and excellent whitening resistance, it is preferred that the propylene polymer (α1) contains atactic polypropylene resin.
[0239] When the propylene polymer (α1) is a recycled product, substances obtained by washing, crushing, and granulating recycled plastics or plastic products with propylene polymer (α1) as the main component can be used.
[0240] The preferred method for propylene polymers (α1) will be described below.
[0241] For propylene polymers (α1), the melt flow rate (MFR) measured according to ASTM D1238 at 230°C and a load of 2.16 kg is preferably 0.01 to 500 g / 10 min. From the viewpoint of improving fluidity, the lower limit of MFR is preferably 0.02 g / 10 min, more preferably 0.03 g / 10 min. From the viewpoint of improving the strength of propylene polymers (α1) themselves, the upper limit is preferably 300 g / 10 min, more preferably 100 g / 10 min, and particularly preferably 50 g / 10 min.
[0242] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, the melt flow rate (MFR) of the propylene polymer (α1) is more preferably 0.01 to 100 g / 10 min, further preferably 0.01 to 80 g / 10 min, especially preferably 0.01 to 50 g / 10 min, particularly preferably 0.01 to 20 g / 10 min, further particularly preferably 0.5 to 20 g / 10 min, and extremely preferably 0.5 to 10 g / 10 min.
[0243] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, the melt flow rate (MFR) of the propylene polymer (α1) is more preferably 0.01 to 100 g / 10 min, further preferably 0.01 to 50 g / 10 min, especially preferably 0.01 to 25 g / 10 min, and particularly preferably 2.5 to 10 g / 10 min.
[0244] When the melt flow rate (MFR) of the propylene polymer (α1) meets such a range, the resin composition (X) of the present invention and the molded article have excellent balance between impact resistance and elongation or between impact resistance and strength, excellent whitening resistance, and excellent molding processability, and are therefore preferred.
[0245] The weight-average molecular weight (Mw) of the propylene polymer (α1) as converted to polystyrene, determined by gel permeation chromatography (GPC), is preferably 80,000 to 900,000, more preferably 100,000 to 700,000, and particularly preferably 150,000 to 700,000.
[0246] The terminal structures of propylene polymers (α1) are typically substantially saturated hydrocarbons. Specifically, the proportion of unsaturated terminals in propylene polymers (α1) is usually less than 0.1 per 1000 carbon atoms.
[0247] The melting point (Tm) of the propylene polymer (α1), as determined by differential scanning calorimetry (DSC), is preferably 100-170°C, more preferably 120-170°C.
[0248] [Vinyl polymers (α2)] The resin composition (X) of the present invention may contain an ethylene polymer (α2).
[0249] The ethylene-based polymer (α2) may have at least one structural unit derived from a monomer derived from biomass. Examples of monomers derived from biomass include ethylene derived from biomass and α-olefins derived from biomass with 3 to 20 carbon atoms. The same type of monomers constituting the polymer may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0250] The ethylene polymer (α2) contained in the resin composition (X) of the present invention may be one or more types.
[0251] By including the ethylene polymer (α2) in the resin composition (X) of the present invention, it is possible to obtain a molded article with a balance between impact resistance and elongation or a balance between impact resistance and strength, as well as excellent resistance to whitening.
[0252] As the ethylene-based polymer (α2), any polymer from ethylene homopolymers or ethylene-based copolymers containing more than 50 mol% of structural units derived from ethylene can be used. The ethylene-based polymer (α2) contains preferably 60 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more of structural units derived from ethylene.
[0253] Preferably, the ethylene-based polymer (α2) is a homopolymer of ethylene, or a copolymer of ethylene and at least one α-olefin selected from those having 3 to 20 carbon atoms. From the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent resistance to whitening, the ethylene-based polymer (α2) preferably comprises a copolymer with at least one α-olefin selected from those having 3 to 20 carbon atoms, more preferably a copolymer with at least one α-olefin selected from those having 3 to 20 carbon atoms. The copolymer can be a random copolymer or a block copolymer. Specific examples of the aforementioned α-olefins with 3 to 20 carbon atoms include propylene, 1-butene, 2-methyl-1-propene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, and so on. The α-olefins include propylene, 1-butene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene. Among these, α-olefins from propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene are preferred, as are α-olefins from 1-butene, 1-pentene, and 1-hexene.
[0254] The content of ethylene-derived structural units (vi) in the ethylene polymer (α2) is 60-99 mol%, preferably 65-99 mol%, more preferably 70-99 mol%, and particularly preferably 80-99 mol%.
[0255] The content of structural units (vii) derived from α-olefins with 3 to 20 carbon atoms in the vinyl polymer (α2) is 1 to 40 mol%, preferably 1 to 35 mol%, more preferably 1 to 30 mol%, and particularly preferably 1 to 20 mol%.
[0256] Their content is relative to 100 mol% of the total structural units derived from ethylene and α-olefins with 3 to 20 carbon atoms.
[0257] The content of the above structural units can be utilized 1 H-NMR or 13 The measurements were performed using C-NMR.
[0258] If the content of structural units is within the above range, it is easy to obtain molded articles with excellent balance between impact resistance and elongation or between impact resistance and strength, as well as excellent resistance to whitening.
[0259] The vinyl polymer (α2) can be composed of a single polymer from the above polymers or a combination of polymers.
[0260] In this invention, the ethylene polymer (α2) can be any of the manufactured products, commercially available products, or recycled products obtained by polymerization or copolymerization.
[0261] When the ethylene-based polymer (α2) is a product obtained by polymerization or copolymerization, it can be manufactured by polymerizing or copolymerizing monomers with ethylene as the main component using known catalysts for olefin polymerization, such as Ziegler-Natta catalysts.
[0262] When ethylene-based polymers (α2) are commercially available, they can be used without particular restrictions. Examples of commercially available ethylene-based polymers include so-called homopolymer polyethylene resins, ethylene-α-olefin copolymers, ethylene-based elastomers, and other polyethylene-based resins.
[0263] When the ethylene polymer (α2) is a recycled product, substances obtained by washing, crushing, and granulating recycled plastics or plastic products with ethylene polymers as the main component can be used.
[0264] The preferred method for ethylene-based polymers (α2) will be described below.
[0265] For ethylene-based polymers (α2), the density measured at 25°C according to ASTM D1505 (density measured using the density gradient tube method) is preferably 840 kg / m³. 3 The above, more preferably 845 kg / m 3 The above is further optimized to 850 kg / m 3 The above is particularly preferred, with 855 kg / m³ being the optimal value. 3 The preferred value is 940 kg / m³. 3 The following is more preferably 920 kg / m 3 The following is a further preferred value: 900 kg / m 3 The following is particularly preferred: 890 kg / m 3 The optimal value is 885 kg / m³. 3 The following is preferred: 840 kg / m³ 3 ~940kg / m 3 More preferably 845 kg / m 3~920kg / m 3 Further optimized to 850 kg / m 3 ~900kg / m 3 The preferred value is 855 kg / m³. 3 ~890kg / m 3 The optimal value is 855 kg / m³. 3 ~885kg / m 3 .
[0266] If the density is within the above range, it is easy to obtain molded articles with excellent balance between impact resistance and elongation or between impact resistance and strength, as well as excellent resistance to whitening.
[0267] For vinyl polymers (α2), the melt flow rate (MFR) measured according to ASTM D1238 at 190°C and a load of 2.16 kg is preferably 0.01 to 500 g / 10 min. From the viewpoint of improving fluidity, the lower limit of MFR is preferably 0.02 g / 10 min, more preferably 0.03 g / 10 min. From the viewpoint of improving the strength of vinyl polymers (α2) themselves, the upper limit is preferably 300 g / 10 min, more preferably 100 g / 10 min, and particularly preferably 50 g / 10 min.
[0268] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, from the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent whitening resistance, the MFR of the ethylene polymer (α2) is more preferably 0.01 to 5.0 g / 10 min, further preferably 0.01 to 2.0 g / 10 min, especially preferably 0.1 to 1.5 g / 10 min, and particularly preferably 0.2 to 1.3 g / 10 min.
[0269] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, from the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent whitening resistance, the MFR of the propylene polymer (α1) is more preferably 0.5 to 500 g / 10 min, further preferably 0.5 to 100 g / 10 min, and especially preferably 0.6 to 20 g / 10 min.
[0270] The weight-average molecular weight (Mw) of the vinyl polymer (α2) obtained by gel permeation chromatography (GPC) based on polystyrene is preferably 40,000 to 900,000, more preferably 60,000 to 700,000, and particularly preferably 80,000 to 700,000.
[0271] The terminal structures of vinyl polymers (α2) are typically substantially saturated hydrocarbons. Specifically, the proportion of unsaturated terminals in vinyl polymers (α2) is usually less than 0.1 per 1000 carbon atoms.
[0272] [Resin Composition (X)] Examples of the resin composition (X) of the present invention include a resin composition comprising an olefin resin (β) and an propylene polymer (α1), a resin composition comprising an olefin resin (β), an propylene polymer (α1) and an ethylene polymer (α2), and a resin composition comprising an olefin resin (β) and an ethylene polymer (α2), but preferably a resin composition comprising an olefin resin (β), an propylene polymer (α1) and an ethylene polymer (α2).
[0273] The resin composition (X) of the present invention more preferably contains a propylene polymer (α1) and an ethylene polymer (α2) in a mass ratio of 1:99 to 99:1. In the resin composition (X) of the present invention containing both the propylene polymer (α1) and the ethylene polymer (α2), by including an olefin resin (β), it is possible to produce a resin composition in which the propylene polymer (α1) and the ethylene polymer (α2), which are generally incompatible, are uniformly dispersed.
[0274] The resin composition (X) of the present invention may contain one or more of the following: olefin resin (β), propylene polymer (α1), and ethylene polymer (α2).
[0275] The resin composition (X) of the present invention can be a resin composition comprising olefin resin (β), propylene polymer (α1) and ethylene polymer (α2) in any proportion.
[0276] For the resin composition (X) of the present invention, the ratio of the total mass of the olefin resin (β) to the total mass of the propylene polymer (α1) and the ethylene polymer (α2) ((β) / ((α1)+(α2))) is preferably 0.01 to 0.5.
[0277] Here, when the main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer, from the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent whitening resistance, the above ratio ((β) / ((α1)+(α2))) is more preferably 0.02 to 0.23, and even more preferably 0.03 to 0.20.
[0278] Furthermore, when the main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer, from the viewpoints of excellent balance between impact resistance and elongation or between impact resistance and strength, and excellent whitening resistance, the above ratio ((β) / ((α1)+(α2))) is more preferably 0.08 to 0.20, further preferably 0.08 to 0.18, and especially preferably 0.09 to 0.16.
[0279] The resin composition (X) described above can be made into a resin composition in which propylene polymer (α1) and ethylene polymer (α2) are more uniformly dispersed. The resin composition (X) is a resin composition with excellent balance between impact resistance and elongation or between impact resistance and strength, as well as excellent resistance to whitening. Therefore, it is preferred.
[0280] It should be noted that, for the resin composition (X) of the present invention, when the main chain of the grafted olefin polymer [R1] in the olefin resin (β) is an ethylene-1-butene copolymer, in a preferred embodiment, the melt flow rate (MFR) of the propylene polymer (α1), as measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is 0.01 to 25 g / 10 min, and the density of the ethylene polymer (α2), as measured according to ASTM D1505 at 25°C, is 850 to 900 kg / m³. 3 .
[0281] For the resin composition (X) of the present invention, in the case where the main chain of the grafted olefin polymer [R1] in the olefin resin (β) is an ethylene-1-butene copolymer, in a preferred embodiment, The ratio of the total mass of olefin resin (β) to the total mass of propylene polymer (α1) and ethylene polymer (α2) ((β) / ((α1)+(α2))) is 0.08~0.20, and the melt flow rate (MFR) of ethylene polymer (α2) is 0.5~100g / 10min, as determined by ASTM D1238 at 190°C and a load of 2.16kg.
[0282] The resin composition (X) of the present invention may contain other components besides the aforementioned propylene polymer (α1), ethylene polymer (α2), and olefin resin (β) without prejudice to the purpose of the present invention. Examples of other components include other resins, rubbers, inorganic fillers, additives, etc. Examples of additives include weather stabilizers, heat stabilizers, antistatic agents, antislip agents, anti-caking agents, antifogging agents, lubricants, pigments, dyes, plasticizers, anti-aging agents, hydrochloric acid absorbents, antioxidants, nucleating agents, etc.
[0283] The resin composition (X) of the present invention can also be a blend of used recycled (PIR (post-industrial recycling) or PCR (post-consumer recycling) resins. For example, PIR and PCR blends can be used alone or in combination with non-recycled (fresh / unused) polymer resins to prepare articles. The resin composition can be combined with non-recycled plastic resins at, for example, a ratio of 1:99 to 99:1 (e.g., 20:80 to 80:20, 40:60 to 60:40, etc.). Used plastic resins can also be formed to form the resin composition (X) for preparing articles.
[0284] <Method for manufacturing resin composition (X)> The method for manufacturing the resin composition (X) is not particularly limited. For example, it can be prepared by mixing olefin resin (β), propylene polymer (α1), ethylene polymer (α2), and any other components used as needed in the above-described proportions using a Henschel mixer, V-type mixer, belt mixer, drum mixer, kneading extruder, etc., or by melt mixing using a single-screw extruder, twin-screw extruder, kneader, Banbury mixer, etc., whether mixed or not. Furthermore, granulation, pulverization, etc., can be performed as needed.
[0285] When mixing and blending them, the various components can be added all at once or in stages.
[0286] There are no particular limitations on the melt mixing method, and commercially available melt mixing equipment such as extruders can be used. For example, the temperature of the mixing section in the melt mixing equipment is typically 120~250°C, preferably 120~230°C. The mixing time is typically 0.5~30 minutes, particularly preferably 0.5~5 minutes.
[0287] Resin compositions (X) comprising olefin resin (β), olefin resin (β) and propylene polymer (α1), resin compositions (X) comprising olefin resin (β) and ethylene polymer (α2), or resin compositions (X) comprising olefin resin (β), propylene polymer (α1) and ethylene polymer (α2) are suitable for use as granules, hot melt adhesives, coating agents, and skin materials. These hot melt adhesives can be used in automotive parts such as interior and exterior trim components. Furthermore, molded articles comprising resin compositions (X) can also be used in films, sheets, packaging materials using them, nonwoven fabrics, closures, sealing sheet materials, foams, and automotive parts such as interior and exterior trim components.
[0288] Hot melt adhesive Examples of applications of olefin-based resins (β) or resin compositions (X) include hot melt adhesives. The hot melt adhesives disclosed herein can be obtained, for example, by methods such as: sequentially melting and mixing the components in a melt-dissolving tank, such as a heated melting and stirring tank, preferably under vacuum and nitrogen flow, by rotating stirring blades; melting and mixing by applying shear under heating using the double-rotating blades of a kneader; or melting and mixing using the screw of a single-screw or twin-screw extruder. The temperature is typically adjusted within a range of 120–230°C, preferably 150–200°C. Bundles or granules thus prepared can be used for various applications.
[0289] In the case of hot melt adhesives, the adhered objects can be bonded before the adhesive cures, or they can be bonded after the temporarily cured hot melt adhesive has been reheated to activate it. Examples of the shapes of such temporarily cured hot melt adhesives include sheets, films, non-woven fabrics, small flakes, and rods.
[0290] In hot melt adhesives, the content of olefin resin (β) relative to the total amount of adhesive is typically 1 to 90% by mass, preferably 3 to 50% by mass, and more preferably 5 to 40% by mass. A content within the above range is preferred from the viewpoint of the balance between the adhesive strength and coatability of the hot melt adhesive.
[0291] Hot melt adhesives may contain non-crystalline polyalphaolefins (APAO) as needed.
[0292] The melt viscosity of APAO is preferably 500~200,000 mPa·s / 190°C, more preferably 1,000~50,000 mPa·s / 190°C. When the melt viscosity is 500 mPa·s / 190°C or higher, sufficient cohesive force can be obtained, and the adhesive strength of the adhesive is improved. On the other hand, when it is 200,000 mPa·s / 190°C or lower, the workability is improved when applying hot melt adhesive, and therefore it is preferred.
[0293] As components of such APAO, there are various compositions. For example, there are homopolymers or copolymers such as stereopolypropylene and stereopoly-1-butene, or copolymers or trimers of propylene, ethylene, 1-butene, etc., propylene homopolymers, propylene-butene copolymers, propylene-ethylene copolymers, etc.
[0294] Olefin resins (β) also have excellent compatibility with APAO and can be used appropriately.
[0295] Specific examples of APAO include REXtac's RT2730 (melt viscosity at 190°C: 4,000 mPa·s) and VESTOPLAST 704 (product name, Evonik, melt viscosity (190°C): 3,500 mPa·s).
[0296] APAO can be used alone or in combination with two or more types.
[0297] In hot melt adhesives, the content of APAO, relative to the total amount of adhesive, is typically 1 to 99% by mass, preferably 10 to 90% by mass, and more preferably 20 to 80% by mass. A content within the above range is preferred from the viewpoint of the balance of adhesive strength and coatability of the hot melt adhesive.
[0298] Hot melt adhesives may contain tackifiers as needed.
[0299] As a tackifier, examples include at least one resin selected from natural rosin, modified rosin, polyterpene resins, synthetic petroleum resins, benzofuran resins, phenolic resins, xylene resins, styrene resins, low molecular weight styrene resins, and isoprene resins. Among these, rosin resins, polyterpene resins, and synthetic petroleum resins are preferred, and resins having aliphatic and / or alicyclic structures are even more preferred.
[0300] Here, examples of resins particularly preferred as petroleum resins having aliphatic and / or alicyclic structures include partially and fully hydrogenated rosin and their derivatives; homopolymers or copolymers of cyclic terpenes in polyterpene resins; and hydrogenated synthetic petroleum resins, including aliphatic petroleum resins, alicyclic petroleum resins, aliphatic-alicyclic copolymers, and copolymers of naphtha cracking oil with various terpenes.
[0301] As a tackifier, a tackifier with a softening point of 25 to 160°C is preferred. If the softening point is above 25°C, it can prevent seepage to the surface; if the softening point is below 160°C, the viscosity during melting will not become excessively high, resulting in good processability. Specifically, the trade names "ARKON P-70", "ARKON P-90", "ARKON P-100", "ARKON P-115", "ARKON P-125", and "ARKON P-140" (all manufactured by Arakawa Chemical Industry Co., Ltd.) can be appropriately used.
[0302] A single adhesive can be used alone, or two or more can be used together.
[0303] In hot melt adhesives, the content of the tackifier, when used relative to the total amount of adhesive, is typically 1 to 70% by mass, preferably 5 to 50% by mass, and more preferably 10 to 40% by mass. Contents within these ranges are preferred as they impart flowability and adhesive strength without reducing bond strength.
[0304] Hot melt adhesives may contain wax as needed.
[0305] Examples of waxes include synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, and polypropylene wax; petroleum waxes such as paraffin wax and microcrystalline wax; and natural waxes such as wood wax, carnauba wax, and beeswax. Olefin resins (β) have excellent compatibility with polypropylene, therefore polypropylene waxes are particularly preferred.
[0306] The type B viscosity (190°C) of the wax is preferably 10~8000 mPa·s, more preferably 100~5000 mPa·s. If the type B viscosity is within the above range, it is preferred from the perspective of cohesiveness and processability.
[0307] The melting point of the wax, as determined by DSC, is preferably 80-150°C, more preferably 90-140°C. If the melting point is within the above range, it is preferable in terms of flexibility and processability when using adhesives.
[0308] Commercially available waxes include, for example, “Mitsui Hi-WAX 420P”, “Mitsui Hi-WAX NL100”, and “Mitsui Hi-WAX NP015” (all manufactured by Mitsui Chemicals Co., Ltd.).
[0309] One type of wax can be used alone, or two or more types can be used together.
[0310] In hot melt adhesives, the content of wax, when used, is typically 1 to 60% by mass, preferably 1 to 50% by mass, and more preferably 1 to 40% by mass, relative to the total amount of adhesive. Contents within these ranges are preferred as they impart flowability and heat resistance without reducing adhesive strength.
[0311] In hot melt adhesives, at least one additive selected from conventionally known flow modifiers, nucleating agents, antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, pigments, dyes, antibacterial agents, mildew inhibitors, antistatic agents, foaming agents, foaming aids, mineral oils, plasticizers, and fillers may be added as needed, without prejudice to the purpose of this disclosure.
[0312] Regarding the application of hot melt adhesives, there are no particular restrictions as long as the purpose of this disclosure is achieved, and commercially available hot melt coaters can be widely used. Examples of hot melt coaters include slot coaters, roller coaters, spiral coaters capable of spiral coating, Omega coaters capable of wavy coating, controlled slot coaters, slot spray coaters capable of surface coating, curtain spray coaters, dot coaters capable of dot coating, and droplet coaters capable of linear coating. A particularly preferred application for hot melt adhesives is the bonding of corrugated paper to each other.
[0313] As a method for using the hot melt adhesive of this disclosure as a hot melt adhesive, there are the following bonding methods: using a screw extruder having a die section called a T-die method, blow molding method, calendering method, or spinning method, the obtained hot melt adhesive is formed into a sheet, film, or non-woven fabric shape, fixed in the middle of the objects to be laminated, and then heat-bonded; or the adhesive, which has been formed into a sheet shape, is heated and melted on one object to be laminated, and the other object to be laminated is directly pressed together while cooling. Additionally, there are the following methods: using the aforementioned screw extruder to melt the hot melt adhesive of this disclosure, and directly inserting the adhesive between the objects to be laminated without performing the molding process described above, and then heat-bonding; or, if one object to be laminated is a thermoplastic, directly bonding by co-extrusion, or directly coating it onto one object to be laminated and then heat-bonding again.
[0314] Hot melt adhesives are suitable for bonding, for example, substrates formed of polyolefin resins to each other, bonding the substrates to metal materials (e.g., metal plates, metal foils, metal mesh) or other raw materials (e.g., nonwoven fabrics, textiles, cloth, corrugated paper, etc., glass), and bonding the metal materials or other raw materials to each other. They are particularly suitable for bonding corrugated paper to other adhered materials, or bonding corrugated paper to corrugated paper.
[0315] Examples of resin sheets formed from polyolefin resins, etc., include single-layer or laminated resin sheets of polyolefin resins (e.g., polyethylene, polypropylene), polyester resins, polycarbonate resins, polyarylate resins, acrylic resins, polyphenylene sulfide resins, polystyrene resins, vinyl resins, vinyl chloride resins, polyimide resins, epoxy resins, etc.
[0316] Coating Agent As a coating agent in this disclosure, there are no particular limitations; for example, a coating agent prepared by dissolving or dispersing an olefinic resin (β) or a resin composition (X) using the same in an organic solvent may be cited. The coating agent comprises an olefinic resin (β) or a resin composition (X).
[0317] Examples of organic solvents include, for example, aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, and decane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, and decahydronaphthalene; alcohols such as methanol, ethanol, isopropanol, butanol, pentanol, hexanol, and propylene glycol; ketone solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanol, hexanone, isophorone, and acetophenone; cellosols such as methyl cellosol and ethyl cellosol; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and butyl formate; and halogenated hydrocarbons such as trichloroethylene, dichloroethylene, and chlorobenzene. One or more organic solvents may be used.
[0318] There are no particular restrictions on the proportion of organic solvent in the coating agent. For example, it can be more than 30% by mass or more than 40% by mass. Alternatively, it can be less than 90% by mass or less than 80% by mass.
[0319] The coating agent can be used as, for example, an adhesive or heat sealant for metals, an adhesive or heat sealant for polyolefins, or an adhesive or heat sealant for metals and polyolefins. It can also be used as an adhesive for PTP (press-through pack) packaging, an adhesive for lamination, a raw material for coatings, or a raw material for primers. It is particularly suitable when at least one of the adhered materials is a plastic material, and among plastic materials, polyolefin materials, especially polybutene-based materials and polypropylene-based materials, are preferred.
[0320] <Molded Body> The molded article of the present invention can be obtained by molding the resin composition (X) of the present invention described above using known molding methods. For example, it can be obtained using known thermoforming methods such as extrusion molding, injection molding, blow molding, blow molding, extrusion blow molding, injection blow molding, pressure molding, vacuum molding, powder slush molding, calendering, and foam molding.
[0321] The molded articles of the present invention are obtained from resin compositions (X) in which the contained components are highly dispersed, and therefore exhibit excellent impact resistance and elongation. In the present invention, even when both propylene polymers (α1) and ethylene polymers (α2) are contained, the components are more highly dispersed, resulting in molded articles with excellent impact resistance and elongation compared to those containing conventionally known compatibilizers.
[0322] The molded parts of this invention can be used for door interior panels, rear package trims, dashboards, gaskets, seat back garnishes, column covers, bumpers, fenders, side body strips, wheel covers, mudguards, rearview mirror covers, dashboards, exterior doors, engine hoods, spoilers, windshields, wheel hubcaps, mirror frames, body panels, airbag covers, protective side body strips, shoe soles, shoe midsoles, insoles, outsoles, sandals, wire sheaths for automotive or equipment wiring, wire insulation, outer sheaths for other metal wires and cables, housings, pads, heating plates, the main body of rice cookers and kettles, washing machine components, and battery boxes. Containers, electronic component packaging films, waterproof sheets, flooring materials, ceiling materials, wallpaper, building material component packaging sheets, floor mats, floor finishing materials, blackout curtains, pipes, cosmetic sheets or building material protective sheets, TV cabinets, stereo speaker boxes, video cabinets, various storage furniture, complete sets of furniture, and other household appliances, furniture products, doors, door frames, window frames, cornices, baseboards, opening frames, and other residential components, kitchen and storage furniture doors, office area floor mats, carpet anti-slip mats, low-temperature heat-sealing film, easy-tear film, packaging film, single-dose pharmaceutical packaging materials, handles, gaskets, multi-layer hoses, infusion bottles, bottles for shampoo and other hygiene products, cosmetic bottles and boxes, caps, and sealing sheets. Liners, drinking water lid liners, writing instruments and other stationery, toys, leisure products, disposable diapers, disposable underwear, sanitary napkins and other hygiene components and elastic components, clothing storage boxes, buckets, washbasins, cooking utensils, other various boxes, containers, agricultural films, sports field equipment, boat and jet ski parts, garden furniture, rolling flasks and culture media bottles used in cultivation, diaper Velcro, sterilization wraps, rags, bedding, food packaging films, retort packaging materials, retort cookware. Containers, food packaging trays, beverage cups and bottles, various other bottles, cups, sheets, films, tubes, syringes, syringe barrels, ampoules, petri dishes and other medical instruments, medical kits, bags, pouches and bottles for intravenous injection of bandages, medical protective clothing and aprons, surgical drapes, covers for home appliances and residential lighting fixtures, interior lighting covers for automobiles, LED lamp covers for electrical and electronic components, covers for other display devices, solar cell sealing sheets, battery packaging, lithium-ion battery packaging, etc.
[0323] <membrane> Examples of use of olefinic resins (β) or resin compositions (X) include films containing any of them.
[0324] The film containing an olefinic resin (β) or a resin composition (X) using the olefinic resin can be a stretched film or an unstretched film, preferably an unstretched film.
[0325] The aforementioned unstretched film is acceptable as long as it is not stretched; there are no particular limitations. The shape, size (thickness), etc., can be appropriately selected according to the desired application. Furthermore, the unstretched film can be a single layer or multiple layers. In the case of multiple layers, at least one layer must be a film containing an olefin-based resin (β) or the aforementioned resin composition (X). This includes films obtained by co-extrusion using known multilayer film forming methods such as T-die molding or blown film molding, or films obtained by further laminating layers containing an olefin-based resin (β) or the aforementioned resin composition (X) onto a pre-formed substrate. There are no particular limitations on the substrate; sometimes it is a metal such as aluminum plate, steel plate, or stainless steel plate, and sometimes it is a thermoplastic resin. It should be noted that in the case of a multilayer unstretched film, this means that all its layers are unstretched.
[0326] The thickness of the unstretched film (total thickness in the case of multiple layers) is preferably 5 μm or more, more preferably 10 μm or more, preferably 150 μm or less, and more preferably 100 μm or less.
[0327] It should be noted that this specification does not specifically distinguish between membranes and sheets. However, generally, membranes refer to membrane-like bodies with a thickness of less than 250 μm, while sheets refer to thin plate-like bodies with a thickness of more than 250 μm.
[0328] Membranes can be used as, for example, stretch membranes, shrink membranes, breathable membranes, adhesive membranes, and engineering membranes.
[0329] <Sheet> Examples of use of olefinic resins (β) or resin compositions (X) include sheets containing either of them.
[0330] There are no particular limitations on the sheet material described above. The shape, size (thickness), etc., can be appropriately selected according to the intended use. In addition, the sheet material can be a single layer or multiple layers. In the case of multiple layers, at least one layer may be a sheet material containing an olefin resin (β) or the above-mentioned resin composition (X).
[0331] The thickness of the sheet (total thickness in the case of multiple layers) is preferably 250~2000μm, more preferably 250~1500μm.
[0332] Specific uses of the aforementioned sheet include, for example, packaging sheets for packaging food, liquids, pharmaceuticals, etc., and containers formed from the sheet (e.g., trays, cups obtained by thermoforming the sheet, containers obtained by bending the sheet).
[0333] <Injection Molded and Blow Molded Products> The molded body in this disclosure may also be an injection-molded body, for example. There are no particular limitations on the injection-molded body. For example, an injection-molded body can be described as a molded body manufactured by injection molding into a desired shape using conventionally known injection molding apparatus and under known conditions.
[0334] Injection molded parts can be widely used in applications such as interior trim materials for automobiles, exterior trim parts for automobiles, and housings, containers, tubes, or pipes for household appliances.
[0335] The molded body in this disclosure may also be a blow-molded body, for example. There are no particular limitations on the blow-molded body. For example, a molded body manufactured by blow molding into a desired shape using a conventionally known blow molding apparatus and under known conditions can be cited as an example.
[0336] Blow-molded articles can also be multilayer articles, for example. In this case, at least one layer of the multilayer article is a layer containing an olefinic resin (β) or a resin composition (X).
[0337] Specific applications of injection-molded and blow-molded bodies include, for example, food containers, beverage containers, lids, pharmaceutical containers, various other containers, housings for daily necessities and household appliances, automotive parts, pipes, and conduits. Examples of daily necessities include, for example, clothes organizers, buckets, washbasins, stationery such as writing instruments, containers, toys, cooking utensils, and various other boxes.
[0338] <Sealing membrane> As an example of the above-mentioned molded body, a sealing film can be cited.
[0339] The sealing film described above has at least one layer formed of resin composition (X) (hereinafter also referred to as "layer (X)"). The sealing film may be a single layer or a multilayer of two or more layers. In this case, the resin composition (X) is preferably a resin composition (X) containing an olefin resin (β) and an propylene polymer (α1), or a resin composition (X) containing an olefin resin (β), an propylene polymer (α1), and an ethylene polymer (α2).
[0340] The sealing film described above may have two or more layers (X). The sealing film may also have layer (X) and layers other than layer (X). The sealing film may also have two or more of the aforementioned other layers.
[0341] In this specification, no special distinction is made between membranes and sheets. However, generally, membranes refer to membrane-like bodies with a thickness of less than 250 μm, while sheets refer to thin plate-like bodies with a thickness of more than 250 μm.
[0342] The shape, size, and thickness of the sealing film can be appropriately selected according to the desired application. The sealing film can be either a stretched film or an unstretched film, but an unstretched film is preferred. In the case of a multi-layered unstretched film, "unstretched" means that all its layers are not stretched.
[0343] Unstretched membranes are any membranes that are not stretched; there are no particular restrictions. The shape, size, and thickness can be appropriately selected based on the intended application. Unstretched membranes can be single-layered or multi-layered (two or more layers). In the case of multi-layered unstretched membranes, at least one layer must be layer (X). That is, an unstretched membrane can be a single-layered or multi-layered membrane formed solely of layer (X), or it can be a laminate containing layer (X) and a substrate. Specific examples of the substrate will be described later.
[0344] The thickness of the sealing film or unstretched film (in the case of a multilayer film, the total thickness of each layer) is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, preferably 150 μm or less, more preferably 130 μm or less, even more preferably 100 μm or less, for example, 5 to 150 μm.
[0345] Specific uses of sealing films or unstretched films include, for example, packaging films used for packaging food, liquids, pharmaceuticals or electronic components, and packaging materials derived therefrom.
[0346] The aforementioned sealing film or unstretched film can be manufactured, for example, using at least a resin composition (X) and a conventionally known single-layer or multi-layer film forming machine. The manufacturing method of the unstretched film is not particularly limited as long as it does not impair the purpose of this disclosure. Unstretched films include films obtained by co-extrusion using known multi-layer film forming methods such as T-die film forming and blown film forming, and films obtained by further laminating layers (X) on a pre-formed substrate. For example, the unstretched film can be a film obtained by a manufacturing method including the following steps: laminating a single-layer or multi-layer film (e.g., a single-layer or multi-layer film formed only of layer (X)) to a substrate using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination.
[0347] <Layered Body> As an example of the above-mentioned molded body, a laminated body can be cited.
[0348] The aforementioned laminate has a substrate and a layer (layer (X)) formed from a resin composition (X). In this case, the resin composition (X) is preferably a resin composition (X) containing an propylene polymer (α1), or a resin composition (X) containing an olefin resin (β), an propylene polymer (α1), and an ethylene polymer (α2).
[0349] In one embodiment, the laminate includes a substrate and a sealing film. For example, in the laminate, the substrate and the sealing film are laminated together.
[0350] Examples of substrates include resin films, metal foils, paper, and vapor-deposited films. Examples of resins constituting the resin film include thermoplastic resins, specifically polyolefin resins (e.g., polyethylene, polypropylene), polystyrene resins, polyester resins (e.g., polyethylene terephthalate (PET)), polyamide resins, polyimide resins, polycarbonate resins, polyarylate resins, acrylic resins, polyphenylene sulfide resins, ethylene resins, vinyl chloride resins, and epoxy resins. The resin film can be a single layer or a multilayer of two or more layers. The resin film can be a stretched film or an unstretched film. Examples of metal foils include aluminum foil, steel foil, and stainless steel foil, with aluminum foil being preferred.
[0351] The preferred substrate is at least one selected from the group consisting of polyolefin film, polystyrene film, polyester film, polyamide film, laminated film of polyolefin film and gas barrier resin film, metal foil such as aluminum foil, paper, and vapor-deposited film.
[0352] The aforementioned laminate can be manufactured, for example, using conventionally known single-layer or multi-layer film forming machines. The aforementioned laminate can be manufactured, for example, by a manufacturing method including the following steps: laminating a substrate to the aforementioned sealing film using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination. The aforementioned laminate can be manufactured, for example, by a manufacturing method including the following steps: laminating a substrate to a single-layer or multi-layer film formed solely of layer (X) using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination.
[0353] The laminate itself can also be used as a sealing film. In this case, the substrate is preferably a resin film, and more preferably an unstretched film. That is, the sealing film can be a single-layer or multi-layer film formed only by layer (X), or it can be a laminate having layer (X) and substrate.
[0354] The aforementioned sealing film and the aforementioned laminate exhibit excellent resistance to whitening during stretching, as well as good heat resistance and tensile strength. Therefore, the characteristics of the sealing film can be utilized to make it suitable for use as packaging for all kinds of items, such as daily necessities, food (food packaging materials), liquids, pharmaceuticals, electronic components, and building materials.
[0355] The aforementioned sealing film or laminate can be incorporated into energy storage devices such as lithium-ion batteries and lithium-ion capacitors. The aforementioned sealing film or laminate can be suitably used, for example, as a packaging for lithium-ion batteries. Alternatively, this disclosure can also be described as providing an energy storage device comprising a resin composition (X). Examples of such energy storage devices include, for instance, an energy storage device comprising the aforementioned sealing film or laminate; a specific example is a packaging for a lithium-ion battery comprising the aforementioned sealing film or laminate.
[0356] Lithium-ion batteries The aforementioned sealing film or the aforementioned laminate can be suitably used as a packaging for lithium-ion batteries.
[0357] Lithium-ion batteries typically contain a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and a non-aqueous electrolyte. The positive electrode typically includes a positive current collector formed of a metallic or carbon material, and a positive electrode active material, such as a composite oxide formed of lithium and a transition metal, capable of absorbing and releasing lithium ions. The negative electrode typically includes a negative current collector formed of a carbon material, and a negative electrode active material, such as metallic lithium, lithium-containing alloys, or metals or alloys capable of alloying with lithium, capable of absorbing and releasing lithium ions. The non-aqueous electrolyte includes a lithium salt as the electrolyte and a non-aqueous solvent. In lithium-ion batteries, the positive electrode, negative electrode, and separator are impregnated with a non-aqueous electrolyte. Details regarding the non-aqueous solvent will be described later in the section on <Non-Aqueous Solvents>.
[0358] In most cases, lithium-ion batteries have a packaging body (lithium-ion battery packaging body) at their periphery. Inside this packaging body are sealed a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. Typically, a positive terminal and a negative terminal are connected to the positive and negative electrodes, respectively. A portion of the positive terminal and a portion of the negative terminal protrude outside the packaging body.
[0359] The following describes the use of the aforementioned sealing film or laminate as the packaging body. A lithium-ion battery is obtained by thermally fusing the positive and negative electrodes, etc., with a portion of the positive and negative terminals exposed to the outside of the pair of sealing films or the pair of laminates, at the periphery of these films or laminates. When using the aforementioned laminate as the packaging body, the laminate may also have a substrate made of a metal such as aluminum foil.
[0360] Lithium-ion batteries using lithium-ion battery packaging can be used in, for example, portable electronic devices, personal computers, robots, drones, automobiles, aircraft, wearable devices, and energy storage systems (ESS) for home or renewable energy generation.
[0361] <Non-aqueous solvent> Non-aqueous electrolytes used in lithium-ion batteries typically contain non-aqueous solvents.
[0362] Various known non-aqueous solvents can be suitably selected as non-aqueous solvents. Preferably, at least one solvent selected from the group consisting of cyclic aprotic solvents and chain-like aprotic solvents is used. When it is desirable to intentionally increase the flash point of the solvent to improve battery safety, a cyclic aprotic solvent is preferred as the non-aqueous solvent.
[0363] (Cyclic aprotic solvent) Examples of cyclic aprotic solvents include, for example, cyclic carbonates, cyclic carboxylic esters, cyclic sulfones, and cyclic ethers.
[0364] One type of cyclic aprotic solvent can be used, or two or more types can be used in combination.
[0365] The proportion of the cyclic aprotic solvent in the non-aqueous solvent is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass. By setting such a proportion, the conductivity of the electrolyte, for example, which is related to the charge-discharge characteristics of the battery, can be improved.
[0366] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, 1,2-butanediol carbonate, 2,3-butanediol carbonate, 1,2-pentanediol carbonate, and 2,3-pentanediol carbonate. Among these, ethylene carbonate and propylene carbonate, which have high dielectric constants, are preferred. In batteries where graphite is used as the negative electrode active material, ethylene carbonate is more preferred. Two or more cyclic carbonates may also be used in combination.
[0367] Examples of cyclic carboxylic acid esters include, for example, γ-butyrolactone, δ-valerolactone, or alkyl-substituted derivatives such as methyl-γ-butyrolactone, ethyl-γ-butyrolactone, and ethyl-δ-valerolactone.
[0368] Cyclic carboxylic esters have low vapor pressure, low viscosity, and high dielectric constant, which can reduce the viscosity of the electrolyte without lowering its flash point or degree of dissociation. Therefore, cyclic carboxylic esters have the characteristic of improving electrolyte conductivity, an indicator related to the charge-discharge characteristics of the battery, without increasing the flammability of the electrolyte. Thus, when there is an intention to increase the flash point of the solvent, cyclic carboxylic esters are preferred as cyclic aprotic solvents. γ-Butyrolactone is the most preferred.
[0369] Cyclic carboxylic esters are preferably used in combination with other cyclic aprotic solvents and / or chain aprotic solvents. Examples include cyclic carboxylic esters and mixtures (combinations) with cyclic carbonates and / or chain carbonates.
[0370] Examples of combinations of cyclic carboxylic acid esters and cyclic carbonates and / or chain carbonates include: γ-butyrolactone with ethylene carbonate; γ-butyrolactone with ethylene carbonate and dimethyl carbonate; γ-butyrolactone with ethylene carbonate and methyl ethyl carbonate; γ-butyrolactone with ethylene carbonate and diethyl carbonate; γ-butyrolactone with propylene carbonate; γ-butyrolactone with propylene carbonate and dimethyl carbonate; γ-butyrolactone with propylene carbonate... methyl ethyl carbonate; γ-butyrolactone with propylene carbonate and diethyl carbonate; γ-butyrolactone with ethylene carbonate and propylene carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and dimethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and methyl ethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and diethyl carbonate; γ-butyrolactone with ethylene carbonate, dimethyl carbonate, and methyl ethyl carbonate; γ-butyrolactone γ-Butyrolactone with ethylene carbonate, dimethyl carbonate, and diethyl carbonate; γ-Butyrolactone with ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-Butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, and methyl ethyl carbonate; γ-Butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate; γ-Butyrolactone It is associated with ethylene carbonate, propylene carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-butyrolactone with sulfolane; γ-butyrolactone with ethylene carbonate and sulfolane; γ-butyrolactone with propylene carbonate and sulfolane; γ-butyrolactone with ethylene carbonate, propylene carbonate, and sulfolane; and γ-butyrolactone with sulfolane and dimethyl carbonate.
[0371] Examples of cyclic sulfones include sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, dipropyl sulfone, methyl ethyl sulfone, and methyl propyl sulfone.
[0372] Examples of cyclic ethers include, for instance, dioxane.
[0373] (Chain-like aprotic solvent) Examples of chain-like aprotic solvents include chain carbonates, chain carboxylic esters, chain ethers, and chain phosphates.
[0374] A chain-like aprotic solvent can be used in one form or in combination of two or more.
[0375] The proportion of the chain-like aprotic solvent in the non-aqueous solvent is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass.
[0376] Examples of chain carbonates include, for example, dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, ethyl propyl carbonate, dipropyl carbonate, methyl butyl carbonate, ethyl butyl carbonate, dibutyl carbonate, methyl pentyl carbonate, ethyl pentyl carbonate, dipentyl carbonate, methyl heptacarbonate, ethyl heptacarbonate, diheptyl carbonate, methyl hexyl carbonate, ethyl hexyl carbonate, dihexyl carbonate, methyl octyl carbonate, ethyl octyl carbonate, dioctyl carbonate, and methyl trifluoroethyl carbonate. Two or more chain carbonates may also be used in combination.
[0377] Examples of chain-like carboxylic acid esters include, for instance, methyl tervaline.
[0378] Examples of chain ethers include, for instance, dimethoxyethane.
[0379] Examples of chain phosphate esters include, for instance, trimethyl phosphate.
[0380] (Combination of solvents) The non-aqueous electrolyte may contain only one type of non-aqueous solvent or two or more types.
[0381] One or more cyclic aprotic solvents, one or more chain-like aprotic solvents, or a mixture of cyclic aprotic solvents and chain-like protic solvents can be used. When there is a particular intention to improve the battery's load characteristics and low-temperature characteristics, it is preferable to use a combination of cyclic aprotic solvents and chain-like aprotic solvents as non-aqueous solvents.
[0382] Considering the electrochemical stability of the electrolyte, cyclic carbonates are the preferred choice as cyclic aprotic solvents, while linear carbonates are preferred as linear aprotic solvents. Combinations of cyclic carboxylic esters with cyclic carbonates and / or linear carbonates can also be used to improve the electrolyte conductivity, which is related to the charge-discharge characteristics of the battery.
[0383] Examples of combinations of cyclic and chain carbonates include: ethylene carbonate and dimethyl carbonate; ethylene carbonate and methyl ethyl carbonate; ethylene carbonate and diethyl carbonate; propylene carbonate and dimethyl carbonate; propylene carbonate and methyl ethyl carbonate; propylene carbonate and diethyl carbonate; ethylene carbonate, propylene carbonate and methyl ethyl carbonate; ethylene carbonate, propylene carbonate and diethyl carbonate; ethylene carbonate and dimethyl carbonate, methyl ethyl carbonate; ethylene carbonate and... Dimethyl carbonate, diethyl carbonate; ethylene carbonate and methyl ethyl carbonate, diethyl carbonate; ethylene carbonate and dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, methyl ethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and methyl ethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate.
[0384] The mixing ratio of cyclic carbonates to chain carbonates (cyclic carbonate: chain carbonate), expressed as a mass ratio, is preferably 5:95 to 80:20, more preferably 10:90 to 70:30. By setting such a mixing ratio, the increase in electrolyte viscosity can be suppressed and the degree of electrolyte dissociation can be improved. Therefore, the conductivity of the electrolyte, which is related to the charge-discharge characteristics of the battery, can be improved, and the solubility of the electrolyte can be further improved. Thus, an electrolyte with excellent conductivity at room temperature or low temperature can be produced, thereby improving the battery load characteristics at room temperature to low temperature.
[0385] Lithium-ion batteries contain a non-aqueous electrolyte containing the aforementioned non-aqueous solvent. Therefore, the packaging material constituting the lithium-ion battery (a packaging material for lithium-ion batteries) preferably does not readily leach into the aforementioned non-aqueous solvent, nor does it readily swell due to the aforementioned non-aqueous solvent, and preferably maintains a certain mechanical strength even when exposed to contact with the aforementioned non-aqueous solvent. The aforementioned sealing film and the aforementioned laminate having a layer (layer (X)) formed of resin composition (X) exhibit excellent resistance to whitening and are not prone to, for example, leaching into the aforementioned non-aqueous solvent, nor swelling due to the aforementioned non-aqueous solvent, and maintain a certain mechanical strength even when exposed to contact with the aforementioned non-aqueous solvent. Therefore, the aforementioned sealing film and the aforementioned laminate can be suitably used as a packaging material for lithium-ion batteries.
[0386] Example The present invention will now be described in more detail based on embodiments, but the present invention is not limited to these embodiments, as long as they do not depart from its spirit.
[0387] <Measurement and Evaluation Methods> In the following examples and comparative examples, each physical property was measured or evaluated using the following methods.
[0388] [Weight-average molecular weight (Mw)] The weight-average molecular weight (Mw) of the polymer samples was determined using gel permeation chromatography (Tosoh HLC-8321 GPC / HT type) with two Tosoh TSKgel GMH6-HT and two Tosoh GMH6-HTL columns (each with an inner diameter of 7.5 mm and a length of 300 mm) connected in tandem. The mobile phase was prepared by adding 0.025% by mass of BHT (FUJIFILM Wako Pure Chemical Corporation) as an antioxidant to o-dichlorobenzene, and the determination was performed at a sample concentration of 0.15% (w / v), a flow rate of 1.0 ml / min, and 140°C. Standard polystyrene with a molecular weight of 590–20,600,000 was prepared using Tosoh products. The obtained chromatograms were analyzed using Waters Empower3 data processing software, employing known methods and a standard curve using standard polystyrene samples, from which the weight-average molecular weight (Mw) was calculated.
[0389] [Melting point (Tm) and heat of fusion (ΔH)] The melting point (Tm) and heat of fusion (ΔH) of the olefin resin (β) described later are determined by DSC under the following conditions.
[0390] Using a differential scanning calorimeter (SII DSC220), approximately 5.0 mg of the sample was heated from 30 °C to 200 °C at a rate of 10 °C / min under a nitrogen atmosphere and held at that temperature for 10 minutes. It was then further cooled to -100 °C at a rate of 10 °C / min, held at that temperature for 5 minutes, and then heated to 200 °C at a rate of 10 °C / min. The endothermic peak observed during this second heating was taken as the melting peak, and the temperature at which the melting peak appeared was determined as the melting point (Tm). Tables 1-1 to 1-3, which are described later, list the temperatures of the two melting points (Tm) when two melting peaks are present. Furthermore, the area of the aforementioned melting peaks was calculated to determine the heat of fusion (ΔH). It should be noted that when the melting peak is multimodal, the area of all melting peaks is calculated to determine the heat of fusion.
[0391] [Glass transition temperature (Tg)] For the glass transition temperature (Tg) of the olefinic resin (β) described later, it is determined by DSC measurement under the same conditions as the melting point (Tm) mentioned above. The glass transition temperature (Tg) can be perceived by the fact that the DSC curve bends and the baseline shifts parallel during the second heating due to the change in specific heat. The temperature at which the tangent of the baseline with a temperature lower than this bend intersects the tangent at the point with the steepest slope in the bend is taken as the glass transition temperature (Tg).
[0392] [Composition of each monomer component] For the backbone of the olefin resin (β) described later, the repeating units derived from the monomers of the copolymers of ethylene and propylene or 1-butene were calculated based on a standard curve relating the composition ratio (mol%) of ethylene to the melting point (Tm) (°C). The standard curve was prepared as follows: In the examples described later, polymerization was performed similarly except that terminally unsaturated polypropylene was not added, and the supply ratio of continuously supplied ethylene to propylene or 1-butene was further varied, thereby obtaining various ethylene-propylene copolymers or ethylene-1-butene copolymers with different propylene or 1-butene composition ratios. For the obtained ethylene-propylene copolymers or ethylene-1-butene copolymers, the composition ratio of propylene or 1-butene was determined by the following nuclear magnetic resonance spectroscopy analysis to prepare a standard curve. For the side chains of the olefin resin (β) described later, the analytical values of the terminally unsaturated propylene polymer and the terminally unsaturated propylene-ethylene copolymer obtained in step (A) of the examples described later were used directly.
[0393] (Nuclear magnetic resonance spectroscopy analysis: measurement conditions) Apparatus: JEOL ECX400P nuclear magnetic resonance spectrometer, used for measuring nuclei: 1 H (400MHz); 13 C (125MHz), Measurement mode: single pulse, pulse width: 45° (5.25μs), number of points: 32k, measurement range: 20ppm (-4~16ppm), repetition time: 7.0 seconds, cumulative number of times: 64, measurement solvent: o-dichlorobenzene-d4, sample concentration: ca.20mg / 0.6mL, measurement temperature: 120℃, window function: exponential (BF: 0.12Hz), chemical shift standard: o-dichlorobenzene (7.1ppm).
[0394] It should be noted that the ratio of ethylene to propylene in the ethylene-propylene copolymer that forms the backbone of the grafted olefin polymer [R1] in the olefin resin (β), or the ratio of ethylene to 1-butene in the ethylene-1-butene copolymer that forms the backbone of the grafted olefin polymer [R1] in the olefin resin (β), is determined using a 125MHz... 13The peak intensities (integrated values) from ethylene and propylene or 1-butene obtained by C-NMR (Nippon Electron ECX400P) were used for determination and quantification.
[0395] [Terminal Vinyl Ratio] The terminal vinyl percentage of terminally unsaturated polypropylene and terminally unsaturated propylene-ethylene copolymers was determined by means of a 400MHz... 1 The intensity ratio of peaks from unsaturated bonds obtained by H-NMR (JEOL ECX400P) is used to quantify the terminal vinyl ratio in terms of the amount of vinyl in the total unsaturated content at the end.
[0396] [The proportion of P (the total content of components (i) to (iv) above) in the olefin-based resin (β)] (Method 1: Calculated from input amount) The proportion of component P from terminal unsaturated polypropylene and terminal unsaturated propylene-ethylene copolymer in the olefin resin (β) described later (the proportion of the total content of component P in (i) to (iv) above) is calculated from the difference between the amount of terminal unsaturated polypropylene or terminal unsaturated propylene-ethylene copolymer added and the amount of olefin resin (β) obtained.
[0397] (Method 2: Calculated by analyzing olefin-based resins (β)) The proportion of component P from terminally unsaturated polypropylene and terminally unsaturated propylene-ethylene copolymer in the olefin resin (β) described later was calculated by analyzing the olefin resin (β). Specifically, the proportion (mass%) of P, which is the total proportion of components from terminally unsaturated polypropylene and terminally unsaturated propylene-ethylene copolymer, was calculated from a standard curve relating the heat of fusion (ΔH) (J / g) based on the melting point (Tm) (°C) to the proportion (mass%) of P calculated from the input amount.
[0398] The method for preparing the standard curve is as follows. First, by varying the loading amounts of terminally unsaturated polypropylene and terminally unsaturated propylene-ethylene copolymer, polymerization was carried out in the same manner as in the examples described later, resulting in various olefin resins with different proportions (mass%) of P. Next, polymerization was carried out similarly for various main-chain ethylene compositions, resulting in various olefin resins with different main-chain ethylene composition proportions and different proportions (mass%) of P. Furthermore, a standard curve was prepared based on the melting point (Tm) and heat of fusion (ΔH) (J / g) of the various olefin resins, and the proportion (mass%) of P calculated from the loading amounts.
[0399] It should be noted that the proportion of P in the olefin resin (β-1) manufactured in Example 1A described later is equivalent to 46.1% by mass in Method 1 (the result calculated from the input amounts) and 46.3% by mass in Method 2 (the result of analysis based on the prepared standard curve). Furthermore, the proportion of P in the olefin resin (β-2) manufactured in Example 2A described later is equivalent to 31.6% by mass in Method 1 (the result calculated from the input amounts) and 31.5% by mass in Method 2.
[0400] The values calculated using method 1 are described in the following examples (see Tables 1-1 to 1-3).
[0401] [Confirmation of the grafted olefin polymer [R1]] Peak separation was performed on the chromatogram obtained by gel permeation chromatography, which confirmed that the terminal unsaturated polypropylene and the terminal unsaturated propylene-ethylene copolymer were consumed, and that a grafted olefin polymer was generated [R1].
[0402] Intrinsic viscosity [η] For the intrinsic viscosity [η] of the olefin resin (β) described later, an Ubbelohde viscometer was used as the measuring device, and the measurement was performed at 135°C in decahydronaphthalene solvent.
[0403] After dissolving approximately 20 mg of the copolymer in 25 mL of decahydronaphthalene, the specific viscosity ηsp was measured using an Ubbelohde viscometer in an oil bath at 135 °C. The solution was then diluted by adding 5 mL of decahydronaphthalene, and the specific viscosity ηsp was measured in the same manner. This dilution was repeated twice more, and the value of ηsp / C, extrapolated to 0 from the concentration (C), was determined as the intrinsic viscosity [η] (unit: dl / g) (see the formula below).
[0404] [η]=lim (ηsp / C) (C→0) Melt Flow Rate (MFR) For the melt flow rate (MFR) of the olefin resins (β) described later, it was determined according to ASTM D1238E under conditions of 190°C and 2.16 kg load.
[0405] [density] Using the wire harness resin that flowed out in the above-mentioned melt flow rate (MFR) determination, the density was determined at 23°C using the density gradient tube method according to JIS K7112.
[0406] <Reagents> [Reagents] Toluene was purified using an organic solvent purification system manufactured by GlassContour. For xylene, a first-grade product manufactured by Pure Chemicals was used after passing it through a 500 mL alumina column.
[0407] For the alumina column, alumina obtained by drying E. Merck's activated alumina 90 (neutral, activity level I) at 150°C for more than 4 hours was used. For the toluene solution of aluminoxane, a 20% by mass methylaluminoxane / toluene solution manufactured by Nippon Aluminum Alkyls, Ltd. was diluted with toluene (1.0 M) before use.
[0408] For triisobutylaluminum, dilute the triisobutylaluminum manufactured by Tosoh Finechem Corporation with toluene (1.0M) before use. For triphenylcarbium tetra(pentafluorophenyl)borate, dissolve the triphenylcarbium tetra(pentafluorophenyl)borate manufactured by Asahi Glass Co., Ltd. in toluene to a concentration of 4.0 mmol / L before use.
[0409] The bridged metallocene compound represented by the following formula (B-1) used as a polymerization catalyst for compound [A] and as a polymerization catalyst for compound [B] is synthesized according to known methods.
[0410] [Chemical Formula 16] [Example 1A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) 1.5 L of toluene was added to a 2 L glass reactor that had undergone nitrogen replacement, and the temperature was raised to 87 °C. Propylene was continuously fed into the reactor at a rate of 240.0 L / hr while stirring at 600 rpm until both liquid and gas phases were saturated. While continuing the continuous propylene feed, 7.5 mL (7.5 mmol) of a toluene solution of methylaluminoxane (also referred to as MAO) (1.0 mol / L) was added, followed by 4.0 mL (0.012 mmol) of a toluene solution of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride (0.0030 mol / L). Polymerization was carried out at 87 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and then dried under reduced pressure at 80°C for 10 hours to obtain 108.3 g of propylene polymer (terminated unsaturated polypropylene (M-1)). For the obtained terminal unsaturated polypropylene (M-1), based on polypropylene conversion, Mw = 22,907, Mw / Mn = 1.88. 1 The single-terminal vinyl content, as determined by H-NMR, was 72%.
[0411] Process (B): Manufacturing of olefin-based resin (β-1) 10.0 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone complete nitrogen replacement. The reactor was then heated to 100 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene and propylene were continuously supplied to the reactor at 99.0 L / hr and 15.6 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under continuous ethylene and propylene supply, 3.0 mL (3.0 mmol) of a toluene solution (1.0 mol / L) of triisobutylaluminum (also known as iBu3Al) and 1.5 mL (0.0030 mmol) of a toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) were added, followed by 3.75 mL (0.015 mmol) of a toluene solution (4.0 mmol / L) of triphenylcarbazium tetra(pentafluorophenyl)borate (also known as Ph3CB(C6F5)4). Polymerization was carried out at 100 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization reaction solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 21.7 g of olefin resin (β-1). Gel permeation chromatography confirmed the consumption of terminally unsaturated polypropylene and the formation of a grafted olefin polymer [R1-1]. The analytical results of the olefin resin (β-1) are shown in Table 1-1.
[0412] [Example 2A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 7.0 g, the toluene solution (0.0020 mol / L) of the bridged metallocene compound (B-1) was changed to 2.5 mL (0.0050 mmol), and the amount of the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 6.25 mL (0.025 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 22.2 g of olefin resin (β-2). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-2] was formed. The analytical results of the obtained olefin resin (β-2) are shown in Table 1-1.
[0413] [Example 3A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 9.5 g, and the propylene supply rate was changed to 7.2 L / hr. Otherwise, the same operation as in Example 1A was performed to obtain 21.4 g of olefin resin (β-3). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-3] was formed. The analytical results of the obtained olefin resin (β-3) are shown in Table 1-1.
[0414] [Example 4A] In step (B) of Example 2A, the propylene supply was changed to 7.2 liters / hr, and the same operation as in Example 2A was performed to obtain 22.6 g of olefin resin (β-4). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-4] was formed. The analytical results of the obtained olefin resin (β-4) are shown in Table 1-1.
[0415] [Example 5A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 8.0 g, the propylene supply was changed to 24.0 L / hr, the toluene solution of triisobutylaluminum (1.0 mol / L) was changed to 2.3 mL (2.3 mmol), the toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L) was changed to 1.0 mL (0.0020 mmol), and the toluene solution of triphenylcarbazide tetra(pentafluorophenyl)borate (4.0 mmol / L) was changed to 2.5 mL (0.010 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 17.1 g of olefin resin (β-5). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-5] was formed. The analytical results of the obtained olefin resin (β-5) are shown in Table 1-1.
[0416] [Example 6A] In step (B) of Example 5A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 6.0 g, the toluene solution (0.0020 mol / L) of the bridged metallocene compound (B-1) was changed to 2.0 mL (0.0040 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Example 5A were performed to obtain 20.9 g of olefin resin (β-6). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-6] was formed. The analytical results of the obtained olefin resin (β-6) are shown in Table 1-1.
[0417] [Example 7A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 7.0 g, the ethylene supply rate was changed to 90.0 L / hr, the propylene supply rate was changed to 30.0 L / hr, the toluene solution of triisobutylaluminum (1.0 mol / L) was changed to 2.0 mL (2.0 mmol), the toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L) was changed to 2.0 mL (0.0040 mmol), and the toluene solution of triphenylcarbazium tetra(pentafluorophenyl)borate (4.0 mmol / L) was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 11.6 g of olefin resin (β-7). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-7] was formed. The analytical results of the obtained olefin resin (β-7) are shown in Table 1-1.
[0418] [Example 8A] In step (B) of Example 7A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 4.5 g, the toluene solution (0.0020 mol / L) of the bridged metallocene compound (B-1) was changed to 3.0 mL (0.0060 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 7.5 mL (0.030 mmol). Otherwise, the same procedures as in Example 7A were performed to obtain 14.4 g of olefin resin (β-8). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-8] was formed. The analytical results of the obtained olefin resin (β-8) are shown in Table 1-1.
[0419] [Example 9A] In step (B) of Example 1A, the ethylene supply was changed to 120.0 L / hr, the propylene supply was changed to 18.0 L / hr, the triisobutylaluminum toluene solution (1.0 mol / L) was changed to 2.5 mL (2.5 mmol), and the polymerization temperature was changed to 96 °C. Otherwise, the same procedures as in Example 1A were performed to obtain 23.1 g of olefin resin (β-9). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-9] was formed. The analytical results of the obtained olefin resin (β-9) are shown in Table 1-1.
[0420] [Example 10A] In step (B) of Example 9A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 9.0 g, the propylene supply rate was changed to 7.2 L / hr, the toluene solution of triisobutylaluminum (1.0 mol / L) was changed to 3.0 mL (3.0 mmol), the toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L) was changed to 1.0 mL (0.0020 mmol), and the toluene solution of triphenylcarbazide tetra(pentafluorophenyl)borate (4.0 mmol / L) was changed to 2.5 mL (0.010 mmol). Otherwise, the same procedures as in Example 9A were performed to obtain 20.1 g of olefin resin (β-10). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-10] was formed. The analytical results of the obtained olefin resin (β-10) are shown in Table 1-1.
[0421] [Example 11A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0422] Process (B): Manufacturing of olefin-based resin (β-11) 7.5 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone complete nitrogen replacement. The temperature was then raised to 103 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene, propylene, and hydrogen were continuously supplied to the reactor at 120.0 L / hr, 19.2 L / hr, and 6.0 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under a continuous supply of ethylene, propylene, and hydrogen, 3.0 mL (3.0 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L), 2.5 mL (0.0050 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L), and then 6.25 mL (0.025 mmol) of a toluene solution of triphenylcarbazium tetra(pentafluorophenyl)borate (4.0 mmol / L) were added. Polymerization was carried out at 103 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 15.1 g of olefin resin (β-11). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-11] was formed. The analytical results of the olefin-based resin (β-11) are shown in Table 1-1.
[0423] [Example 12A] In step (B) of Example 2A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 3.0 g, and the same operation as in Example 2A was performed to obtain 18.2 g of olefin resin (β-12). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-12] was formed. The analytical results of the obtained olefin resin (β-12) are shown in Table 1-1.
[0424] [Example 13A] In step (B) of Example 12A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 14.0 g, the toluene solution (0.0010 mol / L) of the bridged metallocene compound (B-1) was changed to 2.0 mL (0.0020 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 2.5 mL (0.010 mmol). Otherwise, the same procedures as in Example 12A were performed to obtain 19.9 g of olefin resin (β-13). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-13] was formed. The analytical results of the obtained olefin resin (β-13) are shown in Table 1-1.
[0425] [Example 14A] Process (A): Manufacturing of end-unsaturated polypropylene (M-2) 1.5 L of toluene was added to a 2 L glass reactor that had undergone nitrogen replacement, and the temperature was raised to 100 °C. Propylene was continuously fed into the reactor at a rate of 180.0 L / hr while stirring at 600 rpm to saturate both the liquid and gas phases. While continuing the continuous propylene feed, 8.0 mL (8.0 mmol) of a toluene solution of methylaluminoxane (also referred to as MAO) (1.0 mol / L) was added, followed by 8.0 mL (0.032 mmol) of a toluene solution of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconia (0.0040 mol / L). Polymerization was carried out at 100 °C for 15 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and then dried under reduced pressure at 80°C for 10 hours to obtain 88.4 g of propylene polymer (terminated unsaturated polypropylene (M-2)). For the obtained terminal unsaturated polypropylene (M-2), based on polypropylene conversion, Mw = 12,297, Mw / Mn = 2.11. 1 The single-terminal vinyl content, as determined by H-NMR, is 80%.
[0426] Process (B): Manufacturing of olefin resin (β-14) 6.5 g of terminally unsaturated polypropylene (M-2) and 500 mL of xylene were added to a 1 L glass reactor that had undergone nitrogen replacement. The temperature was then raised to 100 °C to dissolve the terminally unsaturated polypropylene (M-2). Ethylene and propylene were continuously supplied to the reactor at 99.0 L / hr and 15.6 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under continuous ethylene and propylene supply, 3.0 mL (3.0 mmol) of a toluene solution (1.0 mol / L) of triisobutylaluminum (also known as iBu3Al), 1.5 mL (0.0015 mmol) of a toluene solution (0.0010 mol / L) of the aforementioned bridged metallocene compound (B-1), and then 1.88 mL (0.0752 mmol) of a toluene solution (4.0 mmol / L) of triphenylcarbazium tetra(pentafluorophenyl)borate (also known as Ph3CB(C6F5)4) were added. Polymerization was carried out at 100 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization reaction solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 12.1 g of olefin resin (β-14). Gel permeation chromatography confirmed the consumption of terminally unsaturated polypropylene and the formation of a grafted olefin polymer [R1-14]. The analytical results of the olefin resin (β-14) are shown in Table 1-1.
[0427] [Example 15A] In step (B) of Example 14A, the amount of terminally unsaturated polypropylene (M-2) added was changed to 4.5 g, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 1.0 mL (0.0020 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 2.5 mL (0.010 mmol). Otherwise, the same procedures as in Example 14A were performed to obtain 13.1 g of olefin resin (β-15). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-15] was formed. The analytical results of the obtained olefin resin (β-15) are shown in Table 1-1.
[0428] [Example 16A] Process (A): Manufacturing of end-unsaturated polypropylene (M-3) 2 L of toluene and 4.0 mL (4.0 mmol) of a toluene solution (1.0 mol / L) of methylaluminoxane (MAO) were added to a 4 L stainless steel autoclave that had undergone nitrogen replacement. The autoclave was heated to 90 °C while stirring at 600 rpm, and then sealed after reaching the temperature. The partial pressure of propylene was then increased by 0.30 MPaG. 5.0 mL of toluene and 2.0 mL (0.002 mmol) of a toluene solution (0.0010 mol / L) of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconia dichloride were added to initiate polymerization. While continuously supplying propylene gas and maintaining the pressure, polymerization was carried out at 90 °C for 20 minutes, after which 5 mL of methanol was added to stop the polymerization. The resulting polymerization solution was added to 5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and then dried under reduced pressure at 80°C for 10 hours to obtain 63.8 g of propylene polymer (terminated unsaturated polypropylene (M-3)). For the obtained terminal unsaturated polypropylene (M-3), based on polypropylene conversion, Mw = 49,332, Mw / Mn = 1.99, using... 1 The single-terminal vinyl content, as determined by H-NMR, was 74%.
[0429] Process (B): Manufacturing of olefin resin (β-16) In step (B) of Example 14A, the terminal unsaturated polypropylene was changed from (M-2) to (M-3), and otherwise the same operation as in Example 14A was performed to obtain 12.5 g of olefin resin (β-16). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-16] was formed. The analytical results of the obtained olefin resin (β-16) are shown in Table 1-1.
[0430] [Example 17A] In step (B) of Example 15A, the terminal unsaturated polypropylene was changed from (M-2) to (M-3) 4.0 g, and otherwise the same operation as in Example 15A was performed to obtain 12.1 g of olefin resin (β-17). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-17] was formed. The analytical results of the obtained olefin resin (β-17) are shown in Table 1-1.
[0431] [Example 18A] Process (A): Manufacturing of terminally unsaturated propylene-ethylene copolymer (M-4) 250 mL of toluene was added to a 500 mL glass reactor that had undergone nitrogen replacement, and the temperature was raised to 90 °C. Ethylene and propylene were continuously supplied to the reactor at 15.0 L / hr and 120.0 L / hr, respectively, while stirring at 600 rpm, until the liquid and gas phases were saturated. While continuing the continuous supply of ethylene and propylene, 0.5 mL (0.5 mmol) of a toluene solution of methylaluminoxane (also referred to as MAO) in 1.0 mol / L was added, followed by 1.0 mL (0.001 mmol) of a toluene solution of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconia dichloride in 0.0010 mol / L. Polymerization was carried out at 90 °C for 15 minutes under normal pressure. Polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and then dried under reduced pressure at 80°C for 10 hours to obtain 8.3 g of terminally unsaturated propylene-ethylene copolymer (M-4). For the obtained terminally unsaturated propylene-ethylene copolymer (M-4), based on polypropylene conversion, Mw = 20,735, Mw / Mn = 1.91. 1 The single-terminal vinyl content determined by H-NMR is 69%, and the propylene composition is 88.7 mol based on the standard curve of the correlation between the ethylene composition (mol%) and melting point (Tm) (°C).
[0432] Process (B): Manufacturing of olefin-based resin (β-18) In step (B) of Example 15A, 3.5 g of terminally unsaturated polypropylene (M-2) was changed to terminally unsaturated propylene-ethylene copolymer (M-4). Otherwise, the same procedures as in Example 15A were performed to obtain 11.8 g of olefin resin (β-18). Gel permeation chromatography confirmed the consumption of the terminally unsaturated propylene-ethylene copolymer and confirmed the formation of a grafted olefin polymer [R1-18]. The analytical results of the obtained olefin resin (β-18) are shown in Tables 1-2.
[0433] [Example 19A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 12.5 g, the ethylene supply rate was changed to 102.0 L / hr, the propylene supply rate was changed to 14.4 L / hr, the hydrogen supply rate was changed to 1.44 L / hr, the toluene solution (0.0020 mol / L) of the bridged metallocene compound (B-1) was changed to 4.0 mL (0.0080 mmol), and the toluene solution (4.20 mmol / L) of triphenylcarbamate tetra(pentafluorophenyl)borate was changed to 8.0 mL (0.032 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 25.6 g of olefin resin (β-19). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-19] was formed. The analytical results of the obtained olefin resin (β-19) are shown in Tables 1-2.
[0434] [Example 20A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 8.5 g, the propylene supply was changed to 19.2 L / hr, the toluene solution of triisobutylaluminum (1.0 mol / L) was changed to 3.5 mL (3.5 mmol), and the toluene solution of triphenylcarbazide tetra(pentafluorophenyl)borate (4.0 mmol / L) was changed to 3.0 mL (0.012 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 16.6 g of olefin resin (β-20). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-20] was formed. The analytical results of the obtained olefin resin (β-20) are shown in Tables 1-2.
[0435] [Example 21A] In step (B) of Example 20A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 7.0 g, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 2.5 mL (0.0050 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Example 20A were performed to obtain 20.5 g of olefin resin (β-21). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-21] was formed. The analytical results of the obtained olefin resin (β-21) are shown in Tables 1-2.
[0436] [Example 22A] In step (B) of Example 1A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 12.5 g, the propylene supply was changed to 26.4 L / hr, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 2.5 mL (0.0050 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Example 1A were performed to obtain 22.2 g of olefin resin (β-22). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-22] was formed. The analytical results of the obtained olefin resin (β-22) are shown in Tables 1-2.
[0437] [Example 23A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0438] Process (B): Manufacturing of olefin-based resin (β-23) 13.0 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone nitrogen replacement. The temperature was then raised to 100 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene, 1-butene, and hydrogen were continuously supplied to the reactor at 99.0 L / hr, 10.8 L / hr, and 1.44 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under a continuous supply of ethylene, 1-butene, and hydrogen, 3.1 mL (3.1 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L), 3.5 mL (0.0070 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L), and then 7.0 mL (0.028 mmol) of a toluene solution of triphenylcarbazium tetra(pentafluorophenyl)borate (4.0 mmol / L) were added. Polymerization was carried out at 100 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 28.3 g of olefin resin (β-23). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-23] was formed. The analytical results of the olefin-based resin (β-23) are shown in Tables 1-3.
[0439] [Example 24A] In step (B) of Example 23A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 5.5 g, and the same operation as in Example 23A was performed to obtain 19.7 g of olefin resin (β-24). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-24] was formed. The analytical results of the obtained olefin resin (β-24) are shown in Tables 1-3.
[0440] [Example 25A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0441] Process (B): Manufacturing of olefin-based resin (β-25) 12.0 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone nitrogen replacement. The temperature was then raised to 103 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene and 1-butene were continuously supplied to the reactor at 99.0 L / hr and 18.0 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under continuous supply of ethylene and 1-butene, 3.5 mL (3.5 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L), 2.5 mL (0.0050 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L), and then 5.0 mL (0.020 mmol) of a toluene solution of triphenylcarbazium tetra(pentafluorophenyl)borate (4.0 mmol / L) were added. Polymerization was carried out at 103 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 24.5 g of olefin resin (β-25). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that the grafted olefin polymer [R1-25] was formed. The analytical results of the olefin-based resin (β-25) are shown in Tables 1-3.
[0442] [Example 26A] In step (B) of Example 25A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 6.0 g, and the same operation as in Example 25A was performed to obtain 19.5 g of olefin resin (β-26). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-26] was formed. The analytical results of the obtained olefin resin (β-26) are shown in Tables 1-3.
[0443] [Example 27A] In step (B) of Example 23A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 14.0 g, the supply of 1-butene was changed to 22.8 L / hr, the supply of hydrogen was changed to 0.60 L / hr, the toluene solution of triisobutylaluminum (1.0 mol / L) was changed to 2.5 mL (2.5 mmol), the toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L) was changed to 2.5 mL (0.0050 mmol), and the toluene solution of triphenylcarbazide tetra(pentafluorophenyl)borate (4.0 mmol / L) was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Example 23A were performed to obtain 26.9 g of olefinic resin (β-27). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefinic polymer [R1-27] was formed. The analytical results of the obtained olefin resin (β-27) are shown in Tables 1-3.
[0444] [Comparative Example 1A] In step (B) of Example 1A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 1A was performed to obtain 14.2 g of olefin resin (β'-1). The analytical results of the obtained olefin resin (β'-1) are shown in Tables 1-2.
[0445] [Comparative Example 2A] The procedure (A) of Example 1A was performed in the same manner to obtain 108.3 g of olefin resin (β'-2). The analytical results of the obtained olefin resin (β'-2) are shown in Tables 1-2.
[0446] [Comparative Example 3A] In step (B) of Example 19A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 19A was performed to obtain 12.8 g of olefin resin (β'-9). The analytical results of the obtained olefin resin (β'-9) are shown in Tables 1-2.
[0447] [Comparative Example 4A] In step (B) of Example 21A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 21A was performed to obtain 16.7 g of olefin resin (β'-10). The analytical results of the obtained olefin resin (β'-10) are shown in Tables 1-2.
[0448] [Comparative Example 5A] In step (B) of Example 22A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 22A was performed to obtain 17.4 g of olefin resin (β'-11). The analytical results of the obtained olefin resin (β'-11) are shown in Tables 1-2.
[0449] [Comparative Example 6A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0450] Process (B): Manufacturing of olefin-based resins (β'-3) 6.5 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone nitrogen replacement. The temperature was then raised to 100 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene and hydrogen were continuously supplied to the reactor at 99.0 L / hr and 4.1 L / hr, respectively, while stirring at 600 rpm, to saturate the liquid and gas phases. While continuing the continuous supply of ethylene and hydrogen, 2.0 mL (2.0 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L), 2.0 mL (0.0040 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L), and then 4.0 mL (0.016 mmol) of a toluene solution of triphenylcarbamate tetra(pentafluorophenyl)borate (4.0 mmol / L) were added. Polymerization was carried out at 100 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid, causing the polymer to precipitate. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 14.0 g of olefin resin (β'-3). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer was formed [R1-28]. The analytical results of the olefin resin (β'-3) are shown in Tables 1-2.
[0451] [Comparative Example 7A] In step (B) of Comparative Example 6A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 4.0 g, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 2.5 mL (0.0050 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 5.0 mL (0.020 mmol). Otherwise, the same procedures as in Comparative Example 6A were performed to obtain 12.4 g of olefin resin (β'-4). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer was formed [R1-29]. The analytical results of the obtained olefin resin (β'-4) are shown in Tables 1-2.
[0452] [Example 28A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0453] Process (B): Manufacturing of olefin-based resin (β'-5) 6.0 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone nitrogen replacement. The temperature was then raised to 96 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene and propylene were continuously supplied to the reactor at 81.0 L / hr and 42.0 L / hr, respectively, while stirring at 600 rpm, to saturate the liquid and gas phases. While continuing the continuous supply of ethylene and propylene, 2.0 mL (2.0 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L), 1.0 mL (0.0020 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L), and then 2.0 mL (0.008 mmol) of a toluene solution of triphenylcarbamate tetra(pentafluorophenyl)borate (4.0 mmol / L) were added. Polymerization was carried out at 96 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid, causing the polymer to precipitate. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 12.5 g of olefin resin (β'-5). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer was formed [R1-30]. The analytical results of the olefin resin (β'-5) are shown in Tables 1-2.
[0454] [Example 29A] In step (B) of Example 28A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 4.0 g, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 1.5 mL (0.0030 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 3.0 mL (0.012 mmol). Otherwise, the same procedures as in Example 29A were performed to obtain 11.7 g of olefin resin (β'-6). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer [R1-31] was formed. The analytical results of the obtained olefin resin (β'-6) are shown in Tables 1-2.
[0455] [Comparative Example 8A] Process (A): Manufacturing of end-unsaturated polypropylene (M-1) Perform the same operation as in step (A) of Example 1A to synthesize terminally unsaturated polypropylene (M-1).
[0456] Process (B): Manufacturing of olefin-based resin (β'-7) 5.0 g of terminally unsaturated polypropylene (M-1) and 500 mL of xylene were added to a 1 L glass reactor that had undergone complete nitrogen replacement. The temperature was then raised to 105 °C to dissolve the terminally unsaturated polypropylene (M-1). Ethylene, propylene, and hydrogen were continuously supplied to the reactor at 120.0 L / hr, 20.4 L / hr, and 18.0 L / hr, respectively, while stirring the reactor at 600 rpm, to saturate the liquid and gas phases. Under a continuous supply of ethylene, propylene, and hydrogen, 3.5 mL (3.5 mmol) of a toluene solution of triisobutylaluminum (1.0 mol / L) and 3.5 mL (0.0070 mmol) of a toluene solution of the aforementioned bridged metallocene compound (B-1) (0.0020 mol / L) were added, followed by 7.0 mL (0.028 mmol) of a toluene solution of triphenylcarbazium tetra(pentafluorophenyl)borate (4.0 mmol / L). Polymerization was carried out at 105 °C for 30 minutes under normal pressure. The polymerization was stopped by adding a small amount of isobutanol. The resulting polymerization solution was added to 1.5 L of methanol containing a small amount of hydrochloric acid to precipitate the polymer. The precipitate was washed with methanol and dried under reduced pressure at 130 °C for 10 hours to obtain 10.0 g of olefin resin (β'-7). Gel permeation chromatography confirmed that the terminal unsaturated polypropylene was consumed and that a grafted olefin polymer was formed [R1-32]. The analytical results of the olefin-based resin (β'-7) are shown in Table 1-2.
[0457] [Comparative Example 9A] In step (B) of Comparative Example 8A, the amount of terminally unsaturated polypropylene (M-1) added was changed to 3.0 g, the toluene solution (0.0020 mol / L) of the aforementioned bridged metallocene compound (B-1) was changed to 5.0 mL (0.010 mmol), and the toluene solution (4.0 mmol / L) of triphenylcarbazide tetra(pentafluorophenyl)borate was changed to 10.0 mL (0.040 mmol). Otherwise, the same procedures as in Comparative Example 8A were performed to obtain 9.0 g of olefin resin (β'-8). Gel permeation chromatography confirmed that the terminally unsaturated polypropylene was consumed and that a grafted olefin polymer was formed [R1-33]. The analytical results of the obtained olefin resin (β'-8) are shown in Tables 1-2.
[0458] [Comparative Example 10A] In step (B) of Example 23A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 23A was performed to obtain 21.7 g of olefin resin (β'-12). The analytical results of the obtained olefin resin (β'-12) are shown in Tables 1-3.
[0459] [Comparative Example 11A] In step (B) of Example 25A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 25A was performed to obtain 13.5 g of olefin resin (β'-13). The analytical results of the obtained olefin resin (β'-13) are shown in Tables 1-3.
[0460] [Comparative Example 12A] In step (B) of Example 27A, without the addition of terminal unsaturated polypropylene (M-1), the same operation as in Example 27A was performed to obtain 14.5 g of olefin resin (β'-14). The analytical results of the obtained olefin resin (β'-14) are shown in Tables 1-3.
[0461] [Table 1-1] [Table 1-2] [Table 1-3] [Examples 1B-20B, Examples 1C-18C, Reference Examples 1B and 1C, Comparative Examples 1B-7B and 1C-3C] Preparation of resin composition (X) A resin composition was prepared by loading the raw materials listed in Tables 2-1, 2-2, 3-1, and 3-2 into a Labo Plastomill manufactured by Toyo Seiki Co., Ltd., according to the proportions (parts by mass) listed in Tables 2-1, 2-2, 3-1, and 3-2, and then melting and mixing the mixture at 200°C and 60 rpm for about 5 minutes.
[0462] The following substances are used as raw materials for propylene-based polymers (α1) and ethylene-based polymers (α2).
[0463] [Propylene polymers (α1-1)] Homopolymer polypropylene (manufactured by Prime Polymer Co., Ltd., trade name: Prime Polypro F113G, MFR (230℃, 2.16kg load) = 3.0g / 10min) [Vinyl polymers (α2-1)] Metallocene linear low-density polyethylene (manufactured by Prime Polymer Co., Ltd., trade name: Evolue SP2540, MFR (190℃, 2.16kg load) = 3.8g / 10min). The properties of the obtained resin compositions were determined or evaluated using the following test methods. The results are shown in Tables 2-1, 2-2, 3-1, or 3-2.
[0464] [Tension Test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 2 mm.
[0465] After 72 hours from the time of molding at room temperature, the sheet produced is subjected to a tensile test under the following conditions according to JIS K7162. The tensile elongation is determined from this test.
[0466] <Measurement Conditions> Test piece: JIS K7162-5A dumbbell 5mm (width) × 2mm (thickness) × 75mm (length) Stretching speed: 50mm / minute Spacing between fixtures: 50mm Distance between markings: 20mm Temperature: 23℃ [Observation using a transmission electron microscope] The prepared resin composition was heated for 6 minutes using a hydraulic hot press set to 200°C, followed by molding at 10 MPa for 2 minutes. Then, it was cooled at 20°C and 10 MPa for 2 minutes to produce a sheet with a thickness of 3 mm.
[0467] The obtained molded body was made into small pieces of 0.5 mm square and stained with ruthenium acid (RuO4). The pieces were then further processed into ultrathin sections of approximately 100 nm thickness using an ultramicrotome equipped with a diamond blade. Carbon was deposited onto these ultrathin sections, and the phase structure was observed using a transmission electron microscope (H-7650, Hitachi High-Tech Corporation).
[0468] [Edwards impact strength] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 3 mm.
[0469] The Izod impact strength of the produced sheet was determined by testing under the conditions described below according to ASTM D256 after 72 hours at room temperature from the time of molding. Additionally, the failure modes after testing at 23°C or -30°C were visually confirmed.
[0470] <Experimental Conditions> Hammering capacity: 3.92J Swing angle: 149.0 degrees The gap is for machining. Temperature: 23℃ or -30℃ [Rate of change in impact resistance] The rate of change of the Ellis impact strength at a test temperature of 23℃ is calculated using the following formula.
[0471] Rate of change (%) = (Edwards impact strength - Edwards impact strength of the reference example) × 100 / Edwards impact strength of the reference example Regarding the Elodea impact strength of the reference examples in the above formula, the Elodea impact strength of Reference Example 1B was used in Examples 1B to 20B and Comparative Examples 1B to 7B, and the Elodea impact strength of Reference Example 1C was used in Examples 1C to 18C and Comparative Examples 1C to 3C. It should be noted that the larger the value of the rate of change (%), the better the Elodea impact strength is judged.
[0472] [Rate of change in tensile elongation] The rate of change of tensile elongation is calculated using the following formula.
[0473] Change rate (%) = (Elongation at break - Elongation at break of reference example) × 100 / Elongation at break of reference example Regarding the tensile elongation of the reference examples in the above formula, the tensile elongation of reference example 1B was used in Examples 1B to 20B and Comparative Examples 1B to 7B, and the tensile elongation of reference example 1C was used in Examples 1C to 18C and Comparative Examples 1C to 3C. It should be noted that the larger the value of the rate of change (%), the better the assessment of the tensile elongation.
[0474] [Balance between impact resistance and elongation] For resin compositions, high impact resistance and high elongation are required.
[0475] As an indicator of their balance, the value of the balance index (1) based on the following formula was obtained in Examples 1B to 20B, Reference Example 1B and Comparative Examples 1B to 7B, respectively, and the value of the balance index (2) based on the following formula was obtained in Examples 1C to 18C, Reference Example 1C and Comparative Examples 1C to 3C, to evaluate the balance between the impact resistance and elongation of the resin composition.
[0476] Balance index (1) (10) 4 • J / m • % = Ellis impact strength (J / m) × tensile elongation (%) × 10 -4 Balance index (2) (10) 4 ·J / m·%) = (((Edwards impact strength (23℃) (J / m)) 2 + (Ironclad impact strength (-30℃) (J / m)) 2 ) / 2) 1 / 2 ×Elongation at break (%) ×10 -4 In the formula of the above balance index (1), "Edwards impact strength" is the Edwards impact strength measured by the above method at a test temperature of 23℃.
[0477] In the formula of the above balance index (2), "Edwards impact strength (23℃)" is the Edwards impact strength at a test temperature of 23℃, and "Edwards impact strength (-30℃)" is the Edwards impact strength at a test temperature of -30℃.
[0478] The larger the values of the balance index (1) and the balance index (2), the better the balance between the impact resistance and elongation of the resin composition.
[0479] As shown in Tables 2-1, 2-2, 3-1 and 3-2, it can be seen that the resin composition of the examples has higher Elliott impact strength and tensile elongation at 23°C than the resin composition of the comparative examples, and exhibits excellent impact resistance and elongation at room temperature.
[0480] Furthermore, as shown in Tables 3-1 and 3-2, it can be seen that the Elchample impact strength of the resin compositions of the Examples at -30°C is higher than that of the resin compositions of the Comparative Examples, and the low-temperature impact resistance is also excellent. Specifically, the Elchample impact strength and tensile elongation of Examples 1B-20B and Examples 1C-18C are higher than those of Comparative Examples 1B-7B and Comparative Examples 1C-3C, thus confirming that simply having the ethylene-propylene copolymer and the terminally unsaturated polypropylene exist independently does not have the effect of improving impact resistance and elongation. However, by including the grafted olefin polymer [R1], both impact resistance and elongation are improved. In addition, as shown in Comparative Examples 4B and 5B, when the ethylene composition of the main chain of the grafted olefin polymer [R1] is as high as 100 mol%, although elongation is observed, the impact resistance is poor. The resin compositions of the Examples achieve a balance between impact resistance and elongation. Furthermore, as can be seen from Comparative Examples 6B and 7B, when the molecular weight of the olefin resin (β) is too low, both the impact resistance and elongation are poor. The resin composition of the examples achieves a balance between impact resistance and elongation.
[0481] The results obtained by observing the phase structure of the resin compositions obtained in Example 1B, Reference Example 1B, Comparative Example 1B, Example 1C, Reference Example 1C, and Comparative Example 1C using a transmission electron microscope are shown below. Figure 1 , Figure 2 , Figure 3 and Figure 4 , Figure 5 , Figure 6 middle. Figure 1 , Figure 2 , Figure 3 It has a phase separation structure comprising an ocean phase formed by propylene resin components and an island phase formed by ethylene resin components. However, compared with Reference Example 1B and Comparative Example 1B, the phase formed by ethylene resin components has a smaller dispersed particle size and is well dispersed. Figure 4 , Figure 5 , Figure 6 The composition exhibits a phase-separated structure comprising an ocean phase formed from ethylene-based resin components and an island phase formed from propylene-based resin components. However, compared to Reference Example 1C and Comparative Example 1C, the phase formed from propylene-based resin components in Example 1C has a smaller dispersed particle size and is well dispersed. The above results confirm that the presence of the grafted olefin polymer [R1-1] improves compatibility and enhances the impact resistance and elongation of the resin composition.
[0482] [Table 2-1] [Table 2-2] [Table 3-1] [Table 3-2] [Examples 1D~7D and Comparative Examples 1D~6D] Preparation of resin composition A resin composition was prepared by loading the raw materials listed in Table 4 into a Labo Plastomill manufactured by Toyo Seiki Co., Ltd. at the proportions (parts by mass) listed in Table 4, and then melting and mixing the mixture at 200°C and 60 rpm for about 5 minutes.
[0483] The olefin resins (β-20) to (β-23), (β-25) to (β-27), (β'-2), and (β'-10) to (β'-14) of the raw materials are the olefin resins obtained in Examples 20A to 23A, Examples 25A to 27A, Comparative Example 2A, Comparative Example 4A to 5A, and Comparative Example 10A to 12A, respectively.
[0484] The following substances are used as raw materials for propylene-based polymers (α1-2), propylene-based polymers (α1-3), and ethylene-based polymers (α2-2).
[0485] [Propylene polymers (α1-2)] Random polypropylene (MFR (230℃, 2.16kg load, according to ASTM D1238): 7g / 10min, melting point: 140℃, propylene content: 95 mol%, ethylene content: 1 mol%, 1-butene content: 4 mol%) [Propylene polymers (α1-3)] Propylene polymers (α1-3) prepared according to the method of propylene polymer 1 described in the Example section of Japanese Patent Application Publication No. 2024-116045 (MFR (230°C, 2.16 kg load, according to ASTM D1238): 6 g / 10 min) [Vinyl polymers (α2-2)] Ethylene-propylene copolymer (melting point: 44℃, density 869kg / m³) 3 Ethylene content = 81 mol%, propylene content = 19 mol%, MFR (190℃, 2.16 kg load) = 0.6 g / 10 minutes Determination of the physical properties of molded parts The molded physical properties of the prepared resin composition were determined using the following method. The results are shown in Table 4.
[0486] [Whitening resistance] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 0.5 mm.
[0487] After being left at room temperature for more than 7 days from the time of molding, dumbbells of shape 2 as specified in JIS K6251 were made from the above-mentioned sheet. For this dumbbell, the hue before elongation (L value (before elongation)) and the hue after elongation by 15 mm at 23°C and a stretching speed of 50 mm / min were measured using a spectrophotometer (KONICA MINOLTA Co., Ltd., CM-3700A). The hue change (ΔL) was calculated based on the following formula. The smaller the ΔL value, the better the whitening resistance of the above polymer composition.
[0488] ΔL = L value (after elongation) - L value (before elongation) [Tension Test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 2 mm.
[0489] After 72 hours from the time of molding at room temperature, the sheet material is subjected to a tensile test under the following conditions according to JIS K7162. The elastic modulus and breaking stress are determined from this test.
[0490] <Measurement Conditions> Test piece: JIS K7162-5A dumbbell 5mm (width) × 2mm (thickness) × 75mm (length) Stretching speed: 50mm / minute Spacing between fixtures: 50mm Distance between markings: 20mm Temperature: 23℃ [High-speed surface impact test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 0.5 mm.
[0491] After 72 hours from the time of molding at room temperature, the produced sheet is subjected to a high-speed surface impact test under the following conditions, according to JIS K7211-2. The puncture point energy is determined from this test.
[0492] <Measurement Conditions> Impactor diameter: 20mmΦ Support platform diameter: 40mmΦ Test speed: 4.4 m / s Temperature: -20℃ [Impact resistance and stress balance] For resin compositions, high impact resistance and high stress resistance are required.
[0493] As an indicator of their balance, the impact resistance and stress balance of the resin composition were evaluated by determining the value of the balance index (3) based on the following formula in Examples 1D to 7D and Comparative Examples 1D to 6D.
[0494] Balance index (3) [10·J·MPa] = Penetration point energy (J) × Destructive stress (MPa) × 10 -1 The larger the value of the balance index (3), the better the balance between impact resistance and stress.
[0495] [Whitening resistance, elastic modulus, impact resistance, and stress balance] For resin compositions, high resistance to whitening, high elastic modulus, high impact resistance, and high stress are required.
[0496] As an indicator of their balance, the value of the balance index (4) based on the following formula was obtained in Examples 1D to 7D and Comparative Examples 1D to 6D to evaluate the whitening resistance, elastic modulus, impact resistance and stress balance of the resin composition.
[0497] Balance index (4)
[10] 3 ·J·MPa 2 = Puncture point energy (J) × breaking stress (MPa) × elastic modulus (MPa) / hue change (ΔL) (-) × 10 -3 The larger the value of the balance index (4), the better the balance of whitening resistance, elastic modulus, impact resistance and stress.
[0498] As shown in Table 4, the resin compositions of the Examples exhibit a smaller ΔL value and superior whitening resistance compared to the resin compositions of the Comparative Examples. Furthermore, as shown in Table 4, the resin compositions of the Examples demonstrate higher balance in elastic modulus / puncture point energy and breaking stress / puncture point energy compared to the resin compositions of the Comparative Examples, and also exhibit superior balance in impact resistance and strength. Specifically, Examples 1D-7D, compared to Comparative Examples 1D-6D, exhibited smaller ΔL values and higher balance in elastic modulus / puncture point energy and breaking stress / puncture point energy. This confirms that simply having the ethylene-propylene copolymer and the terminally unsaturated polypropylene exist independently does not improve the balance of whitening resistance, impact resistance, and strength; however, by including the grafted olefin polymer [R1], the balance of whitening resistance, impact resistance, and strength is improved.
[0499] [Table 4] [Refer to Example 1E, Examples 1E~14E and Comparative Examples 1E~7E] Preparation of resin composition A resin composition was prepared by loading the raw materials listed in Tables 5-1 and 5-2 into a Labo Plastomill manufactured by Toyo Seiki Co., Ltd., according to the proportions (parts by mass) listed in Tables 5-1 and 5-2, and then melting and mixing the mixture at 200°C and 60 rpm for about 5 minutes.
[0500] The olefin resins (β-19) to (β-26), (β'-2), and (β'-9) to (β'-13) of the raw materials are the olefin resins obtained in Examples 19A to 26A, Comparative Examples 2A to 5A, and Comparative Examples 10A to 11A, respectively.
[0501] The following substances are used as raw materials for propylene-based polymers (α1-4) and ethylene-based polymers (α2-3).
[0502] [Propylene polymers (α1-4)] Block polypropylene (MFR (230℃, 2.16kg load, according to ASTM D1238): 3.5g / 10min, density: 900kg / m³) 3 (Amorphous part viscosity η: 2.8 dL / g, propylene:ethylene (molar ratio) 81.1:18.9) [Vinyl polymers (α2-3)] Ethylene-1-butene copolymer (MFR (190℃, 2.16kg load) = 1.2g / 10min, density 885kg / m³) 3 ) Determination of the physical properties of molded parts The physical properties of the prepared resin compositions were determined using the following methods. The results are shown in Tables 5-1 and 5-2.
[0503] [Tension Test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 2 mm.
[0504] After 72 hours from the time of molding at room temperature, the sheet produced is subjected to a tensile test under the following conditions according to JIS K7162. The elastic modulus and tensile elongation are determined from this test.
[0505] <Measurement Conditions> Test piece: JIS K7162-5A dumbbell 5mm (width) × 2mm (thickness) × 75mm (length) Stretching speed: 50mm / minute Spacing between fixtures: 50mm Distance between markings: 20mm [High-speed surface impact test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 0.5 mm.
[0506] After 72 hours from the time of molding at room temperature, the produced sheet is subjected to a high-speed surface impact test under the following conditions, according to JIS K7211-2. The puncture point energy is determined from this test.
[0507] <Measurement Conditions> Impactor diameter: 20mmΦ Support platform diameter: 40mmΦ Test speed: 4.4 m / s Temperature: -20℃ [Rate of change in tensile elongation] In Table 5-1, the rate of change of tensile elongation is calculated using the following formula.
[0508] Change rate (%) = (Elongation at break - Elongation at break of reference example 1E) × 100 / Elongation at break of reference example 1E It should be noted that the larger the change rate (%), the better the assessment of tensile elongation.
[0509] Rate of change of tensile modulus of elasticity In Table 5-1, the rate of change of the tensile modulus of elasticity is calculated using the following formula.
[0510] Rate of change (%) = (Tensive modulus of elasticity - Tensile modulus of elasticity of Reference Example 1E) × 100 / Tensile modulus of elasticity of Reference Example 1E [Rate of change of failure stress] In Table 5-1, the rate of change of the failure stress is calculated using the following formula.
[0511] Rate of change (%) = (failure stress - failure stress of reference example 1E) × 100 / failure stress of reference example 1E It should be noted that the larger the value of the rate of change (%), the better the judgment of the destructive stress.
[0512] [Rate of change of energy at the puncture point] In Table 5-1, the rate of change of energy at the puncture point is calculated using the following formula.
[0513] Rate of change (%) = (puncture point energy - puncture point energy of reference example 1E) × 100 / puncture point energy of reference example 1E It should be noted that the larger the change rate (%), the better the judgment of the energy at the puncture point.
[0514] [Impact resistance and stress balance] For resin compositions, high impact resistance and high stress resistance are required.
[0515] As an indicator of their balance, the impact resistance and stress balance of the resin composition were evaluated by determining the value of the balance index (5) based on the following formula in Reference Example 1E, Examples 1E to 14E and Comparative Examples 1E to 7E.
[0516] Balance index (5)
[10] 2 [·J·MPa] = Penetration point energy (J) × Destructive stress (MPa) × 10 -2 The larger the value of the balance index (5), the better the balance between impact resistance and stress.
[0517] [Elongation, flexibility, impact resistance, and stress balance] For resin compositions, high elongation, high flexibility, high impact resistance, and high stress are required.
[0518] As an indicator of their balance, the softness, impact resistance and stress balance of the resin composition were evaluated by determining the value of the balance index (6) based on the following formula in Reference Example 1E, Examples 1E to 14E and Comparative Examples 1E to 7E.
[0519] Balance index (6) [%·J] = tensile elongation (%) × puncture point energy (J) × breaking stress (MPa) / elastic modulus (MPa) The larger the value of the balance index (6), the better the balance of elongation, softness, impact resistance and stress.
[0520] As shown in Tables 5-1 and 5-2, it can be seen that the resin compositions of the Examples have higher balances in elastic modulus / puncture point energy, breaking stress / puncture point energy, and elongation / puncture point energy compared to the resin compositions of the Comparative Examples, and exhibit superior balances in impact resistance, strength, and elongation. Specifically, Examples 1E to 14E have higher balances in elastic modulus / puncture point energy, breaking stress / puncture point energy, and elongation / puncture point energy compared to Comparative Examples 1E to 7E. It has been confirmed that simply having the ethylene-propylene copolymer and the terminally unsaturated polypropylene exist independently does not improve the balance of impact resistance, strength, and elongation. However, by including the grafted olefin polymer [R1], the balance of impact resistance, strength, and elongation is improved.
[0521] [Table 5-1] [Table 5-2] [Examples 1F~4F, Comparative Examples 1F~2F] Preparation of resin composition A resin composition was prepared by loading the raw materials listed in Table 6 into a Labo Plastomill manufactured by Toyo Seiki Co., Ltd. at the proportions (parts by mass) listed in Table 6, and then melting and mixing the mixture at 200°C and 60 rpm for about 5 minutes.
[0522] The olefin resins (β-20) and (β-25) of the raw materials are the olefin resins obtained in Examples 20A and 25A above, respectively.
[0523] The following substances are used as raw materials for propylene-based polymers (α1-5) and ethylene-based polymers (α2-4).
[0524] [Propylene polymers (α1-5)] Block polypropylene (melting point: 162℃, MFR (230℃, 2.16kg load): 54g / 10min), density: 900kg / m³ 3 ) [Vinyl polymers (α2-4)] Ethylene-1-butene copolymer (MFR (190℃, 2.16kg load) = 0.6g / 10min, density 861kg / m³) 3 ) Determination of the physical properties of molded parts The molded physical properties of the prepared resin composition were determined using the following method. The results are shown in Table 6.
[0525] [Edwards impact strength] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 3 mm.
[0526] After 72 hours from molding at room temperature, the Ellowch impact strength (for a total of 4 tests) of the produced sheet was determined under the following conditions according to ASTM D256. Furthermore, the failure mode after each of the 4 tests was visually confirmed.
[0527] <Experimental Conditions> Hammering capacity: 3.92J Swing angle: 149.0 degrees The gap is for machining. Temperature: -40℃ [Bending Test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 3 mm.
[0528] After 72 hours from the time of molding at room temperature, the sheet produced is subjected to a bending test under the following conditions in accordance with ASTM D-790 to determine the flexural modulus (MPa).
[0529] <Experimental Conditions> Span: 48mm Test speed: 5 mm / min Temperature: 23℃ [Tension Test] Using a hydraulic thermoforming machine set to 200°C, the resin composition was heated for 6 minutes and then molded for 2 minutes under a pressure of 10 MPa. It was then cooled for 2 minutes under a pressure of 10 MPa at 20°C to produce a sheet with a thickness of 2 mm.
[0530] After 72 hours from the time of molding at room temperature, the sheet produced is subjected to a tensile test under the following conditions according to JIS K7162. The elastic modulus and tensile elongation are determined from this test.
[0531] <Measurement Conditions> Test piece: JIS K7162-5A dumbbell 5mm (width) × 2mm (thickness) × 75mm (length) Stretching speed: 50mm / minute Spacing between fixtures: 50mm Distance between markings: 20mm [Balance between impact resistance and elongation] For resin compositions, high impact resistance and high elongation are required.
[0532] As an indicator of their balance, the balance index (7) based on the following formula was determined in Examples 1F to 4F and Comparative Examples 1F to 2F to evaluate the balance between the impact resistance and elongation of the resin composition.
[0533] Balance index (7)
[10] 4 [·J / m·%] = Average of the total 4 Ellis impact strengths (J / m) × Elongation at break (%) × 10 -4 The larger the value of the balance index (7), the better the balance between impact resistance and elongation.
[0534] [Elongation, flexibility, impact resistance, and stress balance] For resin compositions, high elongation, high flexibility, high impact resistance, and high stress are required.
[0535] As an indicator of their balance, the elongation, softness, impact resistance and stress balance of the resin composition were evaluated by obtaining the value of the balance index (8) based on the following formula in Examples 1F to 4F and Comparative Examples 1F to 2F.
[0536] Balance index (8)
[10] 3 [J / m%] = Ellis impact strength (J / m) × tensile elongation (%) × breaking stress (MPa) / flexural modulus (MPa) × 10 -3 The larger the value of the balance index (8), the better the balance of elongation, softness, impact resistance and stress.
[0537] As shown in Table 6, it can be seen that the resin compositions of the embodiments have high balance in flexural modulus / Each impact strength measured at -40°C, balance in flexural modulus / breaking stress, and balance in flexural modulus / elongation, and excellent balance in low-temperature impact resistance, strength, and elongation.
[0538] [Table 6]
Claims
1. Olefin resins (β), comprising grafted olefin polymers having a main chain and side chains [R1], The olefin resin (β) satisfies all of the following requirements (I) to (IV): (I) The main chain of the grafted olefin polymer [R1] is composed of ethylene-propylene copolymer or ethylene-1-butene copolymer; (II) The side chains of the grafted olefin polymer [R1] are composed of propylene homopolymer or propylene-ethylene copolymer; (III) The total content of P of the following components (i) to (iv) in the olefin resin (β) is in the range of 10 to 80% by mass: (i) A propylene homopolymer constituting the side chains of the grafted olefin polymer [R1]; (ii) A propylene-ethylene copolymer constituting the side chain of the grafted olefin polymer [R1]; (iii) Terminal unsaturated propylene homopolymers that do not constitute the grafted olefin polymer [R1]; (iv) Terminally unsaturated propylene-ethylene copolymers that do not constitute the grafted olefin polymer [R1]; (IV) The intrinsic viscosity [η] of the olefin resin (β) measured at 135 °C in decahydronaphthalene is 0.5~5.0 dL / g.
2. The olefin-based resin (β) as described in claim 1, wherein, The main chain of the grafted olefin polymer [R1] is an ethylene-propylene copolymer. The content of ethylene-derived structural units in the ethylene-propylene copolymer is 70-99 mol%. The content of propylene-derived structural units in the ethylene-propylene copolymer is 1 to 30 mol.
3. The olefin-based resin (β) as described in claim 2, wherein, The weight-average molecular weight (Mw) of the ethylene-propylene copolymer constituting the backbone of the grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in terms of polyethylene equivalents, is 50,000 to 250,000.
4. The olefin-based resin (β) as described in claim 2, wherein, The total content of P in the olefin resin (β) of the components (i) to (iv) is 10 to 60% by mass.
5. The olefin-based resin (β) as described in claim 2, wherein, The melt flow rate (MFR) of the olefin resin (β), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 0.01~30 g / 10 min.
6. The olefin-based resin (β) as described in claim 2, wherein, The content of ethylene-derived structural units in the ethylene-propylene copolymer is 75-85 mol%. The content of propylene-derived structural units in the ethylene-propylene copolymer is 15-25 mol%. The intrinsic viscosity [η] of the olefin resin (β), measured at 135 °C in decahydronaphthalene, is 0.9~1.25 dL / g.
7. The olefinic resin (β) as described in claim 1, wherein, The main chain of the grafted olefin polymer [R1] is an ethylene-1-butene copolymer. The content of ethylene-derived structural units in the ethylene-1-butene copolymer is 70-90 mol%. The content of 1-butene structural units in the ethylene-1-butene copolymer is 10-30 mol%. The weight-average molecular weight (Mw) of the ethylene-1-butene copolymer, determined by gel permeation chromatography (GPC) in terms of values converted to polyethylene, is 30,000 to 120,000.
8. The olefinic resin (β) as described in claim 7, wherein, The melt flow rate (MFR) of the olefin resin (β), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 2.5~30 g / 10 min.
9. The olefinic resin (β) as described in claim 7, wherein, The content of ethylene-derived structural units in the ethylene-1-butene copolymer is 78-87 mol%. The content of structural units derived from 1-butene in the ethylene-1-butene copolymer is 13-22 mol.
10. The olefinic resin (β) according to claim 7, wherein, The intrinsic viscosity [η] of the olefin resin (β), measured at 135°C in decahydronaphthalene, is 0.5~1.25 dL / g.
11. The olefinic resin (β) according to any one of claims 1 to 10, wherein, The content of propylene-derived structural units in the side chains of the grafted olefin polymer [R1] is 80-100 mol%. The content of ethylene-derived structural units in the side chains of the grafted olefin polymer [R1] is 0-20 mol%. The weight-average molecular weight (Mw) of the polymer or copolymer constituting the side chain of the grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is in the range of 5,000 to 50,000.
12. A method for manufacturing the olefinic resin (β) according to any one of claims 1 to 10, comprising the steps of (A) and (B) below: (A) In the presence of a catalyst for olefin polymerization containing a transition metal compound [A] of Group 4 of the periodic table, which includes a ligand having a dimethylsilyl diindenyl skeleton, The process of polymerizing propylene to produce terminally unsaturated polypropylene, or the process of copolymerizing propylene with ethylene to produce terminally unsaturated propylene-ethylene copolymer. (B) In the presence of a catalyst for olefin polymerization containing a bridged metallocene compound represented by the following general formula [B], The process of copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer manufactured in step (A) with ethylene and propylene, or the process of copolymerizing the terminally unsaturated polypropylene or terminally unsaturated propylene-ethylene copolymer manufactured in step (A) with ethylene and 1-butene. [Chemical Formula 1] In formula [B], R 1 R 2 R 3 R 4 R 5 R 8 R 9 and R 12 Each independently represents a hydrogen atom, a hydrocarbon group, a silicon-containing group, or a group containing heteroatoms other than a silicon-containing group, R 1 ~R 4 Two adjacent groups in R can bond with each other to form a ring; 6 and R 11 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 7 and R 10 R is selected from the same atom or the same group selected from hydrogen atom, hydrocarbon group, silicon-containing group and heteroatom-containing group other than silicon-containing group. 6 and R 7 They can bond together to form a ring, R 10 and R 11 They can bond together to form a ring; among them, Excluding R 6 R 7 R 10 and R 11 The case where all atoms are hydrogen; R 13 and R 14 Each independently represents an aryl group; Y 1 Indicates a carbon atom or a silicon atom; M 1 It represents a zirconium atom or a hafnium atom; Q represents a halogen atom, a hydrocarbon group, a halohydrocarbon group, a neutral conjugated or non-conjugated diene with 4 to 10 carbon atoms, an anionic ligand, or a neutral ligand that can coordinate with lone pair electrons; j represents an integer from 1 to 4. When j is an integer greater than 2, there may be multiple Qs, each of which may be the same or different.
13. A resin composition (X) comprising: The olefin resin (β) according to any one of claims 1 to 10 Propylene polymers (α1), and Vinyl polymers (α2).
14. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-propylene copolymer backbone. The ratio of the total mass of the olefin resin (β) to the total mass of the propylene polymer (α1) and the ethylene polymer (α2) ((β) / ((α1)+(α2))) is 0.02~0.
23.
15. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-propylene copolymer backbone. The melt flow rate (MFR) of the propylene polymer (α1), as determined by ASTM D1238 at 230°C and a load of 2.16 kg, is 0.01~20 g / 10 min.
16. The resin composition (X) of claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-propylene copolymer backbone. The melt flow rate (MFR) of the ethylene polymer (α2), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 0.01~2.0 g / 10 min.
17. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The ratio of the total mass of the olefin resin (β) to the total mass of the propylene polymer (α1) and the ethylene polymer (α2) ((β) / ((α1)+(α2))) is 0.08~0.
20.
18. The resin composition (X) of claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The melt flow rate (MFR) of the propylene polymer (α1), as determined by ASTM D1238 at 230°C and a load of 2.16 kg, is 0.01~25 g / 10 min.
19. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The melt flow rate (MFR) of the ethylene polymer (α2), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 0.5 to 100 g / 10 minutes.
20. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The density of the ethylene polymer (α2), as determined by ASTM D1505 at 25°C, is 850~900 kg / m³. 3 .
21. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The melt flow rate (MFR) of the propylene polymer (α1), as determined by ASTM D1238 at 230°C and a load of 2.16 kg, is 0.01~25 g / 10 min. The density of the ethylene polymer (α2), as determined by ASTM D1505 at 25°C, is 850~900 kg / m³. 3 .
22. The resin composition (X) according to claim 13, wherein, The grafted olefin polymer [R1] in the olefin resin (β) has an ethylene-1-butene copolymer as its main chain. The ratio of the total mass of the olefin-based resin (β) to the total mass of the propylene-based polymer (α1) and the ethylene-based polymer (α2) ((β) / ((α1)+(α2)))) is 0.08~0.
20. The melt flow rate (MFR) of the ethylene polymer (α2), as determined by ASTM D1238 at 190°C and a load of 2.16 kg, is 0.5 to 100 g / 10 minutes.
23. The resin composition (X) according to any one of claims 13 to 22, wherein, The content of propylene-derived structural units in the side chains of the grafted olefin polymer [R1] is 80-100 mol%. The content of ethylene-derived structural units in the side chains of the grafted olefin polymer [R1] is 0-20 mol%. The weight-average molecular weight (Mw) of the polymer or copolymer constituting the side chain of the grafted olefin polymer [R1], as determined by gel permeation chromatography (GPC) in terms of polypropylene equivalents, is in the range of 5,000 to 50,000.
24. The olefinic resin (β) according to any one of claims 1 to 10, used for packaging of lithium-ion batteries.
25. The resin composition (X) according to any one of claims 13 to 22, used in the packaging of a lithium-ion battery.
26. A molded article comprising an olefinic resin (β) according to any one of claims 1 to 10, or a resin composition (X) according to any one of claims 13 to 22.
27. A packaging for lithium-ion batteries, comprising an olefinic resin (β) according to any one of claims 1 to 10, or a resin composition (X) according to any one of claims 13 to 22.
28. An energy storage device comprising the lithium-ion battery packaging as described in claim 27.
Citation Information
Patent Citations
Method of making plateeshaped molding material
JP1979066986A
Anti-wear knitted fabric
JP1983060043A
Catalysts, these catalysts and production of these catalyst polymerization process
JP1989501950A
Catalysts, these catalysts for production, and use of these catalysts
JP1989502036A
Production of benzene-insoluble organoaluminumoxy compound
JP1990078687A